Manufacture method of positive electrode active material and manufacture method of lithium-ion battery
Patent Information
- Application Number
- JP2024131683
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-22
- Filing Date
- 2024-08-08
- Publication Date
- 2025-02-21
AI Technical Summary
【0019】 本発明の一態様により、低温環境においても優れた充放電特性を有するリチウムイオン電池を提供することができる。具体的には、低温環境で放電しても放電容量および/または放電エネルギー密度の大きいリチウムイオン電池に適用可能な正極、負極、及び電解液等を提供することができる。または、低温環境で充電しても充電容量および/または充電エネルギー密度の大きいリチウムイオン電池に適用可能な正極、負極、及び電解液等を提供することができる。
Smart Images

Figure 2025026411000001_ABST
Abstract
Description
[Technical field]
[0001] One embodiment of the present invention relates to a lithium ion battery (also referred to as a lithium ion secondary battery). The present invention is not limited to the above fields, and relates to a semiconductor device, a display device, a light-emitting device, a power storage device, a lighting device, an electronic device, a vehicle, and a manufacturing method thereof. The above-mentioned semiconductor device, display device, light-emitting device, power storage device, lighting device, electronic device, and vehicle can use the lithium ion battery which is one embodiment of the present invention as a necessary power source. For example, the above-mentioned electronic device includes an information terminal device equipped with a lithium ion battery. Furthermore, the above-mentioned power storage device includes a stationary power storage device. [Background technology]
[0002] In recent years, various types of storage batteries have been actively developed, including lithium-ion batteries, lithium-ion capacitors, air batteries, and all-solid-state batteries. In particular, the demand for high-output, high-capacity lithium-ion batteries has rapidly increased along with the development of the semiconductor industry, and they have become indispensable in the modern information society as a rechargeable energy source.
[0003] It is known that the discharge capacity of lithium ion batteries varies depending on the temperature during discharge. Therefore, there is a demand for lithium ion batteries that have excellent battery characteristics even in low-temperature environments (for example, see Patent Document 1).
[0004] Furthermore, in order to increase the capacity of lithium-ion batteries at room temperature and to improve their charge-discharge cycle characteristics, various research and development efforts are being conducted on both the positive and negative electrodes. Lithium cobalt oxide, which has a stable crystal structure, has been considered as a positive electrode active material (see, for example, Patent Document 2).
[0005] Furthermore, fluorides such as fluorite (calcium fluoride) have long been used as fluxes in the iron-making industry and their physical properties have been studied (for example, Non-Patent Document 1).
[0006] Furthermore, as negative electrode active materials, silicon-based materials are known to have higher capacity than graphite-based materials, and negative electrodes using silicon-based materials are being investigated (see, for example, Patent Document 3). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2015-026608 A [Patent Document 2] WO2020 / 026078 Brochure [Patent Document 3] JP 2019-165005 A [Non-patent literature]
[0008] [Non-Patent Document 1] WE Counts, R. Roy, and EF Osborn, "Fluoride Model Systems: II, The Binary Systems CaF2-BeF2, MgF2-BeF2, and LiF-MgF2," Journal of the American Ceramic Society, 36 [1] 12-17 (1953). Summary of the Invention [Problem to be solved by the invention]
[0009] Patent Document 1 describes that a lithium ion battery capable of operating in a low temperature environment (for example, below 0° C.) has been realized by using the electrolyte solution described in Patent Document 1. However, even the lithium ion battery described in Patent Document 1 does not have a large discharge capacity when discharged in a low temperature environment at the time of filing the present application, and further improvement is desired.
[0010] In order to realize a lithium-ion battery having excellent charge / discharge characteristics even in a low-temperature environment, it is necessary to develop not only an electrolyte but also a positive electrode and a negative electrode suitable for a lithium-ion battery that can operate in a low-temperature environment. In addition, it is desirable for the positive electrode to have a positive electrode active material that can be charged and discharged at a high voltage. By using a positive electrode active material that can be charged and discharged at a high voltage, a lithium-ion battery with a large charge capacity and / or charge energy density can be obtained.
[0011] In view of the above, an object of one embodiment of the present invention is to provide a lithium-ion battery having excellent charge / discharge characteristics even in a low-temperature environment. Specifically, an object of the present invention is to provide a positive electrode, a negative electrode, an electrolyte, etc. that can be applied to a lithium-ion battery that has a large discharge capacity even when discharged in a low-temperature environment. Alternatively, an object of the present invention is to provide a positive electrode, a negative electrode, an electrolyte, etc. that can be applied to a lithium-ion battery that has a large charge capacity and / or a large charge energy density even when charged in a low-temperature environment.
[0012] Note that the description of these problems does not preclude the existence of other problems. In addition, it is not necessary for one embodiment of the present invention to solve all of these problems. In addition, it is possible to extract problems other than these from the description of this specification, drawings, claims, etc. [Means for solving the problem]
[0013] One aspect of the present invention is a method for producing a positive electrode active material using a setter that accommodates an object to be heated, the method comprising: a first step of heating lithium cobalt oxide having a median diameter of 10 μm or less at a temperature of 700° C. to 1000° C. for 1 hour to 5 hours; a second step of mixing a fluorine source and a magnesium source with the lithium cobalt oxide that has been subjected to the first step to produce a first mixture; a third step of heating the first mixture at a temperature of 800° C. to 1100° C. for 1 hour to 10 hours; and a third step of mixing a nickel source and an aluminum source with the first mixture that has been subjected to the third step. the third step is performed in a state in which the first mixture is contained in a first setter so that the thickness of the first mixture is 2.0 mm or less, the fifth step is performed in a state in which the second mixture is contained in a second setter so that the thickness of the second mixture is 2.0 mm or less, and the first step, the third step, and the fifth step are performed in an atmosphere containing oxygen.
[0014] In the above, the number of magnesium atoms contained in the magnesium source is preferably 0.3% or more and 3% or less of the number of cobalt atoms contained in the lithium cobalt oxide that has been subjected to the first step.
[0015] In the above, the number of nickel atoms in the nickel source is preferably 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide that has been subjected to the first step.
[0016] In the above-mentioned method for producing a positive electrode active material, the number of aluminum atoms in the aluminum source is 0.05% to 4% of the number of cobalt atoms in the lithium cobalt oxide that has been subjected to the first step.
[0017] Alternatively, one aspect of the present invention is a method for producing a lithium ion battery including a positive electrode, an electrolyte, a negative electrode, a separator, and an exterior body, the method including: dispersing the positive electrode active material produced by any one of the above methods, a conductive material, and polyvinylidene fluoride in an organic solvent to prepare a positive electrode slurry, applying the positive electrode slurry on a positive electrode current collector, and drying to prepare a positive electrode; dispersing graphite particles, silicon particles, and polyacrylic acid in water to prepare a negative electrode slurry, applying the negative electrode slurry on a negative electrode current collector, and drying to prepare a negative electrode; and mixing a lithium salt, a fluorinated cyclic carbonate, and a fluorinated chain carbonate to prepare an electrolyte, wherein the positive electrode and the negative electrode are stacked with the separator interposed therebetween to prepare a laminate, and the laminate and the electrolyte are housed inside the exterior body.
[0018] In the above-mentioned method for producing a lithium ion battery, it is preferable that the lithium salt includes LiPF6, the fluorinated cyclic carbonate includes fluoroethylene carbonate, and the fluorinated chain carbonate includes methyl trifluoropropionate. Effect of the Invention
[0019] According to one embodiment of the present invention, a lithium ion battery having excellent charge / discharge characteristics even in a low-temperature environment can be provided. Specifically, a positive electrode, a negative electrode, an electrolyte solution, etc. applicable to a lithium ion battery having a large discharge capacity and / or a large discharge energy density even when discharged in a low-temperature environment can be provided. Alternatively, a positive electrode, a negative electrode, an electrolyte solution, etc. applicable to a lithium ion battery having a large charge capacity and / or a large charge energy density even when charged in a low-temperature environment can be provided.
[0020] Note that the description of these effects does not preclude the existence of other effects. One embodiment of the present invention does not necessarily have all of these effects. Effects other than these can be extracted from the description in the specification, drawings, and claims. [Brief description of the drawings]
[0021] [Figure 1] 1A to 1D are diagrams illustrating a method for manufacturing a positive electrode active material. [Diagram 2] Figure 2(A) is a schematic cross-sectional view of a heating furnace, Figure 2(B) is a top view of the lid, and Figure 2(C) is a schematic cross-sectional view explaining the heights of the container, the lid, and the object to be heated. [Diagram 3] Fig. 3(A) is a diagram illustrating an example of a manufacturing apparatus, and Fig. 3(B) is a diagram illustrating the arrangement of rollers. [Figure 4] FIG. 4 is a diagram illustrating an example of a manufacturing apparatus. [Diagram 5] FIG. 5 is a diagram illustrating a method for producing a positive electrode active material. [Figure 6] 6A to 6C are diagrams illustrating a method for manufacturing a positive electrode active material. [Figure 7] FIG. 7 is a phase diagram showing the relationship between the composition of lithium fluoride and magnesium fluoride and the temperature. [Figure 8] FIG. 8 is a diagram illustrating the results of the DSC analysis. [Figure 9] FIG. 9(A) is a cross-sectional view illustrating the internal structure of a lithium ion battery, and FIG. 9(B) is a cross-sectional view illustrating a positive electrode active material, an electrolyte solution, and the like of the lithium ion battery. [Figure 10] 10(A) and 10(B) are cross-sectional views illustrating the positive electrode active material. [Figure 11] 11A to 11F are cross-sectional views illustrating the positive electrode active material. [Figure 12] FIG. 12 is a diagram illustrating the crystal structure of the positive electrode active material. [Figure 13] FIG. 13 is a diagram illustrating the crystal structure of a conventional positive electrode active material. [Figure 14] FIG. 14 shows an XRD pattern calculated from the crystal structure. [Figure 15] FIG. 15 shows an XRD pattern calculated from the crystal structure. [Figure 16] FIG. 16 is a diagram illustrating a method for producing a negative electrode active material. [Figure 17] 17(A) to 17(E) are diagrams showing examples of the battery configuration. [Figure 18] 18(A) to 18(C) are diagrams showing examples of the battery configuration. [Figure 19] 19(A) to 19(C) are diagrams showing examples of the battery configuration. [Figure 20] 20(A) to 20(C) are diagrams showing examples of the battery configuration. [Figure 21] FIG. 21 is a diagram illustrating a film processing method. [Figure 22] 22(A) to 22(E) are diagrams for explaining a method of processing a film. [Diagram 23] Figures 23(A) and 23(B) are diagrams explaining a method for processing the film, and Figure 23(C) is a perspective view of a curved battery. [Figure 24] Figures 24(A) and 24(B) are diagrams explaining a method for processing the film, and Figure 24(C) is a perspective view of a curved battery. [Diagram 25] FIG. 25(A) is an exploded perspective view of a coin-type secondary battery, FIG. 25(B) is a perspective view of the coin-type secondary battery, and FIG. 25(C) is a cross-sectional perspective view thereof. [Figure 26] Fig. 26(A) shows an example of a cylindrical secondary battery. Fig. 26(B) shows an example of a cylindrical secondary battery. Fig. 26(C) shows an example of multiple cylindrical secondary batteries. Fig. 26(D) shows an example of a power storage system having multiple cylindrical secondary batteries. [Figure 27] 27(A) and 27(B) are diagrams for explaining an example of a secondary battery, and FIG. 27(C) is a diagram showing the inside of the secondary battery. [Figure 28] 28(A) to 28(C) are diagrams illustrating an example of a secondary battery. [Figure 29] 29(A) and 29(B) are diagrams showing the external appearance of a secondary battery. [Diagram 30] 30(A) to 30(C) are diagrams illustrating a method for manufacturing a secondary battery. [Diagram 31]31A to 31H are diagrams illustrating examples of electronic devices. [Diagram 32] 32A to 32D are diagrams illustrating examples of electronic devices. [Diagram 33] 33A to 33C are diagrams illustrating examples of electronic devices. [Diagram 34] 34(A) to 34(C) are diagrams illustrating an example of a vehicle. [Diagram 35] 35(A) to 35(D) are diagrams for explaining an example of space equipment. [Diagram 36] 36(A) and 36(B) are graphs showing the results of charge-discharge cycles in the example. [Figure 37] 37(A) and 37(B) are graphs showing the results of charge-discharge cycles in the example. [Figure 38] 38(A) and 38(B) are graphs showing the results of charge-discharge cycles in the example. [Figure 39] 39(A) and 39(B) are graphs showing the results of charge-discharge cycles in the example. [Diagram 40] 40(A) and 40(B) are graphs showing the results of the low-temperature charge-discharge test of the example. [Diagram 41] 41(A) and 41(B) are graphs showing the results of the low-temperature charge-discharge test of the example. [Diagram 42] FIG. 42(A) is a photograph of the battery produced in the example, and FIG. 42(B) and FIG. 42(C) are X-ray CT images of the battery before the impact test in the example. [Diagram 43] FIG. 43 is a graph showing the charge / discharge characteristics before the impact test in the example. [Diagram 44] 44(A) and 44(B) are photographs for explaining the impact test of the embodiment, and FIG. 44(C) and FIG. 44(D) are X-ray CT images after the impact test of the embodiment. [Diagram 45] FIG. 45 is a graph showing the charge / discharge characteristics after the impact test of the example. [Figure 46]46(A) to 46(C) are graphs showing the relationship between the number of bending times and the discharge capacity in the bending test of the embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] The embodiments of the present invention will be described with reference to the drawings. However, the present invention is not limited to the following description, and it will be easily understood by those skilled in the art that the modes and details of the present invention can be modified in various ways without departing from the spirit and scope of the present invention. Therefore, in the embodiments of the present invention shown below, the same reference numerals are used in different drawings to indicate the same objects.
[0023] In addition, ordinal numbers such as "first" and "second" in this specification are used to avoid confusion of components, and do not indicate any order or ranking, such as the order of processes or stacking. Even if a term is not used with an ordinal number in this specification, an ordinal number may be used in the claims to avoid confusion of components. Even if a term is used with an ordinal number in this specification, a different ordinal number may be used in the claims. Even if a term is used with an ordinal number in this specification, the ordinal number may be omitted in the claims.
[0024] Furthermore, in each of the embodiments and examples described below, unless otherwise specified, the embodiments and examples described in this specification can be implemented in any suitable combination.
[0025] In this specification, a low temperature environment refers to 0° C. or lower, and 0° C. or lower may be referred to as below freezing. When referring to a low temperature environment in this specification, any temperature below 0° C. can be selected. For example, when referring to a low temperature environment in this specification, one selected from 0° C. or lower, -10° C. or lower, -20° C. or lower, -30° C. or lower, -40° C. or lower, -50° C. or lower, -60° C. or lower, -80° C. or lower, and -100° C. or lower can be selected.
[0026] In this specification and the like, excellent charge / discharge characteristics in a low-temperature environment means that the decrease in discharge capacity in a low-temperature environment is small compared to the discharge capacity at 25°C.
[0027] In this specification, the space group is expressed using short notation of the international notation (or Hermann-Mauguin symbol). Furthermore, the crystal plane and crystal direction are expressed using Miller indices. Individual planes indicating crystal planes are expressed using (). In crystallography, the space group, crystal plane, and crystal direction are expressed by adding a superscript bar to the number, but in this specification, due to format restrictions, instead of adding a bar above the number, a - (minus sign) may be added before the number. Furthermore, individual directions indicating directions within a crystal are expressed with [ ], collective directions indicating all equivalent directions are expressed with < >, individual planes indicating crystal planes are expressed with ( ), and collective planes having equivalent symmetry are expressed with {}. Furthermore, trigonal crystals expressed by the space group R-3m are generally expressed as a composite hexagonal lattice of hexagonal crystals for ease of understanding of the structure, and unless otherwise specified, the space group R-3m will be expressed as a composite hexagonal lattice in this specification. In addition, the Miller indices are sometimes used as (hkil) instead of (hkl), where i is -(h+k).
[0028] Any integer greater than or equal to 1 may also be represented by the letters h, k, i, l, etc. For example, (00l) includes (001), (003), and (006).
[0029] The space group of a crystal structure is identified by XRD, electron beam diffraction, neutron beam diffraction, etc. Therefore, in this specification and the like, "belonging to a certain space group," "belonging to a certain space group," or "being a certain space group" can be rephrased as "identified with a certain space group."
[0030] In this specification, the theoretical capacity of a positive electrode active material refers to the amount of electricity when all of the lithium that can be inserted and removed from the positive electrode active material is removed. For example, the theoretical capacity of LiCoO2 is 274mAh / g, the theoretical capacity of LiNiO2 is 275mAh / g, and the theoretical capacity of LiMn2O4 is 148mAh / g.
[0031] In addition, the amount of lithium remaining in the positive electrode active material that can be inserted or removed can be determined by the x in the composition formula, for example, Li x It can be expressed as x in CoO2 (the occupancy rate of Li on the lithium site). In the case of a positive electrode active material in a lithium-ion battery, x = (theoretical capacity - charging capacity) / theoretical capacity. For example, when a lithium-ion battery using LiCoO2 as the positive electrode active material is charged at 219.2 mAh / g per weight of the positive electrode active material, Li 0.2 CoO2 or x=0.2. x A small x in CoO2 is, for example, x≦0.24. Considering the practical range when used as a positive electrode active material in a lithium ion battery, it is, for example, 0.1 <x≦0.24であるものとする。
[0032] When lithium cobalt oxide approximately satisfies the stoichiometric ratio, it is LiCoO2, and x=1. In addition, it may be said that a lithium ion battery that has finished discharging is also LiCoO2, and x=1. In addition, in general, in a lithium ion battery using LiCoO2, the discharge voltage drops sharply until it reaches 2.5V. For this reason, in this specification, for example, a state in which the voltage reaches 2.5V (counter electrode is lithium) with a current of 100mA / g or less per weight of the positive electrode active material is regarded as a state in which discharging has ended, and x=1. Therefore, in order to obtain lithium cobalt oxide when x=0.2, for example, it is sufficient to charge 219.2mAh / g per weight of the positive electrode active material from the state in which discharging has ended.
[0033] Li x It is preferable to measure the charge capacity and / or discharge capacity used to calculate x in CoO2 under conditions that are free of or have little influence from short circuits and / or decomposition of the electrolyte. For example, it is not preferable to use data from a lithium-ion battery that has experienced a sudden change in voltage that is considered to be a short circuit to calculate x.
[0034] In this specification and the like, the term "carbonate" refers to a compound having at least one carbonate ester in its molecular structure, and unless otherwise specified, includes "cyclic carbonates" and "chain carbonates." Furthermore, "chain" includes both linear and branched chains.
[0035] In this specification and the like, the phrase "having A and / or B" may be used, which means having A, having B, or having both A and B.
[0036] In this specification, a full cell refers to a battery cell assembled using a positive electrode and a non-metallic negative electrode, and a half cell refers to a battery cell assembled using lithium metal as the negative electrode (counter electrode).
[0037] (Embodiment 1) In this embodiment, a method for manufacturing a positive electrode active material applicable to a lithium ion battery having excellent charge / discharge characteristics even in a low-temperature environment will be described with reference to Fig. 1 to Fig. 8. Features of the positive electrode active material applicable to a lithium ion battery will be described in Embodiment 2.
[0038] <Example 1 of a method for producing a positive electrode active material> An example of a method for manufacturing a positive electrode active material of one embodiment of the present invention (example 1 of a method for manufacturing a positive electrode active material) will be described with reference to FIGS.
[0039] First, in step S10, lithium cobalt oxide as a starting material is prepared. The lithium cobalt oxide as a starting material may have a particle size (strictly speaking, a median diameter (D50)) of 10 μm or less (preferably 8 μm or less). The lithium cobalt oxide having a median diameter (D50) of 10 μm or less may be a known or publicly used (in short, commercially available) lithium cobalt oxide, or may be a lithium cobalt oxide produced through steps S11 to S14 shown in FIG. 1(B). A representative example of a commercially available lithium cobalt oxide having a median diameter (D50) of 10 μm or less is lithium cobalt oxide (product name "Cellseed C-5H") manufactured by Nippon Chemical Industry Co., Ltd. Cellseed C-5H has a median diameter (D50) of about 7 μm. A method for producing lithium cobalt oxide having a median diameter (D50) of 10 μm or less through steps S11 to S14 will be described below.
[0040] <Step S11> In step S11 shown in FIG. 1(B), a lithium source (Li source) and a cobalt source (Co source) are prepared as starting materials, that is, lithium and transition metal materials, respectively.
[0041] As the lithium source, it is preferable to use a compound containing lithium, such as lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. It is preferable that the lithium source has high purity, and for example, it is preferable to use a material with a purity of 99.99% or more.
[0042] As the cobalt source, it is preferable to use a compound containing cobalt, for example, tricobalt tetroxide, cobalt hydroxide, etc. The cobalt source is preferably high in purity, for example, a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and even more preferably 5N (99.999%) or more is used. By using a material with high purity, it is possible to control impurities in the positive electrode active material. As a result, the capacity of the secondary battery is increased, and the reliability of the secondary battery is improved.
[0043] <Step S12> Next, in step S12 shown in FIG. 1(B), the lithium source and the cobalt source are pulverized and mixed to prepare a mixed material. The pulverization and mixing can be performed in a dry or wet manner. Wet pulverization and mixing can be performed to obtain lithium cobalt oxide having a median diameter (D50) of 10 μm or less as a starting material because it can be crushed into smaller pieces. In addition, when performing the wet method, a solvent is prepared. As the solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used, but it is preferable to use an aprotic solvent that does not easily react with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. It is preferable to mix the lithium source and the transition metal source in dehydrated acetone with a purity of 99.5% or more, in which the moisture content is suppressed to 10 ppm or less, and then pulverize and mix. By using dehydrated acetone with the above purity, it is possible to reduce impurities that may be mixed in.
[0044] <Step S13> Next, in step S13 shown in FIG. 1B, the mixed material is heated. The heating temperature is preferably 800° C. to 1100° C., more preferably 900° C. to 1000° C., and even more preferably about 950° C. to 1000° C. If the temperature is too low, the decomposition and melting of the lithium source and the transition metal source may be insufficient. On the other hand, if the temperature is too high, lithium may evaporate from the lithium source and / or cobalt may be excessively reduced, which may cause defects. For example, cobalt may change from trivalent to divalent, which may induce oxygen defects.
[0045] If the heating time is too short, lithium cobalt oxide will not be synthesized, but if it is too long, the productivity will decrease. Therefore, the heating time should be 1 hour or more and 100 hours or less, preferably 2 hours or more and 20 hours or less, and more preferably 2 hours or more and 10 hours or less.
[0046] The rate of temperature rise depends on the heating temperature reached, but it is recommended to set it to 80°C / h or more and 250°C / h or less. For example, if heating at 1000°C for 10 hours, the rate of temperature rise should be 200°C / h.
[0047] Heating is preferably performed in an atmosphere with little water, such as dry air, for example, with a dew point of -50° C. or less, more preferably with a dew point of -80° C. or less. In this embodiment, heating is performed in an atmosphere with a dew point of -93° C. In order to suppress impurities that may be mixed into the material, it is preferable that the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere are each 5 ppb (parts per billion) or less.
[0048] The heating atmosphere is preferably an atmosphere containing oxygen. For example, there is a method of continuously introducing dry air into the reaction chamber. In this case, the flow rate of the dry air is preferably 10 L / min. The method of continuously introducing oxygen into the reaction chamber and having oxygen flow through the reaction chamber is called flow.
[0049] When the heating atmosphere is an atmosphere containing oxygen, a method that does not allow the oxygen to flow may be used. For example, the reaction chamber may be depressurized and then filled with oxygen to prevent the oxygen from entering or leaving the reaction chamber, which is called purging. For example, the reaction chamber may be depressurized to -970 hPa and then filled with oxygen to 50 hPa.
[0050] After heating, the material may be naturally cooled, but it is preferable that the time required for the material to cool from the specified temperature to room temperature is within a range of 10 to 50 hours. However, cooling to room temperature is not always necessary, and it is sufficient to cool the material to a temperature that is acceptable for the next step.
[0051] The heating in this step may be performed using a rotary kiln or a roller hearth kiln. Heating using a rotary kiln may be performed while stirring in either a continuous or batch type.
[0052] The container for accommodating the object to be heated during heating is preferably an aluminum oxide crucible or an aluminum oxide setter (also called a sheath). An aluminum oxide crucible is made of a material that is almost free of impurities. In this embodiment, a setter made of aluminum oxide with a purity of 99.9% is used. It is preferable to place a lid on the crucible or setter before heating, as this can prevent the material from volatilizing.
[0053] After the heating is completed, the mixture may be crushed and sieved as necessary.
[0054] <Step S14> By the above steps, lithium cobalt oxide (LiCoO2) shown in step S14 in FIG. 1(B) can be synthesized. Lithium cobalt oxide (LiCoO2) shown in step S14 is an oxide containing multiple metal elements in its structure, so it can be called a composite oxide. In this specification, the term "composite oxide" refers to an oxide containing multiple metal elements in its structure. Note that after step S13, a crushing step and a classification step may be performed to adjust the particle size distribution, and then lithium cobalt oxide (LiCoO2) shown in step S14 may be obtained.
[0055] Although the example of producing the composite oxide by the solid phase method as in steps S11 to S14 has been shown, the composite oxide may be produced by a coprecipitation method or a hydrothermal method.
[0056] Through steps S11 to S14, lithium cobalt oxide can be obtained as a starting material for obtaining a positive electrode active material applicable to lithium ion batteries having excellent charge / discharge characteristics even in a low-temperature environment. Specifically, lithium cobalt oxide having a median diameter (D50) of 10 μm or less can be obtained as the starting material.
[0057] <Step S15> Next, in step S15 shown in Fig. 1(A), the lithium cobalt oxide starting material is heated. The heating in step S15 is sometimes referred to as initial heating in this specification and the like because it is the first heating of the lithium cobalt oxide. Alternatively, since it is heating before step S31 described below, it is sometimes referred to as preheating or pretreatment.
[0058] The initial heating causes lithium compounds unintentionally remaining on the surface of the lithium cobalt oxide to be desorbed. In addition, the effect of increasing the internal crystallinity can be expected. Although impurities may be mixed into the lithium source and / or cobalt source prepared in step S11, etc., the initial heating can reduce the impurities from the lithium cobalt oxide starting material. The effect of increasing the internal crystallinity is, for example, the effect of mitigating distortion, displacement, etc. resulting from shrinkage differences, etc., that the lithium cobalt oxide prepared in step S14 has.
[0059] In addition, the initial heating has the effect of smoothing the surface of the lithium cobalt oxide. In addition, the initial heating has the effect of mitigating cracks and crystal defects that the lithium cobalt oxide has. In this specification and the like, the "smooth" surface of the lithium cobalt oxide refers to a state in which the surface of the lithium cobalt oxide particles has few irregularities, is generally rounded, and has rounded corners. Alternatively, a state in which there is little foreign matter attached to the surface is also called "smooth". Foreign matter is considered to be a cause of irregularities, so it is preferable not to allow it to adhere to the surface.
[0060] In this initial heating, it is not necessary to separately prepare a material that functions as a lithium source, an additive element source, or a flux.
[0061] If the heating time in this step is too short, sufficient effects are not obtained, but if it is too long, productivity decreases. The appropriate heating time range can be selected, for example, from the heating conditions described in step S13. The heating temperature in step S15 is preferably lower than the temperature in step S13 in order to maintain the crystal structure of the complex oxide. The heating time in step S15 is preferably shorter than the time in step S13 in order to maintain the crystal structure of the complex oxide. For example, heating is preferably performed at a temperature of 700°C to 1000°C (more preferably, 800°C to 900°C) for 1 hour to 20 hours (more preferably, 1 hour to 5 hours).
[0062] The heating in step S13 may cause a temperature difference between the surface and the inside of the lithium cobalt oxide. The temperature difference may induce a shrinkage difference. It is also considered that the temperature difference causes the shrinkage difference because the fluidity of the surface and the inside is different. The energy related to the shrinkage difference gives the lithium cobalt oxide a difference in internal stress. The internal stress difference is also called strain, and the energy is sometimes called strain energy. The internal stress is removed by the initial heating in step S15, or in other words, the strain energy is considered to be homogenized by the initial heating in step S15. When the strain energy is homogenized, the strain of the lithium cobalt oxide is relaxed. As a result, the surface of the lithium cobalt oxide becomes smooth. Or, it can be said that the surface is improved. In other words, by going through step S15, the shrinkage difference caused in the lithium cobalt oxide is relaxed, and the surface of the composite oxide can be made smooth.
[0063] Furthermore, the shrinkage difference may cause microscopic deviations in the lithium cobalt oxide, such as deviations in crystals. In order to reduce these deviations, it is preferable to carry out step S15. By carrying out step S15, it is possible to equalize the deviations in the composite oxide (alleviate deviations in crystals, etc., that have occurred in the composite oxide, or align the crystal grains). As a result, the surface of the composite oxide becomes smooth.
[0064] As described above, in step S10, lithium cobalt oxide having a median diameter (D50) of 12 μm or less, preferably 10 μm or less, more preferably 8 μm or less, which is synthesized in advance, may be used. In this case, steps S11 to S13 can be omitted. It is useful to carry out step S15 on lithium cobalt oxide synthesized in advance, and this is a preferred step because lithium cobalt oxide with a smooth surface can be obtained.
[0065] Note that step S15 is not an essential configuration in one aspect of the present invention, and therefore an aspect in which step S15 is omitted is also included in one aspect of the present invention.
[0066] The positive electrode active material of one embodiment of the present invention preferably contains an additional element A. A method for adding the additional element A will be described in the following steps.
[0067] <Step S20> Next, details of step S20 of preparing an additive element A as an A source will be described with reference to FIG. 1(C) and FIG. 1(D).
[0068] <Step S21> Step S20 shown in FIG. 1(C) includes steps S21 to S23. Step S21 prepares an additive element A. Specific examples of the additive element A include one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, barium, bromine, and beryllium. FIG. 1(C) illustrates a case where a magnesium source (Mg source) and a fluorine source (F source) are prepared. In addition to the additive element A, a lithium source may be prepared separately in step S21.
[0069] When magnesium is selected as the additive element A, the source of the additive element A can be called a magnesium source. As the magnesium source, magnesium fluoride (MgF2), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), magnesium carbonate (MgCO3), etc. can be used. A plurality of magnesium sources may be used.
[0070] When fluorine is selected as the additive element A, the additive element A source can be called a fluorine source. As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3), or sodium aluminum hexafluoride (Na3AlF6) can be used. Among these, lithium fluoride is preferred because it has a relatively low melting point of 848° C. and is easily melted in the heating step described below.
[0071] Magnesium fluoride can be used as both a fluorine source and a magnesium source. Lithium fluoride can be used as a lithium source. Other lithium sources that can be used in step S21 include lithium carbonate.
[0072] The fluorine source may be a gas, such as fluorine (F2), carbon fluoride, sulfur fluoride, or oxygen fluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F), which may be mixed into the atmosphere in the heating step described below. A plurality of fluorine sources may be used.
[0073] In this embodiment, lithium fluoride (LiF) is prepared as the fluorine source, and magnesium fluoride (MgF2) is prepared as the fluorine source and magnesium source. In addition, when the melting point of fluorine compounds (sometimes called fluorides) including lithium fluoride is lower than the melting point of other additive element sources, the fluorine compound can function as a flux (also called a fluxing agent) that lowers the melting point of other additive element sources. When the fluorine compound contains LiF and MgF2, the eutectic point P of LiF and MgF2 is around 742°C (T1) as shown in Figure 7 (quoted from Non-Patent Document 1, Figure 5 and added). Therefore, when a mixed fluoride containing LiF and MgF2 is used as the additive element source, it is preferable to set the heating temperature to 742°C or higher in the heating step after mixing the additive element.
[0074] Here, the differential scanning calorimetry (DSC) of the mixed fluoride and the mixture will be described with reference to FIG. 8. The curve labeled "mixed fluoride" in FIG. 8 is the result of DSC measurement of a mixture of LiF and MgF2. The mixed fluoride was prepared by mixing LiF:MgF2=1:3 (molar ratio). The curve labeled "mixture" in FIG. 8 is the result of DSC measurement of a mixture of lithium cobalt oxide, LiF, and MgF2. The mixture was prepared by mixing LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio).
[0075] As shown in Fig. 8, an endothermic peak is observed in the vicinity of 735°C for the mixed fluoride. Also, an endothermic peak is observed in the vicinity of 830°C for the mixture. Therefore, the heating temperature after mixing the additive element (such as step S33 described later) is preferably 742°C or higher, more preferably 830°C or higher. It may also be 800°C (T2 in Fig. 7) or higher, which is between these temperatures.
[0076] Moreover, when lithium fluoride and magnesium fluoride are mixed at a molar ratio of LiF:MgF2=65:35, the effect of lowering the melting point is maximized. Moreover, if the ratio of lithium fluoride is too large, there is a concern that the lithium becomes excessive and the cycle characteristics deteriorate. Therefore, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≦x≦1.9), more preferably LiF:MgF2=x:1 (0.1≦x≦0.5), and even more preferably LiF:MgF2=x:1 (x=0.33 or its vicinity). In this specification, the vicinity of a certain value means a value that is greater than 0.9 times and less than 1.1 times the value, unless otherwise specified.
[0077] <Step S22> 1(C), the magnesium source and the fluorine source are pulverized and mixed. This step can be performed under the pulverization and mixing conditions selected from those described in step S12.
[0078] <Step S23> 1(C), the material crushed and mixed as described above is collected to obtain a source of additive element A (A source). Note that the source of additive element A shown in step S23 has a plurality of starting materials and can be called a mixture.
[0079] The particle size of the mixture is preferably 100 nm to 10 μm in median diameter (D50), more preferably 300 nm to 5 μm in median diameter (D50). Even when a single material is used as the source of the additive element A, the median diameter (D50) is preferably 100 nm to 10 μm, more preferably 300 nm to 5 μm in median diameter (D50).
[0080] When the mixture (including the case where only one kind of additive element is included) pulverized in step S22 is mixed with lithium cobalt oxide in a later step, the mixture is easily adhered uniformly to the surface of the lithium cobalt oxide. If the mixture is adhered uniformly to the surface of the lithium cobalt oxide, the additive element is easily distributed or diffused uniformly in the surface layer portion 100a of the composite oxide after heating, which is preferable.
[0081] <Step S21> A process different from that shown in Fig. 1C will be described with reference to Fig. 1D. Step S20 shown in Fig. 1D includes steps S21 to S23.
[0082] In step S21 shown in Fig. 1(D), four types of additive element A sources to be added to lithium cobalt oxide are prepared. That is, Fig. 1(D) differs from Fig. 1(C) in the type of additive element A source. In addition to the additive element A source, a lithium source may be prepared separately.
[0083] As sources of four kinds of additive elements A, a magnesium source (Mg source), a fluorine source (F source), a nickel source (Ni source), and an aluminum source (Al source) are prepared. The magnesium source and the fluorine source can be selected from the compounds described in FIG. 1(C). Nickel oxide, nickel hydroxide, etc. can be used as the nickel source. Aluminum oxide, aluminum hydroxide, etc. can be used as the aluminum source.
[0084] <Step S22> and <Step S23> Next, steps S22 and S23 shown in FIG. 1(D) are similar to steps S22 and S23 described in FIG. 1(C).
[0085] <Step S31> Next, in step S31 shown in FIG. 1(A), the lithium cobalt oxide that has been subjected to step S15 (initial heating) is mixed with an additive element A source (A source). Here, the ratio of the number of cobalt atoms Co in the lithium cobalt oxide that has been subjected to step S15 to the number of magnesium atoms Mg in the additive element A is preferably Co:Mg=100:y (0.1≦y≦6), and more preferably Co:Mg=100:y (0.3≦y≦3). If the additive element A is added to the lithium cobalt oxide that has been subjected to initial heating, the additive element A can be added evenly. For this reason, it is preferable to add the additive element A after the initial heating (step S15), rather than adding the additive element A and then performing the initial heating (step S15).
[0086] Furthermore, when nickel is selected as the additive element A, it is preferable to perform the mixing in step S31 so that the number of nickel atoms in the nickel source is 0.05% to 4% of the number of cobalt atoms in the lithium cobalt oxide that has undergone step S15. Furthermore, when aluminum is selected as the additive element A, it is preferable to perform the mixing in step S31 so that the number of aluminum atoms in the aluminum source is 0.05% to 4% of the number of cobalt atoms in the lithium cobalt oxide that has undergone step S15.
[0087] The mixing in step S31 is preferably performed under milder conditions than the grinding and mixing in step S12 in order not to destroy the shape of the lithium cobalt oxide. For example, the mixing is preferably performed under conditions of a lower rotation speed or for a shorter time than in step S12. Also, dry mixing is preferably performed. For example, a particle composite device, a ball mill, a bead mill, etc. can be used for mixing.
[0088] Known particle composite devices include commercially available devices such as Mechanofusion (registered trademark) and Nobilta (registered trademark) manufactured by Hosokawa Micron Corporation. Mechanofusion has a fixed blade inside a cylindrical container, and the cylindrical container rotates to impart mechanical energy to the powder, thereby mixing it. Nobilta has a rotating blade inside a cylindrical container, and the rotation of the blade imparts mechanical energy to the powder, thereby mixing it. In this embodiment, mixing is performed at 3000 rpm for 10 minutes using Nobilta.
[0089] <Step S32> 1A, the mixed material is collected to obtain a mixture 903. When collecting the material, it may be crushed and then sieved, if necessary.
[0090] <Step S33> Next, in step S33 shown in FIG. 1(A), the mixture 903 is heated. The heating temperature in step S33 is preferably 800° C. or more and 1100° C. or less, more preferably 800° C. or more and 950° C. or less, and even more preferably 850° C. or more and 900° C. or less. The heating time in step S33 may be 1 hour or more and 100 hours or less, and preferably 1 hour or more and 10 hours or less. The lower limit of the heating temperature in step S33 must be a temperature at which the reaction between the lithium cobalt oxide and the additive element A source proceeds. The temperature at which the reaction proceeds may be a temperature at which mutual diffusion of elements contained in the lithium cobalt oxide and the additive element A source occurs, and may be lower than the melting temperature of these materials. For example, in the case of an oxide, the melting temperature T m 0.757 times (Tammann temperature T d ) solid-phase diffusion occurs, so the heating temperature in step S33 should be 500° C. or higher.
[0091] The reaction proceeds more easily when the temperature is equal to or higher than the melting temperature of one or more of the materials contained in the mixture 903. For example, when LiF and MgF2 are contained as the source of the additive element A, the eutectic point of LiF and MgF2 is around 742°C as described above, so that the lower limit of the heating temperature in step S33 is preferably 742°C or higher.
[0092] In addition, the mixture 903 obtained by mixing LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) shows an endothermic peak at about 830° C. in differential scanning calorimetry (DSC measurement) as described above. Therefore, the lower limit of the heating temperature is more preferably 830° C. or higher.
[0093] A higher heating temperature is preferable because the reaction proceeds more easily, the heating time is shorter, and the productivity is high.
[0094] The upper limit of the heating temperature is set to be lower than the decomposition temperature (1130°C) of lithium cobalt oxide. At temperatures close to the decomposition temperature, there is a concern that lithium cobalt oxide may decompose, albeit in a small amount. Therefore, the heating temperature is preferably 1000°C or lower, more preferably 950°C or lower, and even more preferably 900°C or lower.
[0095] Furthermore, when the mixture 903 is heated, it is preferable to control the partial pressure of fluorine or fluoride resulting from the fluorine source or the like within an appropriate range.
[0096] In the manufacturing method described in this embodiment, some materials, for example, LiF, which is a fluorine source, may function as a flux. This function allows the heating temperature to be lowered to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, to a temperature between 742°C and 950°C, and additive elements such as magnesium can be distributed in the surface layer to manufacture a positive electrode active material with good characteristics.
[0097] However, since LiF has a lower specific gravity in a gaseous state than oxygen, LiF may volatilize or sublime when heated, and the amount of LiF in the mixture 903 decreases when LiF volatilizes or sublimes. In this case, the function as a flux is weakened. Therefore, it is preferable to heat the mixture while suppressing the volatilization or sublimation of LiF.
[0098] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing LiF, that is, to heat the mixture 903 in a state where the partial pressure of LiF is high in the heating furnace. By such heating, it is possible to suppress the volatilization or sublimation of LiF in the mixture 903.
[0099] Moreover, the heating in this step is preferably performed so as not to cause adhesion between particles of the mixture 903. If the particles of the mixture 903 adhere to each other during heating, the contact area with oxygen in the atmosphere decreases, and the route along which the additive element (e.g., fluorine) diffuses is blocked, which may result in poor distribution of the additive element (e.g., magnesium and fluorine) in the surface layer.
[0100] Furthermore, when the additive element (e.g., fluorine) is uniformly distributed in the surface layer portion, a smooth positive electrode active material with few irregularities can be obtained. Therefore, in this process, in order to maintain the surface in a smooth state or to make it even smoother by heating in step S15, it is better that the particles of mixture 903 do not stick to each other.
[0101] FIG. 2(A) shows an example in which step S33 is performed in a heating furnace.
[0102] The heating furnace 220 shown in FIG. 2(A) has a heating furnace space 202, a hot plate 204, a pressure gauge 221, a heater unit 206, and a heat insulating material 208. A container 216 and a lid 218 are shown as setters for accommodating an object to be heated, and it is preferable to place the lid 218 on the container 216 and heat it. FIG. 2(B) shows a top view of the lid 218, and FIG. 2(C) shows a schematic cross-sectional view of the container 216 and the lid 218. A sealed space is created just by placing the lid 218 on the container 216, but since it is not completely sealed, the inside of the container does not become abnormally high pressure, and it is safe. Since a source of an additive element A (typically a fluoride) is added to the container 216 in advance, the inside of the space 219 formed by the container 216 and the lid 218 can be made into an atmosphere containing fluoride. During heating, if the concentration of gasified fluoride in the space 219 is kept constant or does not decrease by covering the space 219, the additive element A including fluorine and magnesium can be contained in the vicinity of the particle surface of the mixture 903. Since the space 219 has a smaller volume than the space 202 in the heating furnace, a small amount of fluoride volatilizes, and an atmosphere containing fluoride can be created. That is, the atmosphere of the reaction system can be made to contain fluoride without significantly reducing the amount of fluoride contained in the mixture 903. In addition, by using the lid 218, the mixture 903 can be heated in an atmosphere containing fluoride simply and inexpensively.
[0103] Furthermore, before heating in the heating furnace space 202, a step of making the heating furnace space 202 an atmosphere containing oxygen and a step of placing the container 216 containing the mixture 903 in the heating furnace space 202 are performed. By performing the steps in this order, the mixture 903 can be heated in an atmosphere containing oxygen and fluoride. For example, the heating can be performed while flowing gas (flow). The gas can be introduced from the bottom surface of the heating furnace space 202 and exhausted to the top surface. Also, the heating furnace space 202 can be sealed during heating to make it a closed space so that the gas is not carried to the outside (purging).
[0104] There is no particular limitation on the method for making the space inside the heating furnace 202 into an oxygen-containing atmosphere, but examples include a method of evacuating the space inside the heating furnace 202 and then introducing an oxygen-containing gas such as oxygen gas or dry air, and a method of injecting an oxygen-containing gas such as oxygen gas or dry air for a certain period of time. Among these, it is preferable to evacuate the space inside the heating furnace 202 and then introduce oxygen gas (oxygen replacement). The air in the space inside the heating furnace 202 may be considered as an oxygen-containing atmosphere.
[0105] Also, a source of the additive element A (typically a fluoride) that has been soaked into the inner walls of the container 216 and the lid 218 can be re-emitted by heating and attached to the mixture 903 .
[0106] There is no particular limitation on the process for heating the heating furnace 220. Heating may be performed using a heating mechanism provided in the heating furnace 220.
[0107] The conditions for storing the mixture 903 in the container 216 will be described with reference to FIG. 2(C). As shown in FIG. 2(C), it is preferable to store the mixture 903 so that the upper surface of the mixture 903 is flat with respect to the bottom surface of the container 216, in other words, so that the height H of the upper surface of the mixture 903 is uniform. The height H of the upper surface of the mixture 903 is preferably 4.0 mm or less, more preferably 2.0 mm or less. By setting the height H of the upper surface of the mixture 903 under the above conditions, oxygen in the atmosphere can reach the mixture 903 near the bottom surface of the container 216. On the other hand, if the height H of the upper surface of the mixture 903 is higher than 4.0 mm, the amount of oxygen that reaches the mixture 903 near the bottom surface of the container 216 becomes insufficient, and the battery characteristics when the positive electrode active material that has undergone this process is used in a battery are deteriorated. In addition, if the height H of the upper surface of the mixture 903 is too low, the amount of the mixture 903 that can be stored in the container 216 is reduced, resulting in a decrease in productivity. Therefore, the height H of the upper surface of the mixture 903 is preferably 0.5 mm or more, or 1.0 mm or more. To summarize the above, the height H of the upper surface of the mixture 903 is preferably 0.5 mm or more and 4.0 mm or less, and more preferably 1.0 mm or more and 2.0 mm or less.
[0108] The heating in step S33 is preferably performed while controlling the pressure inside the furnace with the pressure gauge 221. The inside of the furnace is preferably in an atmospheric pressure state or a pressurized state. For example, it is considered that the surface of lithium cobalt oxide is easily melted when exposed to a pressurized state. Therefore, the surface of lithium cobalt oxide heated together with LiF and MgF2 can be melted by applying pressure.
[0109] Furthermore, when heating the mixture 903, it is preferable to control the partial pressure of fluorine or fluorine compounds originating from the fluorine source or the like within an appropriate range. It is also possible to control the partial pressure by placing a lid on the container used in this step and heating it. As described above, by placing a lid on the container, it is possible to prevent the material from volatilizing or sublimating.
[0110] In the manufacturing method described in this embodiment, the material of the additive element A source (typically a fluoride), for example, LiF, which is a fluorine source, may function as a flux. This function allows the heating temperature to be lowered to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, to 742°C or higher and 950°C or lower, and the additive elements including magnesium are distributed in the surface layer, making it possible to manufacture a positive electrode active material with good characteristics.
[0111] However, since LiF has a lower specific gravity in a gaseous state than oxygen, LiF may volatilize or sublime when heated, and if it volatilizes, the amount of LiF in the mixture 903 will decrease. This weakens its function as a flux. Therefore, it is necessary to heat while suppressing the volatilization of LiF. Even if LiF is not used as the fluorine source, etc., Li on the surface of the lithium cobalt oxide may react with F of the fluorine source to produce LiF, which may then volatilize. Therefore, even if a fluorine compound with a higher melting point than LiF is used, it is necessary to suppress the volatilization in the same way.
[0112] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing LiF, that is, to heat the mixture 903 in a state where the partial pressure of LiF in the heating furnace is high. By such heating, it is possible to suppress the volatilization of LiF in the mixture 903. In order to suppress the volatilization of LiF, it is preferable to place a lid on the container serving as a setter. Since the container serving as a setter and the lid are exposed to high temperatures, if the thermal expansion coefficients of the materials of the container serving as a setter and the lid differ, the gap between the container and the lid may become large. Therefore, it is preferable to use the same material for the container serving as a setter and the lid.
[0113] <Roller hearth kiln> The manufacturing apparatus according to one embodiment of the present invention may be a roller hearth kiln that continuously processes objects contained in a container. Fig. 3(A) is a schematic cross-sectional view of a roller hearth kiln 150. Fig. 3(B) is a diagram illustrating rollers 152 of the roller hearth kiln.
[0114] The roller hearth kiln 150 has a kiln body 151, a plurality of rollers 152, heating means 153a and 153b, an atmosphere control means 154, and adhesion suppression means 155a, 155b and 155c. The roller hearth kiln 150 also preferably has one or more blocking plates 157 and measuring devices 120a and 120b. Figure 3(A) shows an example having three blocking plates 157 (shown as blocking plate 157a, blocking plate 157b and blocking plate 157c).
[0115] The kiln body 151 is tunnel-shaped. The rollers 152 have the function of transporting the container 160 containing the object to be heated 161. The container 160 passes through the tunnel-shaped kiln body 151 by the rollers 152 and is transported to the outside. For the container 160 and the object to be heated 161, the description of the container 216 and the mixture 903 described in FIG. 2(C) can be referred to. That is, the height of the top surface of the object to be heated 161 contained in the container 160 relative to the bottom surface of the container 160 is preferably 0.5 mm or more and 4.0 mm or less, and more preferably 1.0 mm or more and 2.0 mm or less.
[0116] The kiln body 151 has an upstream portion and a downstream portion along the conveying direction of the multiple rollers 152. The kiln body 151 has a heating means 153a in the upstream portion and a heating means 153b in the downstream portion. A blocking plate 157b may be provided between the upstream portion and the downstream portion. By providing the blocking plate 157b, the atmospheres in the upstream portion and the downstream portion can be controlled separately. Also, the blocking plate 157b may be provided near the entrance of the kiln body 151, and the blocking plate 157c may be provided near the exit. By providing these, the atmosphere inside the kiln body 151 can be easily controlled.
[0117] The adhesion suppression means 155 of the roller hearth kiln 150 is, for example, a means for vibrating the container 160. For example, as shown in FIG. 3(A) with three adhesion suppression means 155 (shown as adhesion suppression means 155a, adhesion suppression means 155b, and adhesion suppression means 155c), the adhesion suppression means 155 may be a rod-shaped or plate-shaped device provided between a plurality of rollers 152. The adhesion suppression means 155a, adhesion suppression means 155b, and adhesion suppression means 155c may be fixed, or may move to vibrate the container 160. Although FIG. 3(A) shows a configuration in which three adhesion suppression means 155 are provided, one embodiment of the present invention is not limited thereto. One or two adhesion suppression means 155 may be provided, or four or more adhesion suppression means 155 may be provided.
[0118] The adhesion suppression means of the roller hearth kiln 150 may be a plurality of rollers 152 with different inclinations, as shown in FIG. 3(B).
[0119] 3A for the heating means 153a and 153b, the atmosphere control means 154, etc. Also, the description of FIG. 3A for the measuring device 120a and the measuring device 120b can be referred to.
[0120] The roller hearth kiln 150 is preferable because it has high productivity since it continuously processes the materials to be treated.
[0121] <Cooling section of roller hearth kiln> The roller hearth kiln may be provided with a cooling section.
[0122] 3(A), a roller hearth kiln 150b is an example having a temperature raising zone 121, a first cooling zone 124, and a second cooling zone 125. The area located on the upstream side and heated by heating means 153a is referred to as a first holding zone 122, and the area located on the downstream side and heated by heating means 153b is referred to as a second holding zone 123.
[0123] The atmosphere control means 154 preferably has a function of controlling the atmosphere of each of the five zones (heating zone 121, first holding zone 122, second holding zone 123, first cooling zone 124, and second cooling zone 125). For example, gas is introduced from the atmosphere control means 154 into each of the five zones. The gas introduced from the atmosphere control means 154 into each of the five zones may differ in type, temperature, flow rate, etc.
[0124] 4 shows an example in which five zones are separated by shield plates 157, but a configuration in which no shield plate is provided between adjacent zones may be used. For example, a configuration in which no shield plate is provided between temperature increasing zone 121 and first holding zone 122 may be used. Also, for example, a configuration in which no shield plate is provided between the first cooling zone and the second cooling zone may be used.
[0125] The temperature increasing zone 121 has a heating means 153j. Here, it is preferable that the temperature of the heating means 153j varies depending on the region. For example, it is preferable that the temperature gradually increases from the upstream side to the downstream side. Specifically, for example, the heating means 153j has a plurality of blocks, each block is provided with a heater, and the heater temperature increases from the upstream block to the downstream side.
[0126] The first cooling zone 124 has a heating means 153k. Here, the temperature of the heating means 153k may differ depending on the region. For example, the temperature may be gradually lowered from the upstream side to the downstream side. Specifically, for example, the heating means 153j may have a plurality of blocks, each block is provided with a heater, and the heater temperature may be lowered from the upstream block to the downstream side.
[0127] The second cooling zone 125 is, for example, a room temperature region. By performing cooling at room temperature, the temperature drop rate can be increased.
[0128] Cooling may be performed using cooling water in the first cooling zone 124 and the second cooling zone 125. By using cooling water, the temperature drop rate can be increased.
[0129] In addition, in one embodiment of the roller hearth kiln of the present invention, either the first cooling zone 124 or the second cooling zone 125 may be omitted.
[0130] For example, the first cooling zone 124 may not be provided, and the second holding zone 123 may be connected to the second cooling zone, and cooling may be performed at room temperature immediately after the temperature holding step, thereby increasing the temperature drop rate.
[0131] As the heating means 153j and the heating means 153k, for example, a silicon carbide heater, a carbon heater, a metal heater, a molybdenum disilicide heater, or the like can be used.
[0132] <Step S34> Next, in step S34 shown in FIG. 1(A), the heated material is recovered and crushed as necessary to obtain the positive electrode active material 100. At this time, it is preferable to further sieve the recovered particles of the positive electrode active material 100. Through the above steps, it is possible to prepare the positive electrode active material 100 (composite oxide) having a median diameter (D50) of 12 μm or less (preferably 10.5 μm or less, more preferably 8 μm or less). The positive electrode active material 100 contains the additive element A.
[0133] <Example 2 of a method for producing a positive electrode active material> Another example of a method for producing a positive electrode active material according to one embodiment of the present invention (Example 2 of a method for producing a positive electrode active material) will be described with reference to Fig. 5 and Fig. 6. <Example 2 of a method for producing a positive electrode active material> differs from Example 1 of a method for producing a positive electrode active material described above in the number of times that an additive element is added and the mixing method, but the other descriptions in <Example 1 of a method for producing a positive electrode active material> can be applied.
[0134] 5, steps S10 and S15 are performed in the same manner as in Fig. 1(A) to prepare lithium cobalt oxide that has been subjected to initial heating. Note that step S15 is not an essential configuration in one embodiment of the present invention, and therefore an embodiment in which step S15 is omitted is also included in one embodiment of the present invention.
[0135] <Step S20a> Next, as shown in step S20a, a first additive element A1 source (A1 source) is prepared. Details of step S20a will be described with reference to FIG.
[0136] <Step S21> In step S21 shown in FIG. 6(A), a first additive element A1 source (A1 source) is prepared. The A1 source can be selected from the additive elements A described in step S21 shown in FIG. 1(C). For example, the additive element A1 source can be one or more selected from magnesium, fluorine, and calcium. FIG. 6(A) illustrates a case where a magnesium source (Mg source) and a fluorine source (F source) are used as the additive element A1 source.
[0137] Steps S21 to S23 shown in Fig. 6A can be performed under the same conditions as steps S21 to S23 shown in Fig. 1C. As a result, a source of the additive element A1 (A1 source) can be obtained in step S23.
[0138] Moreover, steps S31 to S33 shown in FIG. 5 can be performed under the same conditions as steps S31 to S33 shown in FIG. 1(A).
[0139] <Step S34a> Next, in step S33, the heated material is recovered to obtain lithium cobalt oxide having the additive element A1. Here, this is also called a second composite oxide to distinguish it from the lithium cobalt oxide (first composite oxide) that has been subjected to step S15.
[0140] <Step S40> In step S40 shown in Fig. 5, a source of the second additive element A2 (A2 source) is prepared. Step S40 will be described with reference to Figs. 6(B) and 6(C).
[0141] <Step S41> In step S40 shown in FIG. 6(B), a second additive element A2 source (A2 source) is prepared. The A2 source can be selected from the additive elements A described in step S20 shown in FIG. 1(C). For example, the additive element A2 can be one or more selected from nickel, titanium, boron, zirconium, and aluminum. FIG. 6(B) illustrates an example in which a nickel source (Ni source) and an aluminum source (Al source) are used as the additive element A2.
[0142] Steps S41 to S43 shown in Fig. 6B can be performed under the same conditions as steps S21 to S23 shown in Fig. 1C. As a result, a source of the additive element A2 (A2 source) can be obtained in step S43.
[0143] Steps S41 to S43 shown in Fig. 6(C) are a modified example of Fig. 6(B). In step S41 shown in Fig. 6(C), a nickel source (Ni source) and an aluminum source (Al source) are prepared, and in step S42a, they are individually pulverized. As a result, in step S43, a plurality of second additive element A2 sources (A2 sources) are prepared. Thus, step S40 in Fig. 6(C) differs from step S40 in Fig. 6(B) in that the additive element sources are individually pulverized in step S42a.
[0144] <Steps S51 to S53> Next, steps S51 to S53 shown in Fig. 5 can be performed under the same conditions as steps S31 to S33 shown in Fig. 1(A). The conditions of step S53 related to the heating step are preferably the same temperature as or lower than the heating temperature of step S33 shown in Fig. 5. Also, the heating time is preferably shorter than that of step S33. Specifically, the heating temperature is preferably 800°C or higher and 950°C or lower, more preferably 820°C or higher and 870°C or lower, and further preferably 850°C±10°C. Also, the heating time is preferably 0.5 hours or higher and 8 hours or lower, and more preferably 1 hour or higher and 5 hours or lower.
[0145] When nickel is selected as the additive element A2, it is preferable to perform the mixing in step S51 so that the number of nickel atoms in the nickel source is 0.05% to 4% of the number of cobalt atoms in the lithium cobalt oxide that has undergone step S15. When aluminum is selected as the additive element A2, it is preferable to perform the mixing in step S51 so that the number of aluminum atoms in the aluminum source is 0.05% to 4% of the number of cobalt atoms in the lithium cobalt oxide that has undergone step S15.
[0146] <Step S54> Next, in step S54 shown in Fig. 5, the heated material is collected and crushed as necessary to obtain the positive electrode active material 100. Through the above steps, a positive electrode active material 100 (composite oxide) having a median diameter (D50) of 12 µm or less (preferably 10.5 µm or less, more preferably 8 µm or less) can be produced. Alternatively, a positive electrode active material 100 applicable to lithium ion batteries having excellent charge / discharge characteristics even in a low temperature environment can be produced. The positive electrode active material 100 contains the additive element A1 and the additive element A2.
[0147] In the above-described example 2 of the manufacturing method, the additive element is introduced into the lithium cobalt oxide in a divided manner into a first additive element A1 and a second additive element A2, as shown in Fig. 5 and Fig. 6. By introducing the additive elements in a divided manner, the distribution of each additive element in the depth direction can be changed.
[0148] The contents of this embodiment mode can be freely combined with the contents of other embodiment modes.
[0149] (Embodiment 2) In this embodiment, a lithium ion battery having excellent charge / discharge characteristics even in a low-temperature environment will be described.
[0150] [Lithium-ion battery] A lithium ion battery according to one embodiment of the present invention includes a positive electrode, a negative electrode, and an electrolyte. A separator is provided between the positive electrode and the negative electrode. The lithium ion battery also includes an exterior body that contains the positive electrode, the negative electrode, the electrolyte, and the like. Note that, although a method for manufacturing a lithium ion battery will be described in this embodiment, the order in which the positive electrode, the negative electrode, and the electrolyte are manufactured is not limited to the order described in this embodiment.
[0151] In this embodiment, the description will focus on the configuration of a lithium ion battery required to realize a lithium ion battery having excellent charge / discharge characteristics even in a low temperature environment (e.g., 0° C., −20° C., preferably −30° C., more preferably −40° C.) Specifically, the description will focus on the positive electrode active material contained in the positive electrode, the negative electrode active material layer, and the electrolyte.
[0152] Fig. 9(A) is a cross-sectional schematic diagram illustrating the internal structure of a battery 10. The battery 10 has a positive electrode 11, a negative electrode 12, and a separator 13. The positive electrode 11 has a positive electrode current collector 21 and a positive electrode active material layer 22 on the positive electrode current collector 21, and the negative electrode 12 has a negative electrode current collector 31 and a negative electrode active material layer 32. As shown in the figure, the positive electrode active material layer 22 and the negative electrode active material layer 32 face each other with the separator 13 interposed therebetween. Although not shown in Fig. 9(A), an electrolyte is impregnated into voids in the positive electrode active material layer 22, voids in the separator, and voids in the negative electrode active material layer 32.
[0153] FIG. 9B is an enlarged view of a portion A enclosed by a dashed line in FIG. 9A.
[0154] The positive electrode active material layer 22 includes a positive electrode active material 100 and a conductive material 41. Although not shown, in addition to the positive electrode active material 100 and the conductive material 41, the positive electrode active material layer 22 may include a binder.
[0155] Also, the voids in the positive electrode active material layer 22 are preferably filled with the electrolyte 60 as shown in the figure. For example, it is preferable that 60% or more of the voids in the positive electrode active material layer 22 are filled with the electrolyte 60, more preferably 70% or more of the voids, more preferably 80% or more of the voids, more preferably 90% or more of the voids, more preferably 95% or more of the voids, and most preferably 99% or more of the voids. The voids in the positive electrode active material layer 22 refer to regions in the positive electrode active material layer 22 other than the solid components (positive electrode active material, conductive material, etc.).
[0156] Although detailed description is omitted, similarly to the above description of the positive electrode active material layer 22, the voids in the negative electrode active material layer 32 may also be filled with the electrolyte solution 60. For example, it is preferable that 60% or more of the voids in the negative electrode active material layer 32 are filled with the electrolyte solution 60, more preferably 70% or more of the voids, more preferably 80% or more of the voids, more preferably 90% or more of the voids, more preferably 95% or more of the voids, and most preferably 99% or more of the voids. The voids in the negative electrode active material layer 32 refer to regions in the negative electrode active material layer 32 other than solid components (negative electrode active material, conductive material, etc.).
[0157] In this way, by filling every corner of the positive electrode active material layer 22 and the negative electrode active material layer 32 with the electrolyte 60, it is possible to increase the area where the positive electrode active material and the negative electrode active material come into contact with the electrolyte. In other words, it is possible to provide a lithium ion battery with excellent charging and discharging characteristics in a low temperature environment.
[0158] In addition, in charging in a low-temperature environment, the energy barrier when lithium ions are desorbed from the positive electrode active material tends to be high. In other words, the lower the temperature of the charging environment, the higher the overvoltage required to desorb lithium ions from the positive electrode active material. In other words, the positive electrode active material may be exposed to a high voltage when charging in a low-temperature environment. In other words, if the positive electrode active material is not exposed to a high voltage when charging in a low-temperature environment, the charging capacity may be reduced.
[0159] Therefore, it is preferable to use a positive electrode active material that can withstand high voltage and obtain a high charge capacity during charging in a low-temperature environment as a positive electrode active material for a lithium-ion battery that has excellent charge and discharge characteristics even in a low-temperature environment.
[0160] In addition, it is preferable that the electrolyte of a lithium ion battery having excellent charging and discharging characteristics even in a low temperature environment uses a material that has excellent lithium ion conductivity even when charging and / or discharging (charging and discharging) in a low temperature environment (e.g., 0°C, preferably -20°C, more preferably -30°C, more preferably -40°C).
[0161] A positive electrode active material and an electrolyte that are preferable for a lithium ion battery having excellent charge and discharge characteristics even in a low temperature environment will be described in detail below.
[0162] [Positive electrode] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, and may further include at least one of a conductive material and a binder.
[0163] <Cathode active material> The positive electrode active material has a function of taking in and releasing lithium ions with charging and discharging. The positive electrode active material of one embodiment of the present invention can be a material that is less deteriorated (or has less increase in resistance) with charging and / or discharging (hereinafter also referred to as "charging and discharging") in a low temperature environment even at a high charging voltage (unless otherwise specified, the voltage value is based on lithium metal, and hereinafter also referred to as "high charging voltage"). Specifically, it is preferable to use a positive electrode active material (composite oxide) having a particle size (strictly speaking, a median diameter (D50)) of 12 μm or less (preferably 10.5 μm or less, more preferably 8 μm or less) obtained by the manufacturing method described in the first embodiment. Of course, the positive electrode active material may have a particle size of more than 12 μm and 20 μm or less. This positive electrode active material is a material containing the additive element A described in the first embodiment, and in this embodiment, the additive element A is divided into additive element X, additive element Y, and additive element Z, and the details will be described. In other words, the positive electrode active material described in this embodiment contains one or more of the additive element X, the additive element Y, and the additive element Z. The additive element X, the additive element Y, and the additive element Z will be described in detail in <Containing elements>. The additive element X described in this embodiment corresponds to the additive element A1 described in the first embodiment. The additive element Y and the additive element Z described in this embodiment correspond to the additive element A2 described in the first embodiment.
[0164] The particle size can be measured by a particle size distribution meter using a laser diffraction / scattering method. The median diameter (D50) is the particle diameter when the cumulative amount in the cumulative curve of the particle size distribution measurement result is 50%. The measurement of particle size is not limited to laser diffraction particle size distribution measurement, and the long diameter of the particle cross section may be measured by analysis such as scanning electron microscope (hereinafter referred to as SEM) or transmission electron microscope (hereinafter referred to as TEM). In addition, as a method for measuring the median diameter (D50) from analysis such as SEM or TEM, for example, 20 or more particles are measured, a cumulative curve is created, and the particle diameter when the cumulative amount is 50% can be taken as the median diameter (D50).
[0165] As one of the indices for evaluating the low-temperature characteristics, the discharge capacity value in a low-temperature environment should be 50% or more (preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, and most preferably 90% or more) of the discharge capacity value at 20° C. The above values should be determined under the same measurement conditions except for the environmental temperature.
[0166] Alternatively, even if a high charging voltage is used, by using a material that is less prone to deterioration (or a material that is less prone to increase in resistance) during charging and discharging as the positive electrode active material, it is preferable that the discharge capacity be large even in a low temperature environment.
[0167] More specifically, the discharge capacity when charging and discharging at -40°C is preferably 60% or more, more preferably 65% or more, more preferably 70% or more, and more preferably 75% or more, relative to the discharge capacity when charging and discharging at 25°C. Although -40°C is used, the temperature may be any low temperature, and may be replaced with other low temperatures such as -20°C or -30°C. The discharge condition may be, for example, a current rate of 0.1C (where 1C=200mA / g (per weight of positive electrode active material)). In the evaluation of low-temperature characteristics as described above, evaluation may be performed at a low rate as long as the measurement conditions other than the environmental temperature are the same.
[0168] As another evaluation of low-temperature characteristics, the discharge energy density value in a low-temperature environment is 50% or more (preferably 60% or more, more preferably 70% or more, even more preferably 80% or more, and most preferably 90% or more) of the discharge energy density value at 25°C.
[0169] The environmental temperature described in this specification refers to the temperature of a lithium-ion battery. In the measurement of battery characteristics using a thermostatic chamber, the environmental temperature can be regarded as the temperature set in the thermostatic chamber. Therefore, after placing a test cell to be measured (e.g., a test battery or a half cell) in the thermostatic chamber, it is advisable to wait a sufficient time (e.g., one hour or more) until the test cell becomes approximately the same temperature as the thermostatic chamber before starting the measurement, but this is not necessarily limited to this method.
[0170] A positive electrode active material 100 according to one embodiment of the present invention will be described with reference to Fig. 10 and Fig. 11. The positive electrode active material 100 is less likely to deteriorate due to repeated charging and discharging at a high voltage based on lithium metal, and therefore can provide sufficient battery characteristics even in a low-temperature environment. In this embodiment, the high voltage is 4.6 V, preferably 4.65 V, and more preferably 4.7 V based on lithium metal.
[0171] 10(A) and 10(B) are cross-sectional views of a positive electrode active material 100 according to one embodiment of the present invention. Enlarged views of the vicinity of AB in FIG. 10(B) are shown in FIGS. 11(A) to 11(C). Enlarged views of the vicinity of CD in FIG. 10(B) are shown in FIGS. 11(D) to 11(F).
[0172] 10(A), the positive electrode active material 100 has a surface layer portion 100a and an interior portion 100b. In the figure, the boundary between the surface layer portion 100a and the interior portion 100b is indicated by a dashed line, but there is no clear boundary.
[0173] The surface layer 100a of the positive electrode active material 100 refers to, for example, a region within 50 nm from the surface toward the inside, more preferably within 35 nm from the surface toward the inside, even more preferably within 20 nm from the surface toward the inside, and most preferably within 10 nm from the surface toward the inside. A narrow region from the surface toward the inside, specifically within 20 nm, is called a shell. Note that "approximately perpendicular" includes perpendicular, specifically 80° to 100°. A surface caused by a crack and / or a crack may also be called a surface. The surface layer is synonymous with the surface vicinity or the surface vicinity region.
[0174] The region deeper than the surface layer 100a of the positive electrode active material is referred to as the inner portion 100b, which is synonymous with the inner region or the core.
[0175] Furthermore, when positive electrode active material 100 has a layered rock-salt crystal structure of space group R-3m, surface layer portion 100a has edge region 100a1 and basal region 100a2, as shown in FIG. 10(B).
[0176] In addition, in Figures 10(A) and 10(B), the straight line marked with (00l) represents the (00l) plane. The basal region 100a2 has a particle surface (called a basal surface) that is parallel or approximately parallel to the (00l) plane. In addition, the particle surface other than the basal surface is called an edge surface, and the region having the edge surface is called an edge region 100a1. When lithium cobalt oxide is applied to the positive electrode active material 100, lithium ions can be inserted and removed at the edge surface.
[0177] The surface of the positive electrode active material 100 refers to the surface of the composite oxide including the surface layer portion 100a and the interior portion 100b. Therefore, the positive electrode active material 100 does not include metal oxides such as aluminum oxide (Al2O3) that do not have lithium sites that can contribute to charging and discharging, carbonates that are chemically adsorbed after the preparation of the positive electrode active material, hydroxyl groups, etc. The attached metal oxide refers to, for example, a metal oxide whose crystal orientation does not match that of the interior portion 100b.
[0178] The fact that the crystal orientations of the two regions roughly coincide can be determined from TEM (Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope) images, electron beam diffraction patterns, etc. It can also be determined from FFT patterns of TEM images and FFT patterns of STEM images, etc. Furthermore, XRD (X-ray Diffraction), neutron beam diffraction, etc. can also be used as materials for determination.
[0179] The positive electrode active material does not include the electrolytic solution, decomposition products of the electrolyte, organic solvent, binder, conductive material, or compounds derived therefrom that are attached to the positive electrode active material 100. In other words, the electrolytic solution, decomposition products of the electrolyte, organic solvent, binder, conductive material, or compounds derived therefrom that are attached to the surface of the positive electrode active material are removed.
[0180] Since the positive electrode active material 100 is a compound containing a transition metal and oxygen capable of inserting and desorbing lithium, the interface between a region where a transition metal M (e.g., Co, Ni, Mn, Fe, etc.) that is oxidized and reduced with the insertion and desorption of lithium and oxygen is present and a region where they are not present may be the surface of the positive electrode active material. Therefore, the surface of the positive electrode active material also includes surfaces caused by slips, cracks, and / or cracks. When the positive electrode active material is subjected to analysis, a protective film may be attached to the surface, but the protective film is not included in the positive electrode active material. As the protective film, a single layer film or a multilayer film of carbon, metal, oxide, resin, etc. may be used.
[0181] <Contained elements> The positive electrode active material 100 contains lithium, cobalt, oxygen, and an additive element. Alternatively, the positive electrode active material 100 may contain lithium cobalt oxide (LiCoO2) to which the additive element is added. However, the positive electrode active material 100 according to one embodiment of the present invention may have a crystal structure described below. Therefore, the composition of the lithium cobalt oxide is not strictly limited to Li:Co:O=1:1:2.
[0182] The additive elements contained in the positive electrode active material 100 are preferably one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, barium, bromine, and beryllium.
[0183] The additive element is preferably dissolved in the positive electrode active material 100. The additive element further stabilizes the crystal structure of the positive electrode active material 100, as described below.
[0184] For example, if the positive electrode active material 100 is substantially free of manganese, the above-mentioned advantages of being relatively easy to synthesize and easy to handle, and having excellent cycle characteristics, will be even greater. The weight of manganese contained in the positive electrode active material 100 is preferably, for example, 600 ppm or less, more preferably 100 ppm or less.
[0185] The surface layer 100a, particularly the edge region having an edge surface, is the region from which lithium ions are first desorbed during charging, and is a region that is likely to have a lower lithium concentration than the interior 100b. In addition, in the surface layer 100a from which lithium ions have been desorbed, particularly in the edge region, some of the bonds of the atoms on the surface of the particles of the positive electrode active material 100 are said to be in a state where they have been cut. For this reason, the surface layer 100a is likely to become unstable, and is a region where degradation of the crystal structure is likely to begin. On the other hand, if the surface layer 100a, particularly the edge region, can be made sufficiently stable, Li xEven when x in CoO2 is small, for example, 0.24 or less, the layered structure of the inner part 100b made of octahedrons of cobalt and oxygen can be made less likely to break. Furthermore, if the surface layer part 100a, especially the edge region, can be made sufficiently stable, the displacement of the layer made of octahedrons of cobalt and oxygen in the inner part 100b can be suppressed.
[0186] In order to make the surface layer 100a have a stable composition and crystal structure, it is preferable that the surface layer 100a contains the above-mentioned additive elements, and more preferably contains a plurality of additive elements. It is also preferable that the surface layer 100a has a higher concentration of one or more selected from the additive elements than the inner portion 100b. It is also preferable that the edge region 100a1 has a higher concentration of one or more selected from the additive elements than the basal region 100a2.
[0187] The distribution of the added elements will be described. Fig. 11(A) to Fig. 11(C) are enlarged views of the vicinity of AB in Fig. 10(B) and are views for explaining the edge region 100a1 of the positive electrode active material 100. Fig. 11(D) to Fig. 11(F) are enlarged views of the vicinity of CD in Fig. 10(B) and are views for explaining the basal region 100a2 of the positive electrode active material 100.
[0188] For example, some of the additive elements, such as magnesium, fluorine, and titanium, preferably have a concentration gradient that increases from the interior 100b toward the surface. In Figures 11(A) and 11(D), the image of the concentration gradient is expressed using the density of the hatching. An additive element having such a concentration gradient is referred to as additive element X. However, the concentration of magnesium, fluorine, titanium, etc. may be higher in the edge region 100a1 than in the basal region 100a2.
[0189] Another additive element, such as aluminum, preferably has a concentration gradient and a concentration peak in a region deeper than the additive element X shown in Figures 11(A) and 11(D). In Figures 11(A) and 11(D), the concentration gradient and the region of the peak are expressed using the density of the hatch. The concentration peak may be present in the surface layer portion 100a or may be deeper than the surface layer portion 100a. For example, it is preferable that the peak is present in a region of 5 nm to 30 nm from the surface toward the inside. An additive element having such a concentration gradient is referred to as additive element Y. However, the concentration of aluminum, etc. may be higher in the edge region 100a1 than in the basal region 100a2.
[0190] Another additive element, such as nickel, may be clearly present in the edge region 100a1 but substantially absent in the basal region 100a2, as shown by the presence or absence of hatching and the density of the hatching in Figures 11(C) and 11(F). The concentration of nickel, etc., may be higher in the edge region 100a1 than in the basal region 100a2. Note that "clearly present" here refers to a case where a characteristic X-ray energy spectrum of the element is detected in a cross-sectional STEM-EDX analysis of the positive electrode active material 100. An additive element having such a distribution is referred to as additive element Z.
[0191] Moreover, the term “substantially free” refers to a case where the characteristic X-ray energy spectrum of the element is not detected in a cross-sectional STEM-EDX analysis of the positive electrode active material 100. It is also referred to as the element being below the lower detection limit in a STEM-EDX analysis.
[0192] For example, magnesium, which is one of the additive elements X, is divalent, and magnesium is more stable at the lithium site than at the cobalt site in the layered rock-salt crystal structure, so it is more likely to enter the lithium site. The presence of magnesium at an appropriate concentration at the lithium site of the surface layer 100a makes it easier to maintain the layered rock-salt crystal structure. This is presumably because the magnesium present at the lithium site functions as a pillar supporting the CoO2 layers. The presence of magnesium also makes it easier to form Li xWhen x in CoO2 is, for example, 0.24 or less, the desorption of oxygen from around magnesium can be suppressed.
[0193] If magnesium is present at an appropriate concentration, it does not adversely affect the insertion and desorption of lithium during charging and discharging, and the above benefits can be enjoyed. However, if there is an excess of magnesium, it may adversely affect the insertion and desorption of lithium. Furthermore, the effect of stabilizing the crystal structure may be reduced. This is thought to be because magnesium enters the cobalt site in addition to the lithium site. In addition, excess magnesium compounds (oxides or fluorides, etc.) that do not substitute for either the lithium site or the cobalt site may segregate on the surface of the positive electrode active material, and may become resistance components in lithium-ion batteries. In addition, as the magnesium concentration of the positive electrode active material increases, the discharge capacity of the positive electrode active material may decrease. This is thought to be because too much magnesium enters the lithium site, reducing the amount of lithium that contributes to charging and discharging.
[0194] Therefore, it is preferable that the amount of magnesium contained in the entire positive electrode active material 100 is appropriate. For example, the number of magnesium atoms is preferably 0.001 times or more and 0.1 times or less than the number of cobalt atoms, more preferably more than 0.01 times and less than 0.04 times, and even more preferably about 0.02 times. The amount of magnesium contained in the entire positive electrode active material 100 may be a value obtained by performing elemental analysis of the entire positive electrode active material 100 using, for example, GD-MS, ICP-MS, etc., or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.
[0195] Aluminum, which is one of the additive elements Y, can be present at the cobalt site in the layered rock salt crystal structure. Aluminum is a typical trivalent element and does not change its valence, so lithium around the aluminum is unlikely to move even during charging and discharging. Therefore, aluminum and the lithium around it function as pillars and can suppress changes in the crystal structure. Aluminum also has the effect of suppressing the elution of surrounding cobalt and improving continuous charging resistance. In addition, since the Al-O bond is stronger than the Co-O bond, it can suppress the desorption of oxygen around the aluminum. These effects improve thermal stability. Therefore, if aluminum is included as an additive element, it is possible to improve safety when used in lithium-ion batteries. In addition, it is possible to obtain a positive electrode active material 100 whose crystal structure is not easily broken even when repeatedly charged and discharged. On the other hand, if there is an excess of aluminum, it may have a negative effect on the insertion and desorption of lithium.
[0196] Therefore, it is preferable that the amount of aluminum contained in the entire positive electrode active material 100 is appropriate. For example, the number of aluminum atoms contained in the entire positive electrode active material 100 is preferably 0.05% to 4% of the number of cobalt atoms, preferably 0.1% to 2% and more preferably 0.3% to 1.5%. Alternatively, 0.05% to 2% is preferable. Alternatively, 0.1% to 4% is preferable. The amount contained in the entire positive electrode active material 100 may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material 100 using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material 100.
[0197] Nickel, which is one of the additive elements Z, can exist on either the cobalt site or the lithium site. When nickel exists on the cobalt site, it has a lower redox potential than cobalt, which leads to an increase in discharge capacity, which is preferable.
[0198] In addition, when nickel is present at the lithium site, the shift in the layered structure consisting of octahedra of cobalt and oxygen can be suppressed. The change in volume caused by charging and discharging is also suppressed. The elastic modulus also increases, that is, the battery becomes harder. This is presumably because the nickel present at the lithium site also functions as a pillar supporting the CoO2 layers. Therefore, it is expected that the crystal structure will become more stable, especially at high temperatures, for example, at 45°C or higher when the battery is in a charged state.
[0199] On the other hand, an excess of nickel is undesirable because it increases the influence of distortion due to the Jahn-Teller effect, and may also adversely affect the insertion and extraction of lithium.
[0200] Therefore, it is preferable that the amount of nickel contained in the entire positive electrode active material 100 is appropriate. For example, the number of nickel atoms contained in the positive electrode active material 100 is preferably higher than 0% and not more than 7.5% of the number of cobalt atoms, preferably 0.05% to 4%, preferably 0.1% to 2%, and more preferably 0.2% to 1%. Alternatively, it is preferably higher than 0% and not more than 4%. Alternatively, it is preferably higher than 0% and not more than 2%. Alternatively, it is preferably 0.05% to 7.5%. Alternatively, it is preferably 0.05% to 2%. Alternatively, it is preferably 0.1% to 7.5%. Alternatively, it is preferably 0.1% to 4%. The amount of nickel shown here may be, for example, a value obtained by performing elemental analysis of the entire positive electrode active material using GD-MS, ICP-MS, or the like, or may be based on the value of the composition of raw materials in the process of producing the positive electrode active material.
[0201] In addition, fluorine, which is one of the additive elements X, is a monovalent anion, and when part of the oxygen is replaced by fluorine in the surface layer portion 100a, the lithium desorption energy is reduced. This is because the valence of the cobalt ion accompanying lithium desorption is changed from trivalent to tetravalent in the absence of fluorine, and from divalent to trivalent in the presence of fluorine, resulting in a difference in oxidation-reduction potential. Therefore, when part of the oxygen in the surface layer portion 100a of the positive electrode active material 100 is replaced by fluorine, it can be said that the desorption and insertion of lithium ions near the fluorine can occur smoothly. Therefore, when used in a lithium ion battery, the charge / discharge characteristics, large current characteristics, etc. can be improved. In addition, the presence of fluorine in the surface layer portion 100a having the surface that is in contact with the electrolyte can effectively improve the corrosion resistance against hydrofluoric acid. In addition, as described in a later embodiment, when the melting point of a fluoride such as lithium fluoride is lower than the melting point of other additive element sources, it can function as a flux (also called a flux agent) that lowers the melting point of other additive element sources.
[0202] In addition, titanium oxide, which is one of the additive elements X, is known to have superhydrophilicity. Therefore, by making the surface layer portion 100a of the positive electrode active material 100 have titanium oxide, the wettability to a highly polar solvent may be improved. When the positive electrode active material 100 is used as a secondary battery, the contact at the interface between the positive electrode active material 100 and the highly polar electrolyte may be improved, and an increase in internal resistance may be suppressed.
[0203] Furthermore, when the surface layer 100a shown in FIG. 11(A) has magnesium and the surface layer 100a shown in FIG. 11(C) has nickel, that is, when both magnesium and nickel are present, there is a possibility that divalent nickel can exist more stably near divalent magnesium. x Even when x in CoO2 is small, the elution of magnesium can be suppressed, which can contribute to the stabilization of the surface layer portion 100a.
[0204] 11(C) and 11(F), the additive element Z is preferably contained in a large amount in the edge region 100a1 (also referred to as being contained preferentially or selectively), which is preferable because it improves the stability of the crystal structure of the edge region 100a1 where lithium ions enter and exit the positive electrode active material 100 during charging and discharging of the lithium ion battery. In addition, when the additive element Z has the above-mentioned distribution, for example, when the positive electrode active material 100 is lithium cobalt oxide, it is preferable because the effects of adding the additive element Z, such as a decrease in discharge voltage or a decrease in discharge capacity, can be minimized.
[0205] As described above, when a plurality of additive elements are included, the effects of the respective additive elements are synergistic and can contribute to further stabilization of the surface layer portion 100a. In particular, when magnesium, nickel, and aluminum are included, the effect of making the composition and crystal structure stable is high and is preferable. In particular, it is preferable that the surface layer portion 100a of the positive electrode active material 100 has a region where aluminum is distributed more inward than magnesium. Furthermore, in addition to the above-mentioned region where magnesium and aluminum are distributed, it is most preferable that the surface layer portion 100a of the positive electrode active material 100 has a region where the distribution of nickel and the distribution of magnesium overlap in the edge region 100a1.
[0206] <Crystal structure> One aspect of the present invention is a lithium ion battery having improved battery characteristics in a low-temperature environment, but the XRD measurements and the like for identifying the crystal structure and the like were performed at room temperature.
[0207] <Li x When x in CoO2 is 1> The positive electrode active material 100 according to one embodiment of the present invention is in a discharged state, i.e., Li xWhen x=1 in CoO2, it is preferable that the layered rock-salt type complex oxide belongs to the space group R-3m. The layered rock-salt type complex oxide has a high discharge capacity, has a two-dimensional lithium ion diffusion path, is suitable for the lithium ion insertion / extraction reaction, and is excellent as a positive electrode active material for lithium ion batteries. Therefore, it is preferable that the inner part 100b, which occupies most of the volume of the positive electrode active material 100, has a layered rock-salt type crystal structure.
[0208] On the other hand, the surface layer portion 100a of the positive electrode active material 100 according to one embodiment of the present invention preferably has a function of reinforcing the layered structure of the inner portion 100b, which is made up of octahedra of cobalt and oxygen, so that it is not broken even if lithium is removed from the positive electrode active material 100 by charging. Alternatively, the surface layer portion 100a preferably functions as a barrier film for the positive electrode active material 100. Alternatively, the surface layer portion 100a, which is the outer periphery of the positive electrode active material 100, preferably reinforces the positive electrode active material 100. The reinforcement referred to here means suppressing structural changes in the surface layer portion 100a and the inner portion 100b of the positive electrode active material 100, such as oxygen desorption, and / or suppressing oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.
[0209] For the reinforcing function, the surface layer portion 100a may have a different crystal structure from the inner portion 100b. For example, the surface layer portion 100a preferably has a composition and a crystal structure that are more stable at room temperature (25° C.) than the inner portion 100b. For example, at least a part of the surface layer portion 100a of the positive electrode active material 100 of one embodiment of the present invention may have a rock-salt type crystal structure. Alternatively, the surface layer portion 100a may have both a layered rock-salt type crystal structure and a rock-salt type crystal structure. Alternatively, the surface layer portion 100a may have characteristics of both a layered rock-salt type crystal structure and a rock-salt type crystal structure.
[0210] Moreover, the fact that it has both the characteristics of the layered rock salt type and the rock salt type crystal structure can be determined by electron beam diffraction, TEM images, cross-sectional STEM images, etc.
[0211] In addition, it is preferable that some of the added elements, especially magnesium, have a higher concentration in the surface layer 100a than in the interior 100b, and that they are present randomly and dilutely in the interior 100b. When aluminum is present at an appropriate concentration in the lithium site of the interior 100b, it has the effect of making it easier to maintain the layered rock-salt crystal structure as described above. When nickel is present at an appropriate concentration in the interior 100b, it is possible to suppress the deviation of the layered structure consisting of octahedra of cobalt and oxygen as described above. When magnesium and nickel are present together, there is a possibility that divalent magnesium can exist more stably near divalent nickel, so a synergistic effect of suppressing the elution of magnesium can be expected.
[0212] It is also preferable that the crystal structure changes continuously from the inside 100b toward the surface due to the above-mentioned magnesium concentration gradient, or that the crystal orientation of the surface layer 100a and the inside 100b are roughly the same.
[0213] In this specification, the layered rock-salt type crystal structure belonging to the space group R-3m, which is possessed by a composite oxide containing lithium and transition metals such as cobalt, refers to a crystal structure having a rock-salt type ion arrangement in which cations and anions are alternately arranged, and in which the transition metal and lithium are regularly arranged to form a two-dimensional plane, allowing two-dimensional diffusion of lithium. Defects such as deficiencies of cations or anions may be present. Strictly speaking, the layered rock-salt type crystal structure may have a distorted lattice structure of the rock-salt type crystal structure, and the orientation of the crystals may roughly match each other.
[0214] The rock salt crystal structure is a cubic crystal structure, such as a crystal structure belonging to the space group Fm-3m, in which cations and anions are arranged alternately. Note that cations or anions may be missing.
[0215] The rock-salt crystal structure does not distinguish between cation sites, but the layered rock-salt crystal structure has two types of cation sites in the crystal structure, one of which is mostly occupied by lithium and the other by the transition metal M. The layered structure, in which two-dimensional planes of cations and two-dimensional planes of anions are alternately arranged, is the same for both the rock-salt and layered rock-salt structures.
[0216] The layered rock-salt crystal structure and the anions in the rock-salt crystal structure have a cubic close-packed structure (face-centered cubic lattice structure). It is presumed that the anions in the O3' crystal, which will be described later, also have a cubic close-packed structure. Therefore, when the layered rock-salt crystal structure and the rock-salt crystal structure come into contact, there is a crystal plane where the cubic close-packed structure composed of anions is aligned.
[0217] Alternatively, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock-salt type has a space group of R-3m and a rhombohedral structure, but to make the structure easier to understand, it is generally represented as a compound hexagonal lattice, and the (0001) plane of the layered rock-salt type has a hexagonal lattice. The triangular lattice of the cubic {111} plane has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock-salt type. When the two lattices are compatible, it can be said that the orientation of the cubic close-packed structure is aligned.
[0218] However, the space group of the layered rock-salt crystal structure and the O3'-type crystal structure described later is R-3m, which is different from the space group Fm-3m (the space group of general rock-salt crystals) of the rock-salt crystal structure, and therefore the Miller indices of the crystal planes that satisfy the above conditions are different between the layered rock-salt crystal structure and the O3'-type crystal structure, and the rock-salt crystal structure. In this specification, when the orientations of the cubic close-packed structures formed by anions are aligned in the layered rock-salt crystal structure, the O3'-type crystal structure, and the rock-salt crystal structure, it may be said that the crystal orientations are roughly the same.
[0219] <Li x CoO2 with small x> The positive electrode active material 100 according to one embodiment of the present invention has the above-described magnesium distribution and / or crystal structure, and therefore, in a discharged state (Li xThe crystal structure in the state where x in CoO2 is small) is different from that of conventional positive electrode active materials. <x≦0.24をいうこととする。
[0220] Using Figs. 12 to 15, Li x The change in crystal structure accompanying the change in x in CoO2 will be described while comparing a conventional positive electrode active material with a positive electrode active material 100 according to one embodiment of the present invention.
[0221] The change in the crystal structure of a conventional positive electrode active material is shown in Figure 13. The conventional positive electrode active material shown in Figure 13 is lithium cobalt oxide (LiCoO2) that does not contain magnesium.
[0222] Figure 13 shows R-3m O3 and Li x The crystal structure of lithium cobalt oxide with x=1 in CoO2 is shown. In this crystal structure, lithium occupies the octahedral site, and there are three CoO2 layers in the unit cell. For this reason, this crystal structure is sometimes called an O3 type crystal structure. Note that a CoO2 layer is an octahedral structure in which cobalt is coordinated with six oxygen atoms, and the edges are shared to form a continuous plane. This is sometimes called a layer consisting of cobalt and oxygen octahedra.
[0223] In addition, conventional lithium cobalt oxide is known to have a crystal structure that belongs to the monoclinic space group P2 / m when the symmetry of lithium increases when x is about 0.5. This structure has one CoO2 layer in the unit cell. Therefore, it is sometimes called O1 type or monoclinic O1 type.
[0224] When x=0, the positive electrode active material has a trigonal space group P-3m1 crystal structure, and there is also one CoO2 layer in the unit cell. Therefore, this crystal structure is sometimes called O1 type, or trigonal O1 type. In addition, the trigonal structure may be converted to a composite hexagonal lattice and called hexagonal O1 type.
[0225] Furthermore, conventional lithium cobalt oxide when x=0.12 has a crystal structure of space group R-3m. This structure can be said to be a structure in which a trigonal O1-type CoO2 structure and an R-3m O3-type LiCoO2 structure are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3-type crystal structure. In reality, the number of cobalt atoms per unit cell in the H1-3-type crystal structure is twice that of other structures. However, in Figure 13 and other parts of this specification, the c-axis of the H1-3-type crystal structure is shown as half the unit cell in order to make it easier to compare with other crystal structures.
[0226] As an example of the H1-3 type crystal structure, the coordinates of cobalt and oxygen in the unit cell can be expressed as Co(0,0,0.42150±0.00016), O1(0,0,0.27671±0.00045), and O2(0,0,0.11535±0.00045). O1 and O2 are oxygen atoms. Which unit cell should be used to express the crystal structure of the positive electrode active material can be determined, for example, by Rietveld analysis of the XRD pattern. In this case, it is sufficient to adopt a unit cell with a small GOF (goodness of fit) value, specifically one close to 1.
[0227] Li x When the battery is repeatedly charged and discharged such that x in CoO2 becomes 0.24 or less, conventional lithium cobalt oxide repeatedly undergoes a change in crystal structure (i.e., a non-equilibrium phase change) between the H1-3 type crystal structure and the R-3m O3 structure in the discharged state.
[0228] However, these two crystal structures have a large misalignment of the CoO2 layer. As shown by the dotted line and arrow in Figure 13, in the H1-3 type crystal structure, the CoO2 layer is significantly misaligned from that of R-3m O3 in the discharged state. Such dynamic structural changes can have a negative effect on the stability of the crystal structure.
[0229] Furthermore, the difference in volume between these two crystal structures is large: when compared per the same number of cobalt atoms, the volume change rate between the H1-3 crystal structure and the R-3m O3 crystal structure in the discharged state exceeds 3.5%, typically 3.9% or more.
[0230] In addition, the H1-3 crystal structure, which has continuous CoO2 layers like the trigonal O1 type, is likely to be unstable.
[0231] Therefore, when charging and discharging are repeated so that x is 0.24 or less, the crystal structure of conventional lithium cobalt oxide collapses. The collapse of the crystal structure causes a deterioration in cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably and makes it difficult to insert and remove lithium.
[0232] On the other hand, in the positive electrode active material 100 according to one embodiment of the present invention shown in FIG. x The change in the crystal structure between the discharged state where x in CoO2 is 1 and the state where x is 0.24 or less, specifically, 0.2 (this may be described as a Li existence probability of 20%) is smaller than that of conventional positive electrode active materials. More specifically, the deviation of the CoO2 layer between the state where x is 1 and the state where x is 0.24 or less can be reduced. Also, the change in volume compared per cobalt atom can be reduced. Therefore, the positive electrode active material 100 of one embodiment of the present invention is unlikely to collapse in crystal structure even when charging and discharging to a value where x is 0.24 or less are repeated, and excellent cycle characteristics can be achieved. Also, the positive electrode active material 100 of one embodiment of the present invention is unlikely to collapse in crystal structure even when charging and discharging to a value where x is 0.24 or less are repeated, and excellent cycle characteristics can be achieved. x When x in CoO2 is 0.24 or less, the positive electrode active material 100 according to one embodiment of the present invention can have a more stable crystal structure than the conventional positive electrode active material. x When the x in CoO2 is kept at 0.24 or less, short circuits are unlikely to occur. In such a case, the safety of the lithium-ion battery is further improved, which is preferable.
[0233] Li x12 shows the crystal structure of the interior 100b of the positive electrode active material 100 when x in CoO2 is approximately 1 and 0.2. The interior 100b occupies most of the volume of the positive electrode active material 100 and is the part that contributes greatly to charge and discharge, so it can be said that the displacement of the CoO2 layer and changes in volume are the most problematic part.
[0234] When x=1, the positive electrode active material 100 has the same crystal structure of R-3m O3 as conventional lithium cobalt oxide.
[0235] However, the positive electrode active material 100 has a crystal structure different from that of conventional lithium cobalt oxide when x is 0.24 or less, for example, about 0.2 or about 0.12, in which case the lithium cobalt oxide has an H1-3 type crystal structure.
[0236] The positive electrode active material 100 according to an embodiment of the present invention when x=0.2 has a crystal structure belonging to the trigonal space group R-3m. The symmetry of the CoO2 layer is the same as that of O3. Therefore, this crystal structure is called an O3'-type crystal structure. The positive electrode active material 100 according to an embodiment of the present invention when x=0.2 is not a spinel structure, but a pattern similar to a spinel structure may appear in the XRD pattern, and this crystal structure may be called a pseudo-spinel structure. This crystal structure is shown in FIG. 12 with R-3m O3'.
[0237] The O3' type crystal structure can be expressed by the coordinates of cobalt and oxygen in the unit cell being Co(0,0,0.5), O(0,0,x), in the range of 0.20≦x≦0.25. The lattice constant of the unit cell is 2.797≦a≦2.837(×10 -1 nm), and 2.807≦a≦2.827(×10 -1 nm) is more preferable, and typically a = 2.817 (× 10 -1 nm). The c-axis is 13.681≦c≦13.881(×10 -1 nm), 13.751≦c≦13.811 is more preferable, and typically c=13.781(×10 -1 nm).
[0238] In the O3' crystal structure, ions of cobalt, magnesium, etc. occupy the 6-coordinate oxygen sites. Light elements such as lithium may occupy the 4-coordinate oxygen sites.
[0239] As shown by the dotted line in FIG. 12, there is almost no deviation in the CoO2 layer between R-3m(O3) in the discharged state and the O3' type crystal structure.
[0240] Furthermore, the volume change rate per the same number of cobalt atoms in the discharged R-3m(O3) and O3' type crystal structures is 2.5% or less, more specifically 2.2% or less, typically 1.8%.
[0241] In this way, in the positive electrode active material 100 according to one embodiment of the present invention, Li x When x in CoO2 is small, that is, when a large amount of lithium is released, the change in the crystal structure is suppressed more than in conventional positive electrode active materials. In addition, the change in volume is also suppressed when compared per the same number of cobalt atoms. Therefore, the crystal structure of the positive electrode active material 100 is not easily broken even when charging and discharging are repeated so that x is 0.24 or less. Therefore, the positive electrode active material 100 suppresses the decrease in charge and discharge capacity during charge and discharge cycles. In addition, since more lithium can be stably used than in conventional positive electrode active materials, the positive electrode active material 100 has a large discharge capacity per weight and volume. Therefore, by using the positive electrode active material 100, a lithium-ion battery with a high discharge capacity per weight and volume can be manufactured.
[0242] The positive electrode active material 100 is Li x It has been confirmed that when x in CoO2 is 0.15 or more and 0.24 or less, it may have an O3' type crystal structure, and it is presumed that even when x is more than 0.24 and 0.27 or less, it has an O3' type crystal structure. However, the crystal structure is Li x Since it is affected by not only x in CoO2 but also the number of charge / discharge cycles, charge / discharge current, temperature, electrolyte, etc., it is not necessarily limited to the above range of x.
[0243] Therefore, the positive electrode active material 100 is Li xWhen x in CoO2 is more than 0.1 and not more than 0.24, the entire interior 100b of the positive electrode active material 100 does not have to have the O3' type crystal structure, but may contain other crystal structures, or may be partially amorphous.
[0244] Also Li x To make the x in CoO2 small, it is generally necessary to charge at a high charging voltage. x A state in which x in CoO2 is small can be rephrased as a state in which the material is charged at a high charging voltage.
[0245] In other words, the positive electrode active material 100 of one embodiment of the present invention is preferable because it can maintain a crystal structure having the symmetry of R-3m O3 even when charged at a high charging voltage, for example, a voltage of 4.6 V or more at 25° C. In other words, it is preferable because it can adopt an O3′-type crystal structure when charged at a higher charging voltage, for example, a voltage of 4.65 V or more and 4.7 V or less at 25° C.
[0246] In some cases, the H1-3 crystal structure is finally observed when the charging voltage is further increased in the positive electrode active material 100. As described above, the crystal structure is affected by the number of charge / discharge cycles, the charge / discharge current, the electrolyte, and the like, and therefore, when the charging voltage is lower, for example, even when the charging voltage is 4.5 V or more and less than 4.6 V at 25° C., the positive electrode active material 100 of one embodiment of the present invention may have the O3′ crystal structure.
[0247] In addition, when graphite is used as the negative electrode active material in a lithium ion battery, the voltage of the lithium ion battery is lower than the above by the potential of the graphite. The potential of graphite is about 0.05 V to 0.2 V based on the potential of lithium metal. Therefore, in the case of a lithium ion battery using graphite as the negative electrode active material, the battery has a similar crystal structure at a voltage obtained by subtracting the potential of graphite from the voltage when lithium metal is used as the negative electrode active material.
[0248] In addition, in FIG. 12, O3' is shown as having lithium with equal probability at all lithium sites, but this is not limited to this. It may be present biasedly at some lithium sites, or, for example, in the monoclinic O1 (Li 0.5 The lithium distribution can be analyzed, for example, by neutron diffraction.
[0249] In order to have an O3'-type crystal structure, it is preferable that the magnesium concentration gradient is the same at multiple locations in the surface layer 100a of the positive electrode active material 100. In other words, it is preferable that the reinforcement derived from magnesium is present homogeneously in the surface layer 100a. Even if a portion of the surface layer 100a is reinforced, if there is a portion without reinforcement, stress may be concentrated in the portion without reinforcement. If stress is concentrated in a portion of the positive electrode active material 100, defects such as cracks may occur there, which may lead to cracking of the positive electrode active material and a decrease in discharge capacity. However, it is not necessary that magnesium has the same concentration gradient in the entire surface layer 100a of the positive electrode active material 100.
[0250] In the layered rock-salt crystal structure of R-3m, cations are arranged parallel to the (001) plane. This can be said to be a structure in which CoO2 layers and lithium layers are alternately stacked parallel to the (001) plane. Therefore, the diffusion path of lithium ions also exists parallel to the (001) plane. Again, the (001) plane is called the basal plane, and the planes other than the (001) plane that expose the diffusion path of lithium ions are called edge planes.
[0251] Since the CoO2 layer is relatively stable, it is more stable for the surface of the positive electrode active material 100 to have a (001) orientation. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) plane.
[0252] On the other hand, the diffusion path of lithium ions is exposed on the surface other than the (001) plane. Therefore, the surface other than the (001) plane and the surface layer portion 100a having the surface are important regions for maintaining the diffusion path of lithium ions, and at the same time, they are regions from which lithium ions are first desorbed and therefore tend to become unstable. Therefore, it is extremely important to reinforce the surface other than the (001) plane and the surface layer portion 100a having the surface in order to maintain the crystal structure of the entire positive electrode active material 100.
[0253] <Analysis method> A certain positive electrode active material is Li x When x in CoO2 is small, whether or not the positive electrode active material 100 according to one embodiment of the present invention has an O3' type crystal structure can be determined by Li x This can be determined by analyzing a positive electrode having a positive electrode active material with a small x in CoO2 using XRD, electron beam diffraction, neutron beam diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR), etc. Among XRD, powder XRD is preferable because it can obtain diffraction peaks that reflect the crystal structure of the inside 100b of the positive electrode active material 100, which occupies most of the volume of the positive electrode active material 100.
[0254] Furthermore, even in the positive electrode active material 100 of one embodiment of the present invention, an H1-3 type or trigonal O1 type crystal structure may be generated when x is too small, such as 0.1 or less, or under conditions where the charging voltage exceeds 4.9 V. Therefore, in order to determine whether or not the positive electrode active material 100 of one embodiment of the present invention is a material, analysis of the crystal structure, such as XRD, and information on the charging capacity or charging voltage, etc. are required.
[0255] In addition, when the positive electrode active material has a small x value, the crystal structure may change when it is exposed to air. For example, the crystal structure may change from O3' to H1-3. Therefore, it is preferable to handle all samples used for crystal structure analysis in an inert atmosphere such as an argon atmosphere.
[0256] In addition, whether or not the distribution of the additive elements contained in the positive electrode active material is in the state described above can be determined by analysis using, for example, XPS, energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.
[0257] Furthermore, the crystal structure of surface layer 100a, grain boundaries, and the like can be analyzed by electron beam diffraction or the like of a cross section of positive electrode active material 100.
[0258] ≪Charging method≫ For example, charging for determining whether a composite oxide is the positive electrode active material 100 of one embodiment of the present invention can be performed by preparing a coin cell (CR2032 type, diameter 20 mm, height 3.2 mm) using the composite oxide for the positive electrode and lithium metal for the counter electrode. The coin cell has an electrolyte, a separator, a positive electrode can, and a negative electrode can.
[0259] More specifically, for the positive electrode, a slurry in which a positive electrode active material, a conductive material, and a binder are mixed is applied to a positive electrode current collector made of aluminum foil and used.
[0260] The counter electrode can be made of lithium metal.
[0261] The lithium salt used is 1 mol / L lithium hexafluorophosphate (LiPF6), the electrolyte is a mixed solvent of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of EC:DEC = 3:7, and vinylene carbonate (VC) is added as an additive at 2 wt% of the mixed solvent.
[0262] The separator may be a 25 μm thick porous polypropylene film.
[0263] The positive electrode can and the negative electrode can may be made of stainless steel (SUS).
[0264] The coin cell prepared under the above conditions is charged at an arbitrary voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). The charging method is not particularly limited as long as the charging can be performed at an arbitrary voltage for a sufficient time. For example, when charging by CCCV, the current in CC charging can be 20mA / g or more and 100mA / g or less per weight of the positive electrode active material. CV charging can be completed at 2mA / g or more and 10mA / g or less per weight of the positive electrode active material. In order to observe the phase change of the positive electrode active material, it is desirable to charge at such a small current value. The temperature is 25°C. After charging in this way, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, and a positive electrode active material with an arbitrary charge capacity can be obtained. When various analyses are performed after this, it is preferable to seal in an argon atmosphere in order to suppress reactions with external components. For example, XRD can be performed by sealing in an airtight container in an argon atmosphere. In addition, it is preferable to quickly take out the positive electrode after charging is completed and provide it for analysis. Specifically, it is preferable to do so within one hour after the completion of charging, and more preferably within 30 minutes.
[0265] In addition, when analyzing the crystal structure in the charged state after multiple charging and discharging, the multiple charging and discharging conditions may be different from the above charging conditions. For example, charging can be performed by constant current charging up to an arbitrary voltage (e.g., 4.6V, 4.65V, 4.7V, 4.75V, or 4.8V) with a current value of 20mA / g or more and 100mA / g or less per weight of the positive electrode active material, followed by constant voltage charging until the current value becomes 2mA / g or more and 10mA / g or less per weight of the positive electrode active material, and discharging can be performed by constant current discharging at 2.5V and 20mA / g or more and 100mA / g or less.
[0266] Furthermore, when analyzing the crystal structure in the discharged state after multiple charge / discharge cycles, constant current discharge can be performed at, for example, 2.5 V, with a current value of 20 mA / g or more and 100 mA / g or less per weight of the positive electrode active material.
[0267] <xrd> As long as appropriate adjustment and calibration are performed, the apparatus and conditions for XRD measurement are not particularly limited. For example, the measurement can be performed using the following apparatus and conditions. XRD equipment: Bruker AXS, D8 ADVANCE X-rays: Cu Kα Output: 40kV, 40mA Divergence angle: Div.Slit, 0.5° Detector: LynxEye Scan method: 2θ / θ continuous scan Measurement range (2θ): 15° to 90° Step width (2θ): 0.01° setting Counting time: 1 second / step Sample stage rotation: 15 rpm The standard sample used for adjustment and calibration may be, for example, NIST (National Institute of Standards and Technology) standard aluminum oxide sintered plate SRM 1976.
[0268] If the measurement sample is a powder, it can be set by placing it on a glass sample holder, sprinkling the sample on a greased silicone non-reflective plate, etc. If the measurement sample is a positive electrode, the positive electrode can be attached to a substrate with double-sided tape, and the positive electrode active material layer can be set to match the measurement surface required by the device.
[0269] To make the characteristic X-rays monochromatic, a filter may be used, or it may be done using XRD data analysis software after obtaining the XRD pattern. For example, using DIFFRAC.EVA (XRD data analysis software manufactured by Bruker), the peak due to CuKα2 radiation can be removed and only the peak due to CuKα1 radiation can be extracted. The same software can also be used to remove background.
[0270] In this specification, data processing will be described when referring to the 2θ value of a certain diffraction peak. First, a calculation model is fitted to an XRD pattern using crystal structure analysis software to obtain a calculated pattern. In the calculated pattern, the 2θ value at which the peak top of the diffraction peak appears is called the 2θ value of the diffraction peak. The crystal structure analysis software used for fitting is not particularly limited, but for example, TOPAS ver. 3 (crystal structure analysis software manufactured by Bruker) can be used.
[0271] The ideal powder XRD patterns calculated from the O3' type crystal structure and the H1-3 type crystal structure model using CuKα1 radiation are shown in Figures 14 and 15. For comparison, the Li x The ideal XRD patterns calculated from the crystal structures of LiCoO2O3 with x=1 in CoO2 and trigonal O1 with x=0 are also shown. The patterns of LiCoO2(O3) and CoO2(O1) were created using Reflex Powder Diffraction, a module of Materials Studio (BIOVIA), based on the crystal structure information obtained from ICSD (Inorganic Crystal Structure Database). The 2θ range was 15° to 75°, Step size=0.01, and wavelength λ1=1.540562×10 -10 m and λ2 were not set, and Monochromator was set to single. The XRD pattern of the H1-3 type crystal structure was created in the same manner as above based on the information of the H1-3 type crystal structure shown in FIG. 15. The XRD pattern of the O3' type crystal structure was estimated from the XRD pattern of the positive electrode active material of one embodiment of the present invention, and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), and the XRD pattern was created in the same manner as the others.
[0272] As shown in FIG. 14, in the O3′ type crystal structure, diffraction peaks appear at 2θ=19.25±0.12° (19.13° or more and 19.37° or less) and 2θ=45.47±0.10° (45.37° or more and 45.57° or less).
[0273] However, as shown in Figure 15, no peaks appear at these positions in the H1-3 type crystal structure and trigonal O1. x When x in CoO2 is small, diffraction peaks appear at 2θ = 19.25 ± 0.12° (19.13° or more and 19.37° or less) and 2θ = 45.47 ± 0.10° (45.37° or more and 45.57° or less), which can be said to be a characteristic of the positive electrode active material 100 of one embodiment of the present invention.
[0274] This can also be said to be because the positions at which XRD diffraction peaks appear are close between the crystal structures of x = 1 and x ≦ 0.24. More specifically, for the main diffraction peaks of the crystal structures of x = 1 and x ≦ 0.24 that appear at 2θ between 42° and 46°, the difference in 2θ is 0.7° or less, more preferably 0.5° or less.
[0275] The positive electrode active material 100 according to one embodiment of the present invention is Li x When x in CoO2 is small, it has an O3' type crystal structure, but it does not have to be entirely O3' type crystal structure. It may contain other crystal structures, or may be partially amorphous. However, when Rietveld analysis is performed on the XRD pattern, it is preferable that the O3' type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more. If the O3' type crystal structure is 50% or more, more preferably 60% or more, and even more preferably 66% or more, it can be a positive electrode active material with sufficiently excellent cycle characteristics.
[0276] In addition, the sharpness of the diffraction peaks in the XRD pattern indicates the high crystallinity. Therefore, it is preferable that each diffraction peak after charging is sharp, that is, the half-width is narrow. The half-width varies depending on the XRD measurement conditions or the value of 2θ, even if the peak is generated from the same crystal phase. In the case of the above-mentioned measurement conditions, in the peak observed at 2θ=43° to 46°, the half-width is preferably 0.2° or less, more preferably 0.15° or less, and even more preferably 0.12° or less. A narrow half-width and high crystallinity contribute to the stabilization of the crystal structure after charging. On the other hand, in the conventional LiCoO2, even if a part of it can have a structure similar to the O3' type crystal structure, the crystallite size becomes small and the peak becomes broad and small.
[0277] <xps> In X-ray photoelectron spectroscopy (XPS), in the case of inorganic oxides, when monochromatic aluminum Kα rays are used as X-rays, it is possible to analyze a region from the surface to a depth of about 2 to 8 nm (usually 5 nm or less), so the concentration of each element can be quantitatively analyzed in a region about half the depth of the surface layer 100a. In addition, narrow scan analysis can be used to analyze the bonding state of elements. The quantitative accuracy of XPS is often about ±1 atomic %, and the lower detection limit is about 1 atomic %, depending on the element.
[0278] The concentration of the added element may be compared in terms of the ratio to cobalt. By using the ratio to cobalt, it is preferable to compare the positive electrode active material after reducing the influence of carbonates and the like chemically adsorbed after the preparation. For example, the ratio Mg / Co of the number of atoms of magnesium and cobalt determined by XPS analysis is preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, more preferably 0.700 or more, more preferably 0.800 or more, more preferably 0.900 or more, and more preferably 1.000 or more. In addition, Mg / Co is preferably 2.000 or less, preferably 1.500 or less, preferably 1.400 or less, preferably 1.300 or less, or preferably 1.200 or less.
[0279] The ratio of the number of atoms of nickel to cobalt, Ni / Co, as determined by XPS analysis, is preferably 0.05 or more, more preferably 0.06 or more, more preferably 0.07 or more, more preferably 0.08 or more, and more preferably 0.09 or more. Ni / Co is preferably 0.200 or less, preferably 0.150 or less, preferably 0.140 or less, preferably 0.130 or less, preferably 0.120 or less, or preferably 0.110 or less.
[0280] The ratio of the number of fluorine and cobalt atoms F / Co, as determined by XPS analysis, is preferably 0.100 or more, more preferably 0.200 or more, more preferably 0.300 or more, more preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, and more preferably 0.700 or more. F / Co is preferably 1.500 or less, preferably 1.200 or less, preferably 1.100 or less, preferably 1.000 or less, and preferably 0.900 or less.
[0281] The above range indicates that these additive elements are not attached to a narrow range on the surface of the positive electrode active material 100, but are widely distributed at preferred concentrations in the surface layer 100a of the positive electrode active material 100. In other words, as a result of the XPS analysis of the positive electrode active material 100, the above range indicates that the crystal structure is not easily broken even when charging and discharging are repeated such that x is 0.24 or less, and excellent cycle characteristics can be achieved.
[0282] Furthermore, when the positive electrode active material 100 according to one embodiment of the present invention is analyzed by XPS, the peak indicating the bond energy between fluorine and other elements is preferably equal to or greater than 682 eV and less than 685 eV, and more preferably about 684.3 eV, which is a different value from both the bond energy of lithium fluoride (685 eV) and the bond energy of magnesium fluoride (686 eV).
[0283] Furthermore, when the positive electrode active material 100 according to one embodiment of the present invention is subjected to XPS analysis, the peak showing the bond energy between magnesium and other elements is preferably equal to or greater than 1302 eV and less than 1304 eV, and more preferably about 1303 eV, which is a different value from the bond energy of magnesium fluoride, 1305 eV, and is close to the bond energy of magnesium oxide.
[0284] <edx> It is preferable that one or more selected from the additive elements contained in the positive electrode active material 100 have a concentration gradient. It is more preferable that the depth from the surface of the concentration peak differs depending on the additive element in the positive electrode active material 100. The concentration gradient of the additive element can be evaluated, for example, by exposing a cross section of the positive electrode active material 100 using a focused ion beam (FIB) or the like and analyzing the cross section using energy dispersive X-ray spectroscopy (EDX), electron probe microanalysis (EPMA), or the like.
[0285] Among EDX measurements, EDX area analysis is performed by scanning an area and evaluating the area in two dimensions. EDX line analysis is performed by scanning a line and evaluating the distribution of atomic concentration within the positive electrode active material. Line analysis may also be used to extract data from a linear area of EDX area analysis. Point analysis is used to measure an area without scanning it.
[0286] By EDX surface analysis (for example, element mapping), the concentration of the additive element in the surface layer 100a, the inside 100b, and the vicinity of the grain boundary of the positive electrode active material 100 can be quantitatively analyzed. In addition, the concentration distribution and maximum value of the additive element can be analyzed by EDX line analysis. In addition, the analysis after thinning the sample by FIB or the like is more preferable because it can analyze the concentration distribution in the depth direction from the surface to the center of the positive electrode active material in a specific region without being affected by the distribution in the depth direction. In addition, in order to increase the spatial resolution in STEM-EDX line analysis, it is preferable that the beam diameter of the electron beam (also called the beam diameter, probe diameter, or probe diameter) is small. The beam diameter in STEM-EDX line analysis is preferably 0.3 nm or less, more preferably 0.2 nm or less, and even more preferably 0.1 nm or less.
[0287] Therefore, when EDX area analysis or EDX point analysis is performed on positive electrode active material 100 of one embodiment of the present invention, it can be confirmed that the concentration of each added element, particularly added element X, in surface layer portion 100a is higher than that in interior portion 100b.
[0288] In STEM-EDX analysis, the graph of the amount of characteristic X-rays of the element does not change sharply in principle or due to measurement errors, and it may be difficult to precisely determine the surface. Therefore, when referring to the depth direction in STEM-EDX analysis, the amount of characteristic X-rays of the transition metal M is the average value M of the amount of characteristic X-rays of the internal transition metal M. AVE and the average amount of characteristic X-rays of the transition metal M in the background, M BG The point where the amount of oxygen characteristic X-rays detected is 50% of the sum of the amount of oxygen characteristic X-rays detected inside the sample, or the amount of oxygen characteristic X-rays detected inside the sample is the average amount of oxygen characteristic X-rays detected inside the sample. AVE and the average amount of oxygen characteristic X-rays detected in the background, O BG The reference point on the surface is the point where the detection amount of the characteristic X-rays of the transition metal M is 50% of the sum of the average detection amount of the characteristic X-rays of the transition metal M inside and the average detection amount of the characteristic X-rays of the transition metal M in the background. If the point where the detection amount of the characteristic X-rays of oxygen is 50% of the sum of the average detection amount of the characteristic X-rays of oxygen inside and the average detection amount of the characteristic X-rays of oxygen in the background is different from the point where the detection amount of the characteristic X-rays of oxygen is 50% of the sum of the average detection amount of the characteristic X-rays of oxygen inside and the average detection amount of the characteristic X-rays of oxygen in the background, this is considered to be due to the influence of metal oxides, carbonates, etc. containing oxygen attached to the surface. AVE and the average amount of characteristic X-rays of the transition metal M in the background, M BG The point where the sum of the transition metals M and M is 50% can be adopted as the surface position of the positive electrode active material. In the case of a positive electrode active material having multiple transition metals M, the M of the element with the largest amount of characteristic X-rays detected inside can be adopted as the surface position of the positive electrode active material. AVE and M BG The reference point can be obtained using the following formula:
[0289] The average background value of the transition metal M BG can be obtained by averaging, for example, a range of 2 nm or more, preferably 3 nm or more, from the outside of the positive electrode active material, avoiding the vicinity where the amount of detected transition metal M starts to increase. AVE can be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, at a depth of 30 nm or more, preferably 50 nm or more, from the region where the counts of the transition metal M and oxygen are saturated and stable, for example, the region where the detected amount of the transition metal M starts to increase. BG and the average internal detection amount of oxygen, O AVE can also be found in the same way.
[0290] The surface of the positive electrode active material 100 in a cross-sectional STEM (scanning transmission electron microscope) image or the like is the boundary between an area where an image originating from the crystal structure of the positive electrode active material is observed and an area where it is not observed, and is the outermost area where atomic columns originating from the atomic nuclei of metal elements having atomic numbers larger than that of lithium among the metal elements constituting the positive electrode active material are confirmed. The surface in a STEM image or the like may be determined in conjunction with an analysis with higher spatial resolution.
[0291] In addition, a peak in STEM-EDX analysis refers to a convex maximum value that appears in a graph of the characteristic X-ray intensity for each element, or the maximum value of the characteristic X-ray for each element. Note that noise in STEM-EDX analysis can be considered to be a measurement value with a half-width less than the spatial resolution (R), for example, R / 2 or less.
[0292] For example, when EDX surface analysis or EDX point analysis is performed on a positive electrode active material 100 having magnesium as an additive element, the magnesium concentration of the surface layer 100a is preferably higher than the magnesium concentration of the interior 100b. When EDX line analysis is performed, the peak of the magnesium concentration of the surface layer 100a is preferably present at a depth of 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. Alternatively, it is preferably within ±1 nm from the surface. Furthermore, it is preferable that the magnesium concentration attenuates to 60% or less of the peak at a point 1 nm deep from the peak. Furthermore, it is preferable that the magnesium concentration attenuates to 30% or less of the peak at a point 2 nm deep from the peak. Note that the peak of concentration here refers to the maximum value of the concentration. Note that, due to the influence of the spatial resolution in EDX line analysis, the position where the magnesium concentration peak exists may take a negative value as a depth from the surface toward the inside.
[0293] In the positive electrode active material 100 having magnesium and fluorine as additive elements, the distribution of fluorine preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the peak of the fluorine concentration and the peak of the magnesium concentration is preferably within 10 nm, more preferably within 3 nm, and even more preferably within 1 nm.
[0294] In addition, when EDX analysis is performed, the fluorine concentration peak of the surface layer 100a is preferably present at a depth of 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. Alternatively, it is preferable that the peak of the magnesium concentration is present slightly inside the fluorine concentration peak, which increases resistance to hydrofluoric acid. For example, it is more preferable that the magnesium concentration peak is 0.5 nm or more inside the fluorine concentration peak, and even more preferable that the magnesium concentration peak is 1.5 nm or more inside the fluorine concentration peak.
[0295] In the positive electrode active material 100 having nickel as an additive element, the nickel concentration peak of the surface layer 100a is preferably present at a depth of 3 nm from the surface of the positive electrode active material 100 toward the center, more preferably at a depth of 1 nm, and even more preferably at a depth of 0.5 nm. Alternatively, it is preferably within ±1 nm from the surface. In the positive electrode active material 100 having magnesium and nickel, the distribution of nickel is preferably superimposed on the distribution of magnesium. For example, the difference in the depth direction between the peak of nickel concentration and the peak of magnesium concentration is preferably within 10 nm, more preferably within 3 nm, and even more preferably within 1 nm.
[0296] Furthermore, when the positive electrode active material 100 contains aluminum as an added element, it is preferable that the peak of the magnesium, nickel, or fluorine concentration is closer to the surface than the peak of the aluminum concentration in the surface layer portion 100a when EDX line analysis is performed. For example, the peak of the aluminum concentration is preferably present at a depth of 0.5 nm to 50 nm from the surface toward the center of the positive electrode active material 100, and more preferably at a depth of 3 nm to 30 nm.
[0297] In addition, when EDX line analysis, surface analysis, or point analysis is performed on the positive electrode active material 100, the ratio of the number of atoms of magnesium Mg and cobalt Co (Mg / Co) at the peak of magnesium concentration is preferably 0.05 to 0.6, more preferably 0.1 to 0.4. The ratio of the number of atoms of aluminum Al and cobalt Co (Al / Co) at the peak of aluminum concentration is preferably 0.01 to 0.6, more preferably 0.05 to 0.45. The ratio of the number of atoms of nickel Ni and cobalt Co (Ni / Co) at the peak of nickel concentration is preferably 0 to 0.2, more preferably 0.01 to 0.1, more preferably 0.05 to 0.1. The ratio of the number of atoms of fluorine F and cobalt Co (F / Co) at the peak of fluorine concentration is preferably 0 to 1.6, more preferably 0.1 to 1.4.
[0298] <Cleaning> Although various analyses have been described, before the analysis, the samples such as the positive electrode active material and the positive electrode active material layer may be washed in order to remove the electrolyte, binder, conductive material, or compounds derived from these that are attached to the surface of the positive electrode active material. At this time, lithium may dissolve in the solvent used for washing, but even in this case, the added element is unlikely to dissolve, and therefore the atomic ratio of the added element is not affected.
[0299] <Positive electrode current collector> A metal foil can be used as the positive electrode current collector. The positive electrode can be formed by applying a slurry onto a metal foil and drying it. Note that pressing may be performed after drying. The positive electrode is formed by forming an active material layer on a positive electrode current collector 21.
[0300] As the current collector, a material having high electrical conductivity, such as metals such as stainless steel, gold, platinum, aluminum, and titanium, and alloys thereof, can be used. In addition, it is preferable that the material used for the positive electrode current collector does not dissolve at the potential of the positive electrode. In addition, an aluminum alloy to which an element that improves heat resistance, such as silicon, titanium, neodymium, scandium, or molybdenum, is added can be used. The current collector can be appropriately shaped in a foil, plate, sheet, net, punched metal, or expanded metal form. It is preferable to use a current collector having a thickness of 5 μm or more and 30 μm or less.
[0301] <Positive electrode binder> The binder that can be used in the positive electrode will be described.
[0302] As the binder, it is preferable to use a rubber material such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, ethylene-propylene-diene copolymer, etc. As the binder, fluororubber can be used.
[0303] Furthermore, as the binder, it is preferable to use materials such as polystyrene, methyl polyacrylate, methyl polymethacrylate (polymethyl methacrylate (abbreviation: PMMA)), sodium polyacrylate, polyvinyl alcohol (abbreviation: PVA), polyethylene oxide (abbreviation: PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (abbreviation: PVDF), polyacrylonitrile (abbreviation: PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose.
[0304] In addition to the binder, it may be preferable to use a thickener. For example, a water-soluble polymer may be used as the thickener. For example, polysaccharides may be used as the water-soluble polymer. For example, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, and regenerated cellulose, or starch may be used as the polysaccharide.
[0305] When the binder covers the surface of the active material, or when the binder in contact with the surface forms a film, it can play the role of a passive film, and is expected to have the effect of suppressing the decomposition of the electrolyte. Here, the "passive film" refers to a film that has no electrical conductivity or a film with extremely low electrical conductivity. For example, when a passive film is formed on the surface of the active material, it can suppress the decomposition of the electrolyte at the battery reaction potential. Moreover, it is more preferable that the passive film suppresses electrical conductivity and can conduct lithium ions.
[0306] <Conductive material> The conductive material that can be used for the positive electrode and the negative electrode is also called a conductive agent or a conductive assistant, and is preferably a carbon material. By attaching the conductive material between a plurality of active materials, the plurality of active materials are electrically connected to each other, and the conductivity is increased. Note that the term "attachment" does not only refer to the physical adhesion between the active material and the conductive material, but also includes the case where a covalent bond is formed, the case where the conductive material is bonded by van der Waals forces, the case where the conductive material covers a part of the surface of the active material, the case where the conductive material is embedded in the surface irregularities of the active material, and the case where the active material is electrically connected even if they are not in contact with each other.
[0307] As the conductive material, for example, one or more of carbon blacks such as acetylene black (AB) and furnace black, graphites such as artificial graphite and natural graphite, carbon fibers such as carbon nanofibers and carbon nanotubes, graphene, and graphene compounds can be used.
[0308] Acetylene black is difficult to bring into surface contact with other active materials, and tends to make point contact. For this reason, when an active material is mixed with acetylene black, it is possible to use a large amount of acetylene black to reduce the contact resistance, but this reduces the ratio of active material, resulting in a decrease in the discharge capacity of the secondary battery. In addition, acetylene black is a material that easily aggregates, and it is preferable to form a slurry using a dispersant or the like so that it is uniformly dispersed.
[0309] In view of these, it is preferable that the weight ratio of acetylene black in the negative electrode is less than or equal to the weight ratio of silicon particles used in the negative electrode active material. In other words, by satisfying this weight ratio, acetylene black can be mixed so as to exhibit high dispersibility without decreasing the proportion of silicon particles. Therefore, the discharge capacity of the secondary battery can be increased.
[0310] As the carbon fiber, for example, mesophase pitch carbon fiber, isotropic pitch carbon fiber, etc. can be used. As the carbon fiber, carbon nanofiber or carbon nanotube can be used. Carbon nanotube can be produced by vapor phase growth method, for example. VGCF (registered trademark) can be used as the carbon fiber.
[0311] The above-mentioned graphene includes graphene, multi-layer graphene, multi-graphene, etc. The above-mentioned graphene compound includes graphene oxide, multi-layer graphene oxide, multi-graphene oxide, reduced graphene oxide, reduced multi-layer graphene oxide, reduced multi-graphene oxide, graphene quantum dots, etc. Graphene refers to a substance that has carbon, has a shape such as a plate shape or a sheet shape, and has a two-dimensional structure formed by six-membered carbon rings. The two-dimensional structure formed by the six-membered carbon rings may be called a carbon sheet. In addition, graphene is preferably hard and has a curved shape. The graphene compound may have a hole in the carbon ring or may have a ring larger than six (e.g., a seven-membered ring), and may also have a functional group. In addition, since the graphene compound is soft, it may be rolled up into a carbon nanofiber, for example.
[0312] Since graphene or a graphene compound can be in surface contact with an active material, the amount of the graphene or the graphene compound is smaller than that of a normal conductive material. This allows the ratio of the active material in the active material layer to be increased, thereby increasing the discharge capacity of the secondary battery.
[0313] Although the carbon fibers are in surface contact with the active materials, the fiber length of the carbon fibers is longer than the fiber diameter of the carbon fibers, so that an appropriate electrical path can be formed between the active materials, which are separated from each other, and therefore the amount of carbon fibers can be smaller than that of a normal conductive material. Therefore, the proportion of the active material in the active material layer can be increased, and the discharge capacity of the secondary battery can be increased.
[0314] <Electrolyte> As one form of the electrolytic solution, an electrolytic solution having a solvent and an electrolyte dissolved in the solvent can be used. As the solvent, an aprotic solvent is preferable, and for example, one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc., or two or more of these can be used in any combination and ratio. When two or more types are used, it may be referred to as a mixed solvent.
[0315] In addition, as another form of the electrolyte, one or more ionic liquids (room-temperature molten salts) that are flame-retardant and non-volatile can be used as the solvent. In this case, even if the internal temperature of the storage device rises due to an internal short circuit or overcharging, the rupture and ignition of the storage device can be prevented. The ionic liquid is composed of a cation and an anion, and includes an organic cation and an anion. Examples of the organic cation used in the electrolyte include aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations, and quaternary phosphonium cations, and aromatic cations such as imidazolium cations and pyridinium cations. Examples of the anion used in the electrolyte include monovalent amide anions, monovalent methide anions, fluorosulfonic acid anions, perfluoroalkylsulfonic acid anions, tetrafluoroborate anions, perfluoroalkylborate anions, hexafluorophosphate anions, and perfluoroalkylphosphate anions. As a specific example, EMI-FSA (1-ethyl-3-methylimidazolium bis(fluorosulfonyl)amide) can be used.
[0316] Examples of the electrolyte (also called lithium salt) dissolved in the above-mentioned solvent include LiPF6, LiN(FSO2)2 (lithium bis(fluorosulfonyl)amide: LiFSA), LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 , Li2B 12 Cl 12 Lithium salts such as LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, and lithium bis(oxalato)borate (chemical formula: Li(C2O4)2, abbreviated as LiBOB) can be used alone or in any combination and ratio of two or more of these.
[0317] An additive may be mixed into the mixed solvent in which the lithium salt is dissolved. Examples of the additive include vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate)borate (LiBOB), and dinitrile compounds such as succinonitrile and adiponitrile. The concentration of the additive may be, for example, 0.1 wt% to 5 wt% of the mixed solvent in which the lithium salt is dissolved.
[0318] <Electrolyte Example 1> The mixed solvent used in the lithium ion battery of the present invention can be a material that has excellent lithium ion conductivity even during charging and / or discharging (charging and discharging) in a low-temperature environment.
[0319] An example of the electrolyte solution will be described below. The electrolyte solution described in this embodiment is a mixed solvent in which a lithium salt is dissolved, and the mixed solvent is liquid at room temperature. The mixed solvent is not limited to being liquid at room temperature, and a solid electrolyte that is solid at room temperature can be used. Alternatively, a semi-solid electrolyte that includes both liquid and solid at room temperature can be used. Semi-solid electrolytes include gel-like electrolytes.
[0320] The mixed solvent of the electrolyte solution according to one embodiment of the present invention may contain two or more selected from fluorinated cyclic carbonates (also referred to as fluorinated cyclic carbonates) and fluorinated chain carbonates (also referred to as fluorinated chain carbonates).
[0321] As the fluorinated cyclic carbonate, fluoroethylene carbonate (fluoroethylene carbonate, FEC, F1EC), difluoroethylene carbonate (DFEC, F2EC), trifluoroethylene carbonate (F3EC), or tetrafluoroethylene carbonate (F4EC) can be used. DFEC has isomers such as cis-4,5 and trans-4,5. Since all of the fluorinated cyclic carbonates have electron-withdrawing substituents, it is believed that the solvation energy of lithium ions is low.
[0322] The following structural formula (H10) is the structural formula of FEC, in which the electron-withdrawing substituent is an F group.
[0323] [ka]
[0324] Methyl 3,3,3-trifluoropropionate is an example of a fluorinated chain carbonate. The following structural formula (H22) is the structural formula of methyl 3,3,3-trifluoropropionate. The abbreviation for methyl 3,3,3-trifluoropropionate is "MTFP." In MTFP, the electron-withdrawing substituent is a CF3 group.
[0325] [ka]
[0326] As a fluorinated chain carbonate, there is trifluoromethyl 3,3,3-trifluoropropionate. The following structural formula (H23) is the structural formula of trifluoromethyl 3,3,3-trifluoropropionate. The electron-withdrawing substituent is the CF3 group.
[0327]
Chem.
[0328] As a fluorinated chain carbonate, there is trifluoromethyl propionate. The following structural formula (H24) is the structural formula of trifluoromethyl propionate. The electron-withdrawing substituent is the CF3 group.
[0329]
Chem.
[0330] As a fluorinated chain carbonate, there is methyl 2,2-difluoropropionate. The following structural formula (H25) is the structural formula of methyl 2,2-difluoropropionate. The electron-withdrawing substituent is the CF2 group.
[0331]
Chem.
[0332] <FEC and MTFP> The mixed solvent described in this embodiment preferably contains FEC and MTFP. The reason will be explained.
[0333] FEC is a cyclic carbonate with a high dielectric constant, and therefore when used in an organic solvent, it has the effect of promoting the dissociation of lithium salts. On the other hand, FEC has a substituent that exhibits electron-withdrawing properties, and therefore desolvation with lithium ions proceeds more easily than ethylene carbonate (EC). Specifically, the solvation energy of lithium ions in FEC is smaller than that of EC that does not have a substituent that exhibits electron-withdrawing properties. Therefore, lithium ions are easily released from the surface of the positive electrode active material and the surface of the negative electrode active material, and the internal resistance of the secondary battery can be reduced. Furthermore, since FEC has a deep highest occupied molecular orbital (HOMO: Highest Occupied Molecular Orbital) level, it is difficult to oxidize and oxidation resistance is improved. On the other hand, there is a concern that FEC has a high viscosity. Therefore, it is recommended to use a mixed organic solvent containing not only FEC but also MTFP in the electrolyte. MTFP is a chain carbonate, and can have the effect of lowering the viscosity of the electrolyte, or maintaining the viscosity at room temperature (typically 25°C) even at low temperatures (typically 0°C). Furthermore, although MTFP has a smaller solvation energy than methyl propionate (abbreviated as "MP"), which does not have an electron-withdrawing substituent, it may form a solvate with lithium ions when used in an electrolyte.
[0334] The organic solvent described above is preferably highly purified with a low content of particulate waste or molecules other than the constituent molecules of the organic solvent (hereinafter, simply referred to as "impurities", including oxygen (O2), water (H2O) or moisture). It is also preferable that the reaction by-products during synthesis are suppressed through appropriate purification. Specifically, the impurity concentration of the electrolyte is 100 ppm or less, preferably 50 ppm or less, and more preferably less than 10 ppm. The concentration of moisture among the impurities can be detected by Karl Fischer titration.
[0335] Furthermore, it is preferable that the above-mentioned organic solvent has almost no peaks due to impurities confirmed by NMR measurement or the like. Almost no peaks can be confirmed includes that the ratio of the integrated area of the peak due to the impurities to the integrated area of the peak due to the main component (simply called integral ratio) is 0.005 or less, preferably 0.002 or less. The device used for NMR measurement is not particularly limited, but for example, Bruker's "AVANCE III 400 type" can be used. In addition, the central peak of the five peaks of acetonitrile derived from acetonitrile-d3 used as a solvent in 1H-NMR measurement can be 1.94 ppm.
[0336] For example, in the case of MTFP, it is known that when 1H-NMR is measured using acetonitrile-d3 solvent, four peaks appear at δ between 3.29 ppm and 3.43 ppm. However, if other peaks appear in the vicinity, for example, if a peak appears at δ between 3.24 ppm and 3.29 ppm, the peak is considered to be due to impurities. Therefore, if the ratio (integral ratio) of the peak area between 3.24 ppm and 3.29 ppm to the peak area between 3.29 ppm and 3.43 ppm is 0.005 or less, preferably 0.002 or less, it can be said that the peaks due to impurities are almost not confirmed.
[0337] The measured values of the HOMO level, solvation energy, and melting point are summarized in the table below.
[0338] [Table 1]
[0339] FEC and MTFP having such physical properties are preferably mixed and used in a volume ratio of x:100-x (where 5≦x≦30, preferably 10≦x≦20) with the total content of these two mixed solvents being 100 vol%. In other words, MTFP is preferably mixed in a larger amount than FEC in the mixed solvent. The above volume ratio may be the volume ratio measured before mixing the mixed solvent, and the outside air during the mixing may be room temperature (typically 25° C.). A mixed solvent in which FEC and MTFP are mixed is preferable because it exhibits a viscosity that allows operation as a lithium ion battery and maintains an appropriate viscosity even in a low-temperature environment.
[0340] Since typical solvents used in lithium ion batteries freeze at about -20°C, it is difficult to fabricate a lithium ion battery that can be charged and discharged at -30°C, preferably -40°C. However, the mixed solvent described as an example in this embodiment allows the freezing point to be -30°C or lower, preferably -40°C or lower, and a lithium ion battery that can be charged and discharged even in a low-temperature environment can be realized. As a result, a lithium ion battery that can be charged and discharged in a wide temperature range including at least a low-temperature environment can be realized.
[0341] Although FEC has been explained above as a representative example, all of the organic compounds mentioned as fluorinated cyclic carbonates have the following characteristics: they have the effect of promoting the dissociation of lithium salts, they have small solvation energies so that the bonds between the lithium ions and the solvent are easily broken, and they have high viscosities so that they are difficult to use below freezing points when used alone.
[0342] Although MTFP has been described as a representative example above, any of the organic compounds described as fluorinated chain carbonates can be said to have the effect of reducing or maintaining the viscosity of the electrolyte solution according to one embodiment of the present invention. Therefore, if the mixed solvent according to one embodiment of the present invention contains a fluorinated cyclic carbonate and a fluorinated chain carbonate, a lithium ion battery that can be charged and discharged in a low-temperature environment can be provided.
[0343] <Electrolyte Example 2> As a mixed solvent for the electrolytic solution which is another aspect of the present invention, it contains ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC). When the total content of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate is 100 vol%, the volume ratio of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate is x:y:100 - x - y (where 5 ≤ x ≤ 35 and 0 < y < 65). Such a mixed solvent can be used. More specifically, a mixed solvent containing EC, EMC, and DMC in a volume ratio of EC:EMC:DMC = 30:35:35 can be used. Note that the above volume ratio may be the volume ratio before mixing the mixed solvent, and the outside air during the mixing may be at room temperature (typically 25°C).
[0344] EC is a cyclic carbonate and has a high relative dielectric constant, so it has the effect of promoting the dissociation of lithium salts. On the other hand, EC has a high viscosity and a high freezing point (melting point) of 38°C. Therefore, when using EC alone as a solvent, it is difficult to use in a low-temperature environment. Thus, the solvent specifically described as one aspect of the present invention is not EC alone, but further contains EMC and DMC. EMC is a chain carbonate and has the effect of lowering the viscosity of the electrolytic solution, and its freezing point is -54°C. Also, DMC is also a chain carbonate and has the effect of lowering the viscosity of the electrolytic solution, and its freezing point is -43°C. An electrolytic solution prepared using a mixed solvent in which EC, EMC, and DMC having such physical properties are mixed so that the total content of these three mixed solvents is 100 vol% and the volume ratio is x:y:100 - x - y (where 5 ≤ x ≤ 35 and 0 < y < 65) has the characteristic that its freezing point is -40°C or lower.
[0345] A general electrolytic solution used in lithium-ion batteries solidifies at about -20°C, so it is difficult to fabricate a battery that can be charged and discharged at -40°C. The electrolytic solution described as an example in this embodiment has a freezing point of -40°C or lower, so a lithium-ion battery that can be charged and discharged even in a low-temperature environment of -40°C can be realized.
[0346] In addition, as the electrolyte to be dissolved in the above-mentioned solvent, a lithium salt can be used. For example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 , Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, lithium bis(oxalate)borate (LiBOB), or any combination and ratio of two or more of these can be used. The lithium salt dissolved in the above-mentioned solvent is preferably 0.5 mol / L or more and 1.5 mol / L or less, preferably 0.7 mol / L or more and 1.3 mol / L or less, and more preferably 0.8 mol / L or more and 1.2 mol / L or less, relative to the volume of the above-mentioned solvent. As a specific example of use, LiPF6 is preferably 0.5 mol / L or more and 1.5 mol / L or less, preferably 0.7 mol / L or more and 1.3 mol / L or less, and more preferably 0.8 mol / L or more and 1.2 mol / L or less, relative to the volume of the above-mentioned solvent.
[0347] In addition, the mixed solvent is preferably highly purified with a low content of granular dust or elements other than the constituent elements of the electrolyte (hereinafter, simply referred to as "impurities"). Specifically, the weight ratio of impurities to the electrolyte is preferably 1% or less, more preferably 0.1% or less, and even more preferably 0.01% or less.
[0348] Furthermore, for the purpose of improving safety, etc., an additive such as vinylene carbonate (VC), propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate)borate (LiBOB), or a dinitrile compound such as succinonitrile or adiponitrile may be added to the electrolyte in order to form a coating (Solid Electrolyte Interphase Film) at the interface between the electrode (active material layer) and the electrolyte. The concentration of the additive may be, for example, 0.1 wt% to 5 wt% relative to the solvent.
[0349] In the electrolyte example 2, the lithium salt may be the same as that described in the electrolyte example 1. Also, as for the additive, the materials described in the electrolyte example 1 may be used.
[0350] As described above, examples of the electrolyte solution that can be used in the lithium-ion battery of one embodiment of the present invention have been described, but the electrolyte solution that can be used in the lithium-ion battery of one embodiment of the present invention is not limited to this example. Other materials can also be used as long as they have excellent lithium-ion conductivity even during charging and discharging in a low-temperature environment.
[0351] [Negative electrode] The negative electrode has a negative electrode active material layer and a negative electrode current collector, and the negative electrode active material layer has a negative electrode active material.
[0352] <Negative electrode binder> It is preferable to use a polymer having a carboxy group as the binder of the negative electrode, which is one aspect of the present invention. The carboxy group can be said to have two basic oxygens, one acidic hydrogen, and one electrophilic carbon. The carboxy group can also be said to have a hydroxyl group OH and a carbonyl group C=O, and to be a polar group. If the binder has a polar group such as a carboxy group, it is expected to interact with lithium ions, which are carrier ions, and for example, lithium ions are attracted, which may assist the insertion of lithium ions in the negative electrode active material. The carboxy group can be identified by FT-IR or the like.
[0353] Examples of polymers having carboxyl groups include polyglutamic acid (sometimes written as PGA), polyacrylic acid (sometimes written as PAA), and alginic acid (sometimes written as polysaccharide). Also, polyamino acids may be used as polymers having carboxyl groups, and specifically, polyornithine and polysarcosine may be applied as binders. Furthermore, polyaspartic acid may be applied as a polymer having ketone groups. Also, binary copolymers (copolymers) may be applied as polymers having ketone groups, and copolymers of acrylic acid and maleic acid, and copolymers of acrylic acid and sulfonic acid may be applied as binders. Using these as binders for the negative electrode also has the effect of reducing the amount of binder mixed in the negative electrode.
[0354] Among the above-mentioned polymers, polyglutamic acid or polyacrylic acid is particularly preferable as a binder for use in a negative electrode. The structural formula of polyglutamic acid is shown below.
[0355] [ka]
[0356] As is clear from the structural formula, polyglutamic acid has nitrogen in addition to the carboxyl group, and since the nitrogen has an unshared electron pair, it is expected to interact with the lithium ion, which is a carrier ion. For example, the unshared electron pair may attract the lithium ion and assist its insertion into the negative electrode active material.
[0357] As is clear from the structural formula, polyglutamic acid has a carbonyl group, C=O, in addition to a carboxy group. If the binder has a polar group such as a carbonyl group, it is expected to interact with lithium ions, which are carrier ions, and may assist, for example, in the insertion and removal of lithium ions in the negative electrode active material.
[0358] Either linear γ-polyglutamic acid or crosslinked γ-polyglutamic acid may be used as the binder, and these are collectively referred to as a structure mainly composed of γ-polyglutamic acid. Note that crosslinked γ-polyglutamic acid is more suitable for the binder in that it has a network structure. Furthermore, the molecular weight of polyglutamic acid is 1 million or more, preferably 3 million or more, and more preferably 10 million or more and 50 million or less.
[0359] Depending on the preparation method, polyglutamic acid may have a structure mainly composed of γ-polyglutamic acid containing other elements (e.g., Ca, Al, Na, Mg, Fe, Si, S). That is, polyglutamic acid may be neutralized with an alkali metal ion, e.g., lithium ion or sodium ion.
[0360] Such polyglutamic acid is hydrophilic, so deionized water can be used as a solvent, which is suitable for forming a slurry.
[0361] The structural formula of polyacrylic acid is shown below.
[0362] [ka]
[0363] As is clear from the structural formula, polyacrylic acid has a carboxy group.
[0364] A material obtained by cross-linking polyacrylic acid may also be used. This is preferable because it is possible to form a cross-linked structure, i.e., a network structure, which may enhance the function as a binder.
[0365] <Negative electrode active material> The negative electrode according to one embodiment of the present invention includes both carbon particles and silicon particles as negative electrode active materials. As the carbon particles, graphite, carbon having a layer structure like graphite, amorphous carbon, hard carbon, and carbon fibers are used. Specifically, graphite particles are preferably used as the carbon particles used in this specification.
[0366] Examples of graphite include artificial graphite and natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Here, as the artificial graphite, spherical graphite having a spherical shape can be used. For example, MCMB may have a spherical shape, which is preferable. In addition, it is relatively easy to reduce the surface area of MCMB, which may be preferable. Examples of natural graphite include flake graphite and spheroidized natural graphite.
[0367] In one embodiment of the present invention, the average particle size of the graphite particles is preferably 1 μm or more, more preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The graphite particles are preferably mixed with silicon particles and used in the negative electrode.
[0368] The average particle size of the graphite particles can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. In this specification and the like, the average particle size of the graphite particles can be determined as the median diameter (D50).
[0369] The specific surface area of a graphite particle is 0.5 m 2 / g or more 3m 2 / g or less. The specific surface area can be measured by the BET method. The specific surface area by the BET method is a value measured by the BET single point method using nitrogen gas adsorption, and can be measured using an automatic specific surface area / pore distribution measuring device Tristar II3020 (manufactured by Shimadzu Corporation).
[0370] Silicon particles having an average particle size of 100 nm or thereabouts are preferably used, and are sometimes called nanosilicon particles. Silicon has a capacity of 4200 mAh / g per weight, which is more than 10 times the capacity of graphite, 372 mAh / g (per active material weight). However, if the negative electrode is made only of silicon, there is a problem that rapid cycle deterioration occurs due to expansion and contraction during charging and discharging. Therefore, in order to improve cycle deterioration, nanosilicon particles in which silicon is finely divided to the above average particle size are suitable.
[0371] The average particle size of silicon particles can be measured by a particle size distribution meter using a laser diffraction / scattering method, etc. In this specification and the like, the average particle size of silicon particles can be determined as the median diameter (D50).
[0372] The silicon particles are preferably prepared by crushing the silicon raw material and adjusting the particle size to a uniform size. Through this adjustment, silicon particles having an average particle size of less than 1 μm can be obtained. If the average particle size is large, the negative electrode active material layer may become thick, so it is preferable that the average particle size is less than 1 μm. The silicon particles may be any silicon-based material, and specifically include at least one of silicon, silicon oxide, and silicon alloy.
[0373] The specific surface area of a silicon particle is 10 m 2 / g or more 35m 2 / g or less, preferably 10m 2 / g or more 15m 2 / g or less. The specific surface area can be measured by the BET method. The specific surface area by the BET method is a value measured by the BET single point method using nitrogen gas adsorption, and can be measured using an automatic specific surface area / pore distribution measuring device Tristar II3020 (manufactured by Shimadzu Corporation).
[0374] In one embodiment of the present invention, the negative electrode active material contains both graphite particles and silicon particles, so that a lithium ion battery with a high discharge capacity can be realized. In addition, since the average particle diameter of the graphite particles is different from that of the silicon particles, when these are mixed and used in the negative electrode, the amount of the negative electrode active material carried can be increased. In addition, in this specification, the amount carried means the weight of the negative electrode active material per unit surface area of the negative electrode current collector. The amount of the negative electrode active material carried can be determined according to the capacity of the positive electrode. If the amount carried is small, the output characteristics of the lithium ion battery can be improved, but if the amount is small, the discharge capacity will be small. Therefore, the amount of the negative electrode active material carried is set to 1.5 mg / cm. 2 The above is preferred.
[0375] In one embodiment of the present invention, the weight ratio of the graphite particles in the negative electrode active material layer is preferably greater than the weight ratio of the silicon particles, for example, the weight ratio of the graphite particles is preferably 5 to 15 times the weight ratio of the silicon particles. In other words, the weight ratio of silicon to the total weight of the powder material constituting the negative electrode active material is preferably 7.5 wt% to 37.5 wt%.
[0376] Furthermore, a conductive material may be added when the negative electrode active material layer is formed.
[0377] In a lithium ion battery, a negative electrode active material layer can be formed on one or both sides of a negative electrode current collector. The negative electrode active material layer is completed by applying a slurry onto the negative electrode current collector and then drying the slurry.
[0378] In this specification, the weight ratio of each raw material may be regarded as the blending ratio of each raw material when the slurry is prepared. That is, the weight ratio of the negative electrode active material is the blending ratio (wt%) of the negative electrode active material to the total weight of the negative electrode active material and the binder in the slurry, or the total weight of the negative electrode active material, the binder, and the conductive material. The weight ratio and blending ratio can be understood by replacing the negative electrode active material with the binder.
[0379] The weight ratio of the binder is preferably smaller than the weight ratio of the graphite particles, and in order to exert the effect as a binder, the weight ratio of the binder is preferably greater than 5 wt %.
[0380] <Negative electrode current collector> The negative electrode current collector can be made of the same material as the positive electrode current collector, as well as copper. Note that metals that form alloys with lithium ions, such as aluminum, cannot be used for the negative electrode current collector.
[0381] <Method of Producing Negative Electrode Active Material Layer> Here, a method for producing the negative electrode active material layer will be described. The negative electrode slurry, which is one embodiment of the present invention, may be prepared by mixing graphite particles, silicon particles, and a binder having a carboxyl group, and then adding a solvent and mixing. In the slurry, which is one embodiment of the present invention, the graphite particles, silicon particles, and a binder having a carboxyl group can be mixed simultaneously, which is preferable because the process can be shortened. Furthermore, when preparing the slurry, the graphite particles, silicon particles, a binder having a carboxyl group, and a solvent can also be mixed simultaneously. Furthermore, when preparing the slurry, a conductive material can also be mixed at the same time. As the conductive material, the conductive material described above can be used, and for example, acetylene black can be used.
[0382] FIG. 16 shows an example of a flow for producing a negative electrode active material layer.
[0383] First, there are prepared graphite particles 400, silicon particles 401, binder 402, and conductive material 403. As the binder, a polymer having a carboxy group is used.
[0384] <Step S60> The above-mentioned raw materials are each weighed, and the first mixing is performed in step S60 of Fig. 16. Specifically, the weight ratio of silicon particles 401 to the total weight of the powders mixed in the first mixing is in the range of 7.5wt% to 37.5wt%, and the weight ratio of binder 402 to the total weight is in the range of 10wt% to 50wt%. In addition, the weight ratio of conductive material 403 to the total weight is in the range of 0wt% to 20wt%. It is recommended to use acetylene black as conductive material 403 that satisfies the above weight ratios.
[0385] For example, silicon particles 401, graphite particles 400, binder 402, and conductive material 403 are weighed out to have a weight ratio of 3:5:1:1. Alternatively, without using a conductive material, silicon particles 401, graphite particles 400, and binder 402 are weighed out to have a weight ratio of 3:5:1. Alternatively, graphite particles 400, silicon particles 401, and binder 402 may be weighed out to have a weight ratio of 9:1:1.
[0386] <Mixing mixture 404 and solvent 405> In one embodiment of the present invention, since all the raw materials are powders in step S60, they are mixed before adding the solvent to obtain a mixture 404. Mixing the powders together allows for a uniform mixture. After that, the solvent 405 is preferably added. Deionized water is preferably used as the solvent 405.
[0387] <Step S61> After the solvent 405 is added, a second mixing is performed in step S61 of Figure 16 to produce a slurry 406. The second mixing is sometimes called a slurry preparation.
[0388] The slurry 406 is a material liquid used to form an active material layer on a current collector, and contains at least an active material, a binder, and a solvent, and may further contain a conductive material. The slurry is sometimes called an electrode slurry or an active material slurry.
[0389] Then, in step S62 of FIG. 16, the slurry 406 is applied onto the negative electrode current collector 407. Thereafter, in step S63 of FIG. 16, the slurry is dried. The drying may be performed by provisional drying and main drying. That is, two drying steps are performed, with the first drying step being performed under milder conditions. For example, the slurry may be dried in a dryer at 40° C. to 60° C. for 10 minutes to 1 hour, which may be regarded as provisional drying. Next, the main drying may be performed by drying in a dryer at 60° C. to 90° C. for 30 minutes to 1.5 hours. Pressing may be performed simultaneously with drying.
[0390] After drying, a pressing process is performed as step S64 in FIG. 16. A roll press machine can be used for the pressing process, and the upper and lower rollers can be heated to a temperature of 100° C. or more and 150° C. or less. In other words, heating can be performed simultaneously with the pressing process. The linear pressure during pressing should be 0.3 MPa or more and 1 MPa or less. Of course, the battery can be operated as a lithium ion battery even if the pressing process is omitted.
[0391] Through the above steps, a negative electrode 408 having a negative electrode active material layer over a negative electrode current collector 407 can be manufactured.
[0392] A lithium ion battery using the negative electrode 408 thus obtained has a large discharge capacity and exhibits excellent cycle characteristics.
[0393] It is advisable to prevent the silicon particles from being oxidized. For example, when preparing a slurry, it is preferable to carry out a mixing process so as to prevent the silicon particles from being oxidized.
[0394] The contents of this embodiment mode can be freely combined with the contents of other embodiment modes.
[0395] [Separator] A separator is disposed between the positive electrode and the negative electrode. The separator may be made of, for example, fibers containing cellulose such as paper, nonwoven fabric, glass fiber, ceramics, or synthetic fibers using nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic, polyolefin, or polyurethane. The separator is preferably processed into a bag shape and disposed so as to encase either the positive electrode or the negative electrode.
[0396] The separator may have a multi-layer structure. For example, an organic material film such as polypropylene or polyethylene may be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture of these. As the ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As the fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As the polyamide material, for example, nylon or aramid (meta-aramid or para-aramid) may be used.
[0397] Coating with ceramic materials improves oxidation resistance, suppressing the deterioration of the separator during high-voltage charging and improving the reliability of the secondary battery. Coating with fluorine-based materials also improves adhesion between the separator and electrodes, improving output characteristics. Coating with polyamide-based materials, especially aramid, improves heat resistance, improving the safety of the secondary battery.
[0398] For example, both sides of a polypropylene film may be coated with a mixed material of aluminum oxide and aramid, or the surface of the polypropylene film that contacts the positive electrode may be coated with a mixed material of aluminum oxide and aramid, and the surface that contacts the negative electrode may be coated with a fluorine-based material.
[0399] By using a separator with a multi-layer structure, the safety of the secondary battery can be maintained even if the overall thickness of the separator is thin, and therefore the capacity per volume of the secondary battery can be increased.
[0400] [Example of electrode laminate] An example of the structure of a laminate having a plurality of laminated electrodes will be described below.
[0401] Fig. 17(A) shows a top view of the positive electrode current collector 21, Fig. 17(B) shows the separator 40, Fig. 17(C) shows the negative electrode current collector 31, Fig. 17(D) shows the positive electrode lead 23 and the negative electrode lead 33, and Fig. 17(E) shows a top view of the film-like exterior body 50. The positive electrode lead 23 has a sealing layer 75 and a lead metal 76a, and the negative electrode lead 33 has a sealing layer 75 and a lead metal 76b.
[0402] The dimensions in each diagram in Fig. 17 are roughly the same, and the area B surrounded by the dashed line in Fig. 17(E) has roughly the same dimensions as the separator in Fig. 17(B). Also, the areas between the dashed line and the end in Fig. 17(E) become sealing portion 51 and sealing portion 52, respectively.
[0403] Moreover, the protruding portion of the positive electrode current collector 21 (the portion indicated by the dashed line in FIG. 17(A)) and the protruding portion of the negative electrode current collector 31 (the portion indicated by the dashed line in FIG. 17(C)) are referred to as tab portions.
[0404] Fig. 18(A) shows an example in which positive electrode active material layers 22 are provided on both sides of a positive electrode collector 21. In more detail, the layers are arranged in the following order: negative electrode collector 31, negative electrode active material layer 32, separator 40, positive electrode active material layer 22, positive electrode collector 21, positive electrode active material layer 22, separator 40, negative electrode active material layer 32, and negative electrode collector 31. Fig. 18(B) shows a cross-sectional view of this laminated structure cut by plane 70.
[0405] 18(A) shows an example in which two separators are used, but it is also possible to use a structure in which one separator is folded and both ends are sealed to form a bag shape, and the positive electrode current collector 21 is stored between the folded separators. Positive electrode active material layers 22 are formed on both sides of the positive electrode current collector 21 stored in the bag-shaped separator.
[0406] It is also possible to provide the negative electrode active material layer 32 on both sides of the negative electrode current collector 31. Fig. 18(C) shows an example of a secondary battery in which three negative electrode current collectors 31 having negative electrode active material layers 32 on both sides, four positive electrode current collectors 21 having positive electrode active material layers 22 on both sides, and eight separators 40 are sandwiched between two negative electrode current collectors 31 having a negative electrode active material layer 32 on only one side. In this case, four pouch-shaped separators may be used instead of eight separators.
[0407] Increasing the number of layers can increase the capacity of the secondary battery. Also, by providing positive electrode active material layers 22 on both sides of positive electrode current collector 21 and negative electrode active material layers 32 on both sides of negative electrode current collector 31, the thickness of the secondary battery can be reduced.
[0408] FIG. 19(A) shows a secondary battery formed by providing a positive electrode active material layer 22 on only one side of a positive electrode collector 21 and providing a negative electrode active material layer 32 on only one side of a negative electrode collector 31. In detail, a negative electrode active material layer 32 is provided on one side of the negative electrode collector 31, and a separator 40 is laminated so as to be in contact with the negative electrode active material layer 32. The surface of the separator 40 on the side not in contact with the negative electrode active material layer 32 is in contact with the positive electrode active material layer 22 of the positive electrode collector 21 on one side of which the positive electrode active material layer 22 is formed. Another positive electrode collector 21 on one side of which the positive electrode active material layer 22 is formed is in contact with the surface of the positive electrode collector 21. At this time, the positive electrode collectors 21 are arranged so that the surfaces on which the positive electrode active material layer 22 is not formed face each other. Then, a separator 40 is further formed, and the negative electrode current collector 31 having the negative electrode active material layer 32 formed on one side thereof is laminated so that the negative electrode active material layer 32 is in contact with the separator. A cross-sectional view of the laminated structure of Fig. 19(A) cut along a plane 71 is shown in Fig. 19(B).
[0409] Although two separators are used in FIG. 19(A), one separator may be folded and sealed at both ends to form a bag, and two positive electrode current collectors 21 having a positive electrode active material layer 22 disposed on one side thereof may be sandwiched between the separator.
[0410] Fig. 19(C) shows a diagram in which a plurality of the laminated structures of Fig. 19(A) are laminated. In Fig. 19(C), the surfaces of the negative electrode current collectors 31 on which the negative electrode active material layers 32 are not formed are arranged facing each other. Fig. 19(C) shows a state in which 12 positive electrode current collectors 21, 12 negative electrode current collectors 31, and 12 separators 40 are laminated.
[0411] The structure in which the positive electrode active material layer 22 is provided on only one side of the positive electrode collector 21 and the negative electrode active material layer 32 is provided on only one side of the negative electrode collector 31 and are stacked results in a thicker secondary battery than the structure in which the positive electrode active material layer 22 is provided on both sides of the positive electrode collector 21 and the negative electrode active material layer 32 is provided on both sides of the negative electrode collector 31. However, the surface of the positive electrode collector 21 on which the positive electrode active material layer 22 is not formed faces the surface of another positive electrode collector 21 on which the positive electrode active material layer 22 is not formed, and the current collectors are in contact with each other. Similarly, the surface of the negative electrode collector 31 on which the negative electrode active material layer 32 is not formed faces the surface of another negative electrode collector 31 on which the negative electrode active material layer 32 is not formed, and the current collectors are in contact with each other. For example, when a treatment for enhancing slidability is applied to the surface of the positive electrode current collector 21 on which the positive electrode active material layer 22 is not formed and / or the surface of the negative electrode current collector 31 on which the negative electrode active material layer 32 is not formed, the surfaces where the current collectors are in contact with each other can be made to slide easily without a large frictional force acting on the surfaces where the current collectors are in contact with each other. In other words, when the secondary battery is bent, the current collectors slide inside the secondary battery, making it easier to bend the secondary battery. Examples of treatments that can be used for enhancing slidability applied to the current collectors include a fluororesin (polytetrafluoroethylene, etc.) coat, a graphene coat, and a graphene compound coat.
[0412] 18 or 19, the positive electrode current collectors 21 are all fixed and electrically connected. Similarly, the negative electrode current collectors 31 are all fixed and electrically connected.
[0413] Here, it is preferable to simultaneously fix and electrically connect the positive electrode lead 23 and the multiple positive electrode current collectors 21. Similarly, it is preferable to simultaneously fix and electrically connect the negative electrode lead 33 and the multiple negative electrode current collectors 31. By simultaneously connecting the multiple current collectors and electrode leads in this manner, the production can be carried out efficiently.
[0414] In addition, the separator 40 is preferably shaped so that the positive electrode 20 and the negative electrode 30 are unlikely to be electrically shorted. For example, as shown in FIG. 20(A), when the width of each separator 40 is larger than that of the positive electrode 20 and the negative electrode 30, even when the relative positions of the positive electrode 20 and the negative electrode 30 are shifted due to deformation such as bending, these are unlikely to come into contact with each other, which is preferable. In addition, when one separator 40 is shaped like an accordion as shown in FIG. 20(B) or when one separator 40 is shaped so that the positive electrode 20 and the negative electrode 30 are alternately wound as shown in FIG. 20(C), these are preferable because they do not come into contact with each other even when the relative positions of the positive electrode 20 and the negative electrode 30 are shifted. In addition, in FIG. 20(B) and (C), an example is shown in which a part of the separator 40 is provided so as to cover the side surface of the stacked structure of the positive electrode 20 and the negative electrode 30.
[0415] 20 does not show the details of the positive electrodes 20 and the negative electrodes 30, but the above description may be referred to for the method of forming them. Also, while an example in which the positive electrodes 20 and the negative electrodes 30 are alternately arranged one by one is shown here, a configuration in which two positive electrodes 20 or two negative electrodes 30 are continuous with each other as shown in FIG. 19 may also be used.
[0416] In this embodiment, an example of a structure in which one rectangular film is folded in the center and the two ends are overlapped to seal is shown, but the shape of the film is not limited to a rectangle. Any shape with symmetry other than a rectangle, such as a triangle, a square, a pentagon, or other polygon, a circle, a star, or the like, may be used.
[0417] A lithium ion battery can be produced by housing the laminate described above with reference to FIGS. 18 to 20 and the electrolyte solution described above in an exterior body and sealing the exterior body.
[0418] [Exterior body] The battery's exterior body can be made of a metal material such as aluminum, stainless steel, or titanium, or a resin material. A film-shaped exterior body can also be used. As the film, a three-layer structure film can be used in which a metal thin film or metal foil with excellent flexibility such as aluminum, stainless steel, titanium, copper, or nickel is provided on a film made of a material such as polyethylene, polypropylene, polycarbonate, ionomer, or polyamide, and an insulating synthetic resin film such as a polyamide resin or polyester resin is further provided on the metal thin film as the outer surface of the exterior body. Such a multilayer structure film can be called a laminate film. In this case, the laminate film may be called an aluminum (aluminum) laminate film, a stainless steel laminate film, a titanium laminate film, a copper laminate film, a nickel laminate film, or the like, using the material name of the metal layer of the laminate film.
[0419] The material or thickness of the metal layer of the laminate film may affect the flexibility of the battery. For example, an aluminum laminate film having a polypropylene layer, an aluminum layer, and nylon is preferably used as an exterior body for a battery with excellent flexibility (bendability). Here, the thickness of the aluminum layer is preferably 50 μm or less, more preferably 40 μm or less, more preferably 30 μm or less, and more preferably 20 μm or less. If the aluminum layer is thinner than 10 μm, there is a concern that the gas barrier property may be reduced due to pinholes in the aluminum layer, so the thickness of the aluminum layer is desirably 10 μm or more.
[0420] Also, a graphene sheet may be used as the laminate film instead of the metal layer. As the graphene sheet, a multi-layer graphene sheet having a thickness of 100 nm to 30 μm, preferably 200 nm to 20 μm, may be used. The graphene sheet is flexible, has a graphene interlayer distance of 0.34 nm, and has gas barrier properties, making it suitable as a film to be used for the exterior of a secondary battery.
[0421] [Method of processing a film having concave and convex parts] Next, a method for processing a film that can be used for the exterior body will be described. As the film, the above-mentioned laminate film can be used.
[0422] For example, a laminate film can be used as the laminate film. For example, a laminate film having a heat seal layer on one or both sides of a metal film can be used as the laminate film. For the adhesive layer, a heat-sealable resin film containing polypropylene or polyethylene can be used. In this embodiment, an aluminum laminate film is used in which a nylon resin is provided on the surface of an aluminum foil, and an acid-resistant polypropylene film and a polypropylene film are laminated on the back surface of the aluminum foil.
[0423] The film is then embossed. As a result, a film having a concave-convex shape is produced. The film has a plurality of concave-convex portions, and thus has a visible wavy pattern.
[0424] The embossing process, which is a type of press working, will be described below.
[0425] Fig. 21 is a cross-sectional view showing an example of embossing. Embossing is a type of press processing, and refers to a process in which an embossing roll with an uneven surface is pressed against a film to form unevenness in the film that corresponds to the unevenness of the embossing roll. The embossing roll is a roll with a pattern engraved on its surface.
[0426] 21 shows an example of embossing on both sides of a film, and a method of forming a film with protrusions having peaks on one side.
[0427] 21 shows a film 90 being sandwiched between an embossing roll 95 in contact with one side of the film and an embossing roll 96 in contact with the other side, and being sent out in a film travel direction 91. A pattern is formed on the film surface by pressure or heat. Note that a pattern may be formed on the film surface by both pressure and heat.
[0428] As the embossing roll, a metal roll, a ceramic roll, a plastic roll, a rubber roll, an organic resin roll, a wood roll, or the like can be appropriately used.
[0429] In Fig. 21, embossing is performed using an embossing roll 96 which is a male pattern embossing roll and a female pattern embossing roll 95. The male pattern embossing roll 96 has multiple convex portions 96a. These convex portions correspond to the convex portions to be formed on the film to be processed. The female pattern embossing roll 95 has multiple convex portions 95a. The adjacent convex portions 95a form recesses that fit into the convex portions to be formed on the film by the convex portions 96a provided on the male pattern embossing roll 96.
[0430] By successively performing embossing to raise a part of the film 90 and blank pressing to depress a part of the film 90, it is possible to continuously form convex portions and flat portions. As a result, a pattern can be formed on the film 90.
[0431] Next, a film having a plurality of convex portions with shapes different from those in Fig. 21 will be described with reference to Fig. 22(A) to Fig. 22(E). By changing the convex shapes of the embossing roll 95 and the embossing roll 96 in Fig. 21 to shapes different from those in Fig. 21, embossing with various cross-sectional shapes as shown in Fig. 22(A) to Fig. 22(E) can be performed.
[0432] Fig. 22(A) is a schematic cross-sectional view of an embossment having a wavy shape, and Fig. 22(B) to Fig. 22(E) are modified examples of Fig. 22(A). Fig. 22(B) and Fig. 22(C) are diagrams showing an example in which the wavy shape is formed in a staircase shape, Fig. 22(D) is a diagram showing an example in which the wavy shape is formed in a rectangular shape, and Fig. 22(E) is a diagram showing an example in which the wavy shape is formed with acute-angled valley shapes and trapezoidal peak shapes.
[0433] Figures 23(A) and 23(B) are bird's-eye views showing the finished shape when the embossing shown in Figures 21 to 22(E) is performed twice by changing the direction of the film 90. Specifically, the film 90 is embossed in a first direction, and then embossed in a second direction rotated 90 degrees from the first direction, to obtain a film 81 (81a, 81b, 81c) having an embossed shape (which can be called a cross-wave shape) shown in Figures 23(A) and 23(B). The film 81a having the cross-wave shape shown in Figure 23(A) shows the outer shape used when a secondary battery is produced from a single film 81a, and can be folded in half at the dashed line for use. In addition, the multiple films (films 81b, 81c) having a cross-wave shape shown in Figure 23(B) indicate the outline used when making a secondary battery using two films (films 81b, 81c), and films 81b and 81c can be used by stacking them.
[0434] As described above, by performing processing using an embossing roll, it is possible to reduce the size of the device. In addition, since processing can be performed without cutting the film, it is excellent in mass productivity. Note that processing is not limited to using an embossing roll, and for example, the film may be processed by pressing a pair of embossing plates having uneven surfaces against the film. In this case, one of the embossing plates may be flat, and processing may be performed in multiple steps.
[0435] 23(C) is a perspective view showing a curved state of battery 10 produced using a laminate film embossed with a unidirectional wave pattern for exterior body 50A. In this way, by using a laminate film embossed with a unidirectional wave pattern for the exterior body, a battery that is easily bent in one direction can be obtained.
[0436] In the above-described configuration example of the secondary battery, the exterior body on one side of the secondary battery and the exterior body on the other side have the same embossed shape, but the configuration of the secondary battery of one embodiment of the present invention is not limited thereto. For example, as shown in FIG. 24(A) to FIG. 24(C), the secondary battery may have an embossed shape on the exterior body on one side of the secondary battery and an embossed shape on the exterior body on the other side. The exterior body on one side of the secondary battery and the exterior body on the other side of the secondary battery may have different embossed shapes. For example, as the exterior body of the secondary battery, a single film having an area with an embossed shape and an area without an embossed shape may be used, as in the case of film 81d in FIG. 24(A). Alternatively, as shown in FIG. 24(B), a film 81e having an embossed shape and a film 81f having no embossed shape may be used as the exterior body. FIG. 24(C) is a diagram showing an example configuration of battery 10B in which the exterior body of one side of the battery in the diagram shown in FIG. 23(C) has an embossed shape, and the exterior body of the other side does not have an embossed shape.
[0437] The contents of this embodiment mode can be freely combined with the contents of other embodiment modes.
[0438] (Embodiment 3) In this embodiment, an example of a secondary battery that can have the positive electrode active material according to one embodiment of the present invention and has a different shape from the above will be described.
[0439] [Coin-type secondary battery] An example of a coin-type secondary battery will be described. Fig. 25(A) is an exploded perspective view of a coin-type (single-layer flat) secondary battery, Fig. 25(B) is an external view, and Fig. 25(C) is a cross-sectional view thereof. Coin-type secondary batteries are mainly used in small electronic devices.
[0440] In addition, in order to make it easier to understand, Fig. 25(A) is a schematic diagram showing the overlapping of components (upper and lower relationships and positional relationships). Therefore, Fig. 25(A) and Fig. 25(B) are not completely corresponding views.
[0441] In Fig. 25(A), a positive electrode 304, a separator 310, a negative electrode 307, a spacer 322, and a washer 312 are stacked. These are sealed with a negative electrode can 302, a positive electrode can 301, and a gasket. Note that the gasket for sealing is not shown in Fig. 25(A). The spacer 322 and the washer 312 are used to protect the inside or to fix the position inside the can when the positive electrode can 301 and the negative electrode can 302 are crimped together. The spacer 322 and the washer 312 are made of stainless steel or an insulating material.
[0442] A laminated structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is used as a positive electrode 304 .
[0443] FIG. 25(B) is a perspective view of the completed coin-type secondary battery.
[0444] In the coin-type secondary battery 300, a positive electrode can 301 also serving as a positive electrode terminal and a negative electrode can 302 also serving as a negative electrode terminal are insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector. The negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector. The negative electrode 307 is not limited to a laminated structure, and may be a lithium metal foil or a lithium-aluminum alloy foil.
[0445] In addition, the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 each need only have an active material layer formed on one side.
[0446] Metals such as nickel, aluminum, and titanium that are corrosion-resistant to the electrolyte, or alloys of these metals or alloys of these metals with other metals (e.g., stainless steel, etc.) can be used for the positive electrode can 301 and the negative electrode can 302. In order to prevent corrosion by the electrolyte, etc., it is preferable to coat them with nickel, aluminum, etc. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.
[0447] These negative electrode 307, positive electrode 304, and separator 310 are immersed in an electrolyte, and as shown in FIG. 25(C), positive electrode can 301 is placed down, and positive electrode 304, separator 310, negative electrode 307, and negative electrode can 302 are stacked in this order, and positive electrode can 301 and negative electrode can 302 are crimped together via gasket 303, to produce coin-type secondary battery 300.
[0448] By applying the configurations described in the above embodiment to the negative electrode, positive electrode, electrolyte, and the like, a coin-type secondary battery having an excellent discharge capacity even in a low-temperature environment can be obtained.
[0449] [Cylindrical secondary battery] An example of a cylindrical secondary battery will be described with reference to Fig. 26(A). As shown in Fig. 26(A), a cylindrical secondary battery 616 has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap 601 and the battery can (external can) 602 are insulated by a gasket (insulating packing) 610.
[0450] Fig. 26(B) is a schematic diagram showing a cross section of a cylindrical secondary battery. The cylindrical secondary battery shown in Fig. 26(B) has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (external can) 602 on the side and bottom surfaces. The positive electrode cap and the battery can (external can) 602 are insulated by a gasket (insulating packing) 610.
[0451] Inside a hollow cylindrical battery can 602, a battery element is provided in which a strip-shaped positive electrode 604 and a negative electrode 606 are wound with a separator 605 sandwiched therebetween. Although not shown, the battery element is wound around a central axis. One end of the battery can 602 is closed and the other end is open. For the battery can 602, metals such as nickel, aluminum, and titanium that are resistant to corrosion by the electrolyte, or alloys of these metals and other metals (e.g., stainless steel, etc.) can be used. In addition, in order to prevent corrosion by the electrolyte, it is preferable to coat the battery can 602 with nickel, aluminum, or the like. Inside the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched between a pair of insulating plates 608 and 609 facing each other. In addition, an electrolyte (not shown) is injected into the inside of the battery can 602 in which the battery element is provided. The electrolyte can be the same as that of a coin-type secondary battery.
[0452] Since the positive and negative electrodes used in a cylindrical storage battery are wound, it is preferable to form active materials on both sides of the current collector.
[0453] By applying the configurations described in the above embodiments to the negative electrode, positive electrode, electrolyte, and the like, a cylindrical secondary battery having an excellent discharge capacity even in a low-temperature environment can be obtained.
[0454] A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode terminal (negative electrode current collector lead) 607 is connected to the negative electrode 606. The positive electrode terminal 603 can be made of a metal material such as aluminum. The negative electrode terminal 607 can be made of a metal material such as copper. The positive electrode terminal 603 is resistance-welded to a safety valve mechanism 613, and the negative electrode terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cap 601 via a PTC (Positive Temperature Coefficient) element 611. The safety valve mechanism 613 cuts off the electrical connection between the positive electrode cap 601 and the positive electrode 604 when the increase in the internal pressure of the battery exceeds a predetermined threshold value. The PTC element 611 is a thermosensitive resistor whose resistance increases when the temperature increases, and limits the amount of current by increasing the resistance to prevent abnormal heat generation. For the PTC element, barium titanate (BaTiO3) based semiconductor ceramics or the like can be used.
[0455] 26C shows an example of a power storage system 615. The power storage system 615 has a plurality of secondary batteries 616. A positive electrode of each secondary battery is in contact with and electrically connected to a conductor 624 separated by an insulator 625. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. A negative electrode of each secondary battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a charge / discharge control circuit that performs charging / discharging, or the like, or a protection circuit that prevents overcharging and / or overdischarging can be used.
[0456] 26(D) shows an example of a power storage system 615. The power storage system 615 has a plurality of secondary batteries 616, and the plurality of secondary batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of secondary batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 by wiring 627. The plurality of secondary batteries 616 may be connected in parallel, may be connected in series, or may be connected in parallel and then further connected in series. By configuring the power storage system 615 having the plurality of secondary batteries 616, it is possible to extract a large amount of power.
[0457] A plurality of secondary batteries 616 may be connected in parallel and then further connected in series.
[0458] Also, a temperature control device may be provided between the multiple secondary batteries 616. When the secondary batteries 616 are overheated, they can be cooled by the temperature control device, and when the secondary batteries 616 are too cold, they can be heated by the temperature control device. Therefore, the performance of the power storage system 615 is less susceptible to the influence of the outside air temperature.
[0459] 26(D), the power storage system 615 is electrically connected to a control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the multiple secondary batteries 616 via a conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the multiple secondary batteries 616 via a conductive plate 614.
[0460] [Other examples of secondary battery structures] An example of the structure of the secondary battery will be described with reference to FIGS.
[0461] A secondary battery 913 shown in FIG. 27(A) has a wound body 950 in which terminals 951 and 952 are provided inside a housing 930. The wound body 950 is immersed in an electrolyte inside the housing 930. The terminal 952 contacts the housing 930, and the terminal 951 does not contact the housing 930 by using an insulating material or the like. Note that in FIG. 27(A), the housing 930 is shown separated for convenience, but in reality, the wound body 950 is covered by the housing 930, and the terminals 951 and 952 extend outside the housing 930. The housing 930 can be made of a metal material (e.g., aluminum) or a resin material.
[0462] As shown in Fig. 27(B), the housing 930 shown in Fig. 27(A) may be formed using a plurality of materials. For example, a secondary battery 913 shown in Fig. 27(B) has a housing 930a and a housing 930b bonded together, and a wound body 950 is provided in a region surrounded by the housing 930a and the housing 930b.
[0463] Considering gas permeability, the housing 930a and the housing 930b can each be made of a metal material (such as aluminum) or an organic resin in addition to a metal material.
[0464] 27(C) shows the structure of the wound body 950. The wound body 950 has a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is a wound body in which the negative electrode 931 and the positive electrode 932 are stacked with the separator 933 sandwiched therebetween, and the laminated sheet is wound. Note that the stack of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked a plurality of times.
[0465] Alternatively, a secondary battery 913 may have a wound body 950a as shown in Fig. 28. A wound body 950a shown in Fig. 28(A) has a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 has a negative electrode active material layer 931a. The positive electrode 932 has a positive electrode active material layer 932a.
[0466] By applying the configurations described in the above embodiments to the negative electrode, positive electrode, electrolyte, and the like, a secondary battery having an excellent discharge capacity even in a low-temperature environment can be obtained.
[0467] The separator 933 has a width wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. From the viewpoint of safety, it is preferable that the width of the negative electrode active material layer 931a is wider than that of the positive electrode active material layer 932a. Moreover, a wound body 950a having such a shape is preferable because of its high safety and productivity.
[0468] 28(B), the negative electrode 931 is electrically connected to a terminal 951 by ultrasonic bonding, welding, or crimping. The terminal 951 is electrically connected to a terminal 911a. The positive electrode 932 is electrically connected to a terminal 952 by ultrasonic bonding, welding, or crimping. The terminal 952 is electrically connected to a terminal 911b.
[0469] 28(C), the wound body 950a and the electrolyte are covered with the housing 930 to form a secondary battery 913. It is preferable to provide a safety valve, an overcurrent protection element, and the like in the housing 930. The safety valve is a valve that opens when the inside of the housing 930 reaches a predetermined internal pressure in order to prevent the battery from exploding.
[0470] As shown in Fig. 28(B), the secondary battery 913 may have a plurality of wound bodies 950a. By using a plurality of wound bodies 950a, the secondary battery 913 can have a larger discharge capacity. For other elements of the secondary battery 913 shown in Figs. 28(A) and (B), the description of the secondary battery 913 shown in Figs. 27(A) to (C) can be referred to.
[0471] <Laminated secondary battery> Next, an example of an external view of a laminated secondary battery is shown in Figures 29(A) and 29(B). Figures 29(A) and 29(B) have a positive electrode 503, a negative electrode 506, a separator 507, an exterior body 509, a positive electrode lead electrode 510, and a negative electrode lead electrode 511.
[0472] FIG. 30(A) shows an external view of a positive electrode 503 and a negative electrode 506. The positive electrode 503 has a positive electrode current collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. The positive electrode 503 has a region where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab region). The negative electrode 506 has a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. The negative electrode 506 has a region where the negative electrode current collector 504 is partially exposed, that is, a tab region. Note that the area or shape of the tab regions of the positive electrode and the negative electrode are not limited to the example shown in FIG. 30(A).
[0473] By applying the configurations described in the above embodiments to the negative electrode, positive electrode, electrolyte, and the like, a laminate type secondary battery having an excellent discharge capacity even in a low temperature environment can be obtained.
[0474] <Method of manufacturing laminated secondary battery> An example of a method for manufacturing the laminate type secondary battery whose external view is shown in FIG. 29(A) will be described with reference to FIGS. 30(B) and 30(C).
[0475] First, the negative electrode 506, the separator 507, and the positive electrode 503 are laminated. FIG. 30(B) shows the laminated negative electrode 506, the separator 507, and the positive electrode 503. Here, an example is shown in which five pairs of negative electrodes and four pairs of positive electrodes are used. This can also be called a laminate consisting of a negative electrode, a separator, and a positive electrode. Next, the tab regions of the positive electrodes 503 are bonded to each other, and the positive electrode lead electrode 510 is bonded to the tab region of the outermost positive electrode. For example, ultrasonic welding or the like may be used for the bonding. Similarly, the tab regions of the negative electrodes 506 are bonded to each other, and the negative electrode lead electrode 511 is bonded to the tab region of the outermost negative electrode.
[0476] Next, the negative electrode 506 , the separator 507 , and the positive electrode 503 are placed on the exterior body 509 .
[0477] Next, as shown in Fig. 30(C), exterior body 509 is folded at the portion indicated by the dashed line. After that, the outer periphery of exterior body 509 is joined. For the joining, for example, thermocompression bonding or the like may be used. At this time, a region (hereinafter referred to as an inlet) that is not joined is provided in a part (or one side) of exterior body 509 so that an electrolyte can be introduced later.
[0478] Next, the electrolyte is introduced into the inside of the exterior body 509 through an inlet provided in the exterior body 509. The electrolyte is preferably introduced under a reduced pressure atmosphere or an inert atmosphere. Finally, the inlet is joined. In this manner, the laminated secondary battery 500 can be produced.
[0479] The contents of this embodiment mode can be freely combined with the contents of other embodiment modes.
[0480] (Embodiment 4) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted on an electronic device will be described with reference to FIGS.
[0481] 31A to 31G show examples of electronic devices to which the secondary battery having the positive electrode active material described in the above embodiment is mounted. Examples of electronic devices to which the secondary battery is applied include television devices (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game machines, personal digital assistants, audio playback devices, and large game machines such as pachinko machines.
[0482] Furthermore, a secondary battery having a flexible shape can be incorporated along the curved surfaces of the inner or outer walls of a house or building, or the interior or exterior of an automobile.
[0483] 31A shows an example of a mobile phone. The mobile phone 7400 includes a display portion 7402 built into a housing 7401, operation buttons 7403, an external connection port 7404, a speaker 7405, a microphone 7406, and the like. Note that the mobile phone 7400 includes a secondary battery 7407. By using the secondary battery of one embodiment of the present invention as the secondary battery 7407, a lightweight mobile phone with a long life can be provided.
[0484] FIG. 31(B) shows the mobile phone 7400 in a bent state. When the mobile phone 7400 is deformed by an external force and bent as a whole, the secondary battery 7407 provided inside is also bent. FIG. 31(C) shows the bent state of the secondary battery 7407 at that time. The secondary battery 7407 is a thin storage battery. The secondary battery 7407 is fixed in a bent state. The secondary battery 7407 has a lead electrode electrically connected to a current collector.
[0485] FIG. 31D shows an example of a bangle-type display device. The portable display device 7100 includes a housing 7101, a display unit 7102, an operation button 7103, and a secondary battery 7104. FIG. 31E shows a bent state of the secondary battery 7104. When the secondary battery 7104 is worn on a user's arm in a bent state, the housing is deformed, and the curvature of the secondary battery 7104 changes in part or in whole. Note that the degree of bending at any point of the curve expressed by the value of the radius of the corresponding circle is called the radius of curvature, and the reciprocal of the radius of curvature is called the curvature. Specifically, the housing or the main surface of the secondary battery 7104 changes in part or in whole when the radius of curvature is in the range of 40 mm to 150 mm. High reliability can be maintained if the radius of curvature of the main surface of the secondary battery 7104 is in the range of 40 mm to 150 mm. By using the secondary battery of one embodiment of the present invention as the secondary battery 7104, a lightweight portable display device with a long life can be provided.
[0486] 31F shows an example of a wristwatch-type portable information terminal. A portable information terminal 7200 includes a housing 7201, a display portion 7202, a band 7203, a buckle 7204, operation buttons 7205, an input / output terminal 7206, and the like.
[0487] The portable information terminal 7200 can execute various applications such as mobile telephone, e-mail, document browsing and creation, music playback, Internet communication, and computer games.
[0488] The display surface of the display portion 7202 is curved, and display can be performed along the curved display surface. The display portion 7202 is also provided with a touch sensor, and can be operated by touching the screen with a finger, a stylus, or the like. For example, an application can be started by touching an icon 7207 displayed on the display portion 7202.
[0489] The operation button 7205 can have various functions, such as time setting, power on / off operation, wireless communication on / off operation, silent mode activation / cancellation, power saving mode activation / cancellation, etc. For example, the function of the operation button 7205 can be freely set by an operating system built into the mobile information terminal 7200.
[0490] The portable information terminal 7200 is also capable of short-distance wireless communication. For example, the portable information terminal 7200 can communicate with a wireless headset to enable hands-free conversation.
[0491] The portable information terminal 7200 also includes an input / output terminal 7206, and can directly exchange data with another information terminal via a connector. Charging can also be performed via the input / output terminal 7206. Note that charging may be performed wirelessly without using the input / output terminal 7206.
[0492] A display portion 7202 of a portable information terminal 7200 includes the secondary battery of one embodiment of the present invention. By using the secondary battery of one embodiment of the present invention, a portable information terminal that is lightweight and has a long life can be provided. For example, the secondary battery 7104 shown in FIG. 31E can be incorporated in a curved state inside a housing 7201 or in a bendable state inside a band 7203.
[0493] The portable information terminal 7200 preferably has a sensor. For example, it is preferable that a fingerprint sensor, a pulse sensor, a human body sensor such as a body temperature sensor, a touch sensor, a pressure sensor, an acceleration sensor, or the like is mounted as the sensor.
[0494] 31G illustrates an example of an armband-type display device. The display device 7300 includes a display portion 7304 and a secondary battery of one embodiment of the present invention. The display device 7300 can also include a touch sensor in the display portion 7304 and can function as a portable information terminal.
[0495] The display surface of the display portion 7304 is curved, and display can be performed along the curved display surface. In addition, the display state of the display device 7300 can be changed by short-range wireless communication or the like.
[0496] The display device 7300 also includes an input / output terminal, and can directly exchange data with other information terminals via a connector. Charging can also be performed via the input / output terminal. Note that charging may be performed wirelessly without using the input / output terminal.
[0497] By using the secondary battery of one embodiment of the present invention as a secondary battery included in the display device 7300, a lightweight display device with a long lifetime can be provided.
[0498] Further, an example in which the secondary battery having good cycle characteristics described in the above embodiment is mounted on an electronic device will be described with reference to FIGS.
[0499] By using the secondary battery of one embodiment of the present invention as a secondary battery in daily electronic devices, products that are lightweight and have a long life can be provided. For example, daily electronic devices include electric toothbrushes, electric shavers, and electric beauty devices. For the secondary battery of these products, a stick-shaped secondary battery that is small, lightweight, and has a large discharge capacity is desired in consideration of ease of holding by users.
[0500] FIG. 31(H) is a perspective view of a device also called a tobacco-receiving smoking device (electronic cigarette). In FIG. 31(H), the electronic cigarette 7500 is composed of an atomizer 7501 including a heating element, a secondary battery 7504 that supplies power to the atomizer, and a cartridge 7502 including a liquid supply bottle, a sensor, and the like. To enhance safety, a protection circuit that prevents overcharging and / or overdischarging of the secondary battery 7504 may be electrically connected to the secondary battery 7504. The secondary battery 7504 shown in FIG. 31(H) has an external terminal so that it can be connected to a charging device. Since the secondary battery 7504 is the tip part when held, it is desirable that the total length is short and the weight is light. Since the secondary battery of one embodiment of the present invention has a high discharge capacity and good cycle characteristics, a small and lightweight electronic cigarette 7500 that can be used for a long period of time can be provided.
[0501] Fig. 32(A) shows an example of a wearable device. The wearable device uses a secondary battery as a power source. In addition, when a user uses the device in daily life or outdoors, in order to improve splash-proof performance, water resistance, or dust resistance, there is a demand for a wearable device that can be charged wirelessly as well as by wire with an exposed connector.
[0502] For example, the secondary battery according to one embodiment of the present invention can be mounted on a glasses-type device 4000 as shown in FIG. 32A. The glasses-type device 4000 includes a frame 4000a and a display unit 4000b. By mounting a secondary battery on the temples of the curved frame 4000a, the glasses-type device 4000 can be lightweight, well-balanced in weight, and has a long continuous use time. By including the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a smaller housing can be realized.
[0503] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the headset type device 4001. The headset type device 4001 has at least a microphone unit 4001a, a flexible pipe 4001b, and an earphone unit 4001c. The secondary battery can be provided in the flexible pipe 4001b and / or the earphone unit 4001c. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with a miniaturized housing can be realized.
[0504] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4002 that can be directly attached to the body. A secondary battery 4002b can be provided in a thin housing 4002a of the device 4002. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.
[0505] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on a device 4003 that can be attached to clothing. A secondary battery 4003b can be provided in a thin housing 4003a of the device 4003. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.
[0506] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the belt type device 4006. The belt type device 4006 has a belt portion 4006a and a wireless power receiving portion 4006b, and a secondary battery can be mounted inside the belt portion 4006a. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving associated with miniaturization of the housing can be realized.
[0507] Furthermore, the secondary battery according to one embodiment of the present invention can be mounted on the wristwatch device 4005. The wristwatch device 4005 has a display portion 4005a and a belt portion 4005b, and the secondary battery can be provided on the display portion 4005a or the belt portion 4005b. By providing the secondary battery according to one embodiment of the present invention, a configuration that can accommodate space saving due to miniaturization of the housing can be realized.
[0508] The display unit 4005a can display not only the time but also various other information such as incoming e-mails and phone calls.
[0509] In addition, since the wristwatch type device 4005 is a wearable device that is directly wrapped around the arm, it may be equipped with sensors that measure the user's pulse, blood pressure, etc. Data on the user's amount of exercise and health can be accumulated to manage the user's health.
[0510] FIG. 32(B) shows a perspective view of the wristwatch type device 4005 removed from the wrist.
[0511] 32C shows a side view of the display portion 4005. FIG. 32C shows a state in which a secondary battery 913 is built in the display portion 4005. The secondary battery 913 is the secondary battery described in the above embodiment. The secondary battery 913 is provided at a position overlapping with the display portion 4005a, and is small and lightweight.
[0512] 32D shows an example of a wireless earphone. Here, the wireless earphone is illustrated having a pair of main bodies 4100a and 4100b, but the pair is not necessarily required.
[0513] The main bodies 4100a and 4100b each have a driver unit 4101, an antenna 4102, and a secondary battery 4103. They may also have a display unit 4104. They also preferably have a substrate on which a circuit such as a wireless IC is mounted, a charging terminal, and the like. They may also have a microphone.
[0514] The case 4110 has a secondary battery 4111. It is preferable that the case 4110 also has a board on which circuits such as a wireless IC and a charge control IC are mounted, and a charging terminal. It may also have a display unit, buttons, and the like.
[0515] The main bodies 4100a and 4100b can wirelessly communicate with other electronic devices such as smartphones. This allows the main bodies 4100a and 4100b to play back audio data sent from other electronic devices. If the main bodies 4100a and 4100b have a microphone, the audio captured by the microphone can be sent to the other electronic device, and the audio data processed by the electronic device can be sent back to the main bodies 4100a and 4100b for playback. This allows the main bodies 4100a and 4100b to be used as a translator, for example.
[0516] In addition, the secondary battery 4103 in the main body 4100a can be charged from the secondary battery 4111 in the case 4110. The coin-type secondary battery, the cylindrical secondary battery, or the like described in the above embodiments can be used as the secondary battery 4111 and the secondary battery 4103. A secondary battery using the positive electrode active material 100 obtained in Embodiment 1 as a positive electrode has high energy density. By using the secondary battery 4103 and the secondary battery 4111 as the positive electrode, a configuration that can accommodate space saving associated with miniaturization of wireless earphones can be realized.
[0517] 33A shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 arranged on the top surface of a housing 6301, a plurality of cameras 6303 arranged on the side surface, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, and the like. Although not shown, the cleaning robot 6300 is provided with tires, a suction port, and the like. The cleaning robot 6300 can move by itself, detect dust 6310, and suck up the dust from a suction port arranged on the bottom surface.
[0518] For example, the cleaning robot 6300 can analyze an image captured by the camera 6303 and determine the presence or absence of an obstacle such as a wall, furniture, or a step. When an object that may become entangled in the brush 6304, such as a wire, is detected by image analysis, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 includes a secondary battery 6306 according to one embodiment of the present invention and a semiconductor device or electronic component therein. By using the secondary battery 6306 according to one embodiment of the present invention in the cleaning robot 6300, the cleaning robot 6300 can be an electronic device with long operating time and high reliability.
[0519] Fig. 33(B) shows an example of a robot. The robot 6400 shown in Fig. 33(B) includes a secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.
[0520] The microphone 6402 has a function of detecting the user's voice, environmental sounds, etc. The speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user using the microphone 6402 and the speaker 6404.
[0521] The display unit 6405 has a function of displaying various information. The robot 6400 can display information desired by the user on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may be a removable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer are possible.
[0522] The upper camera 6403 and the lower camera 6406 have a function of capturing images of the surroundings of the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of an obstacle in the moving direction when the robot 6400 moves forward using the moving mechanism 6408. The robot 6400 can recognize the surrounding environment and move safely using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407.
[0523] The robot 6400 includes a secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or electronic component inside the robot 6400. By using the secondary battery according to one embodiment of the present invention in the robot 6400, the robot 6400 can be a highly reliable electronic device with a long operating time.
[0524] Fig. 33C shows an example of an aircraft. The aircraft 6500 shown in Fig. 33C includes a propeller 6501, a camera 6502, a secondary battery 6503, and the like, and has a function of flying autonomously.
[0525] For example, image data captured by the camera 6502 is stored in the electronic component 6504. The electronic component 6504 can analyze the image data and detect the presence or absence of an obstacle when moving. The electronic component 6504 can estimate the remaining battery charge from a change in the power storage capacity of the secondary battery 6503. The flying object 6500 includes therein the secondary battery 6503 according to one embodiment of the present invention. By using the secondary battery according to one embodiment of the present invention in the flying object 6500, the flying object 6500 can be an electronic device with a long operating time and high reliability.
[0526] This embodiment mode can be implemented in appropriate combination with other embodiment modes.
[0527] (Embodiment 5) In this embodiment, an example is described in which a secondary battery including the positive electrode active material of one embodiment of the present invention is mounted on a vehicle.
[0528] By installing secondary batteries in vehicles, next-generation clean energy vehicles such as hybrid vehicles (HVs), electric vehicles (EVs), and plug-in hybrid vehicles (PHVs) can be realized.
[0529] FIG. 34 illustrates an example of a vehicle using a secondary battery according to one embodiment of the present invention. An automobile 8400 illustrated in FIG. 34(A) is an electric automobile using an electric motor as a power source for running. Alternatively, it is a hybrid automobile in which an electric motor and an engine can be appropriately selected and used as a power source for running. By using one embodiment of the present invention, a vehicle with a long cruising distance can be realized. In addition, the automobile 8400 has a secondary battery. For example, secondary battery modules can be arranged on the floor of the vehicle. The secondary battery can not only drive the electric motor 8406 but also supply power to light-emitting devices such as a headlight 8401 and a room light (not shown).
[0530] The secondary battery can also supply power to display devices such as a speedometer and a tachometer included in the automobile 8400. The secondary battery can also supply power to semiconductor devices such as a navigation system included in the automobile 8400.
[0531] The automobile 8500 shown in FIG. 34(B) can charge the secondary battery of the automobile 8500 by receiving power supply from an external charging facility by a plug-in method and / or a non-contact power supply method. FIG. 34(B) shows a state in which a secondary battery 8024 mounted on the automobile 8500 is being charged from a ground-mounted charging device 8021 via a cable 8022. When charging, the charging method and connector standards may be appropriately performed by a predetermined method such as CHAdeMO (registered trademark) or Combo. The charging device 8021 may be a charging station installed in a commercial facility or a home power source. For example, the secondary battery 8024 mounted on the automobile 8500 can be charged by an external power supply using plug-in technology. Charging can be performed by converting AC power to DC power via a conversion device such as an ACDC converter.
[0532] Although not shown, a power receiving device may be mounted on a vehicle, and charging may be performed by supplying power contactlessly from a ground power transmitting device. In the case of this contactless power supply method, by incorporating a power transmitting device in the road and / or an exterior wall, charging may be performed not only while the vehicle is stopped but also while it is moving. This contactless power supply method may also be used to transmit and receive power between vehicles. Furthermore, a solar cell may be provided on the exterior of the vehicle, and a secondary battery may be charged while the vehicle is stopped and / or moving. For such contactless power supply, an electromagnetic induction method and / or a magnetic field resonance method may be used.
[0533] 34C is an example of a two-wheeled vehicle using the secondary battery of one embodiment of the present invention. A scooter 8600 shown in FIG. 34C includes a secondary battery 8602, a side mirror 8601, and a turn signal light 8603. The secondary battery 8602 can supply electricity to the turn signal light 8603.
[0534] 34(C) is capable of storing a secondary battery 8602 in the under-seat storage 8604. Even if the under-seat storage 8604 is small, the secondary battery 8602 can be stored in the under-seat storage 8604. The secondary battery 8602 is removable, and when charging, the secondary battery 8602 can be carried indoors, charged, and stored before riding.
[0535] According to one aspect of the present invention, the cycle characteristics of the secondary battery are improved, and the discharge capacity of the secondary battery can be increased. Therefore, the secondary battery itself can be made small and lightweight. If the secondary battery itself can be made small and lightweight, it contributes to reducing the weight of the vehicle, and the cruising distance can be improved. In addition, the secondary battery mounted on the vehicle can be used as a power supply source other than the vehicle. In this case, for example, it is possible to avoid using a commercial power source during peak power demand. If it is possible to avoid using a commercial power source during peak power demand, it is possible to contribute to energy conservation and reduction of carbon dioxide emissions. In addition, if the cycle characteristics are good, the secondary battery can be used for a long period of time, and the amount of rare metals used, including cobalt, can be reduced.
[0536] This embodiment mode can be implemented in appropriate combination with other embodiment modes.
[0537] (Embodiment 6) In this embodiment, an example in which a secondary battery which is one embodiment of the present invention is mounted in space equipment will be described.
[0538] 35(A) shows an artificial satellite 6800 as an example of space equipment. The artificial satellite 6800 has a body 6801, a solar panel 6802, an antenna 6803, and a secondary battery 6805. The solar panel may be called a solar cell module.
[0539] When the solar panel 6802 is irradiated with sunlight, the power required for the operation of the artificial satellite 6800 is generated. However, for example, in a situation where the solar panel is not irradiated with sunlight or the amount of sunlight irradiated to the solar panel is small, the generated power is small. Therefore, the power required for the operation of the artificial satellite 6800 may not be generated. In order to operate the artificial satellite 6800 even under a situation where the generated power is small, it is preferable to provide a secondary battery 6805 in the artificial satellite 6800. By using the positive electrode active material of the present invention for the secondary battery, it is possible to obtain a secondary battery having a high discharge capacity and excellent cycle characteristics.
[0540] The artificial satellite 6800 can generate a signal. The signal is transmitted via an antenna 6803, and can be received, for example, by a receiver installed on the ground or by another artificial satellite. By receiving the signal transmitted by the artificial satellite 6800, for example, the position of the receiver that received the signal can be measured. As described above, the artificial satellite 6800 can constitute, for example, a satellite positioning system.
[0541] Alternatively, the artificial satellite 6800 can be configured to have a sensor. For example, by configuring the artificial satellite 6800 to have a visible light sensor, the artificial satellite 6800 can have a function of detecting sunlight reflected by an object on the ground. Alternatively, by configuring the artificial satellite 6800 to have a thermal infrared sensor, the artificial satellite 6800 can have a function of detecting thermal infrared rays emitted from the earth's surface. As described above, the artificial satellite 6800 can have a function as, for example, an earth observation satellite.
[0542] FIG. 35(B) shows a probe 6900 having a solar sail (also called a sun sail) as an example of space equipment. The probe 6900 has a body 6901, a solar sail 6902, and a secondary battery 6905. By using the positive electrode active material of the present invention for the secondary battery, it is possible to obtain a secondary battery having a high discharge capacity and excellent cycle characteristics. When a photon emitted from the sun hits the surface of the solar sail 6902, momentum is transferred to the solar sail 6902. Therefore, the surface of the solar sail 6902 preferably has a thin film with high reflectivity, and further preferably faces the sun.
[0543] The solar sail 6902 may also be designed to be folded up small until it leaves the atmosphere, and then deployed into a large sheet outside the Earth's atmosphere (in outer space) as shown in Figure 35(B).
[0544] FIG. 35(C) shows a spacecraft 6910 as an example of space equipment. The spacecraft 6910 has a body 6911, a solar panel 6912, and a secondary battery 6913. By using the positive electrode active material of the present invention for the secondary battery, it is possible to obtain a secondary battery with high discharge capacity and excellent cycle characteristics. The body 6911 can have, for example, a pressurized compartment and a non-pressurized compartment. The pressurized compartment may be designed to accommodate a crew member. Electric power generated by irradiating the solar panel 6912 with sunlight can be charged into the secondary battery 6913.
[0545] 35(D) shows a rover 6920 as an example of space equipment. The rover 6920 includes a body 6921 and a secondary battery 6923. By using the positive electrode active material of the present invention for the secondary battery, the secondary battery can have a high discharge capacity and excellent cycle characteristics. The rover 6920 may include a solar panel 6922.
[0546] The exploration vehicle 6920 may be designed to accommodate a crew member. The secondary battery 6923 may be charged with electricity generated by irradiating the solar panel 6912 with sunlight, or may be charged with electricity generated by other power sources, such as a fuel cell, a radioisotope thermoelectric converter, or the like.
[0547] The content of this embodiment mode can be appropriately combined with the content of other embodiment modes. EXAMPLES
[0548] In this example, a test battery (half cell) including a positive electrode active material according to one embodiment of the present invention was fabricated and a charge-discharge cycle test was performed. A fabrication process of the sample will be described, and the results of cycle characteristics will be shown.
[0549] <Preparation of positive electrode active material> The positive electrode active material used in this example will be described with reference to the preparation method shown in FIG. 5 and FIG.
[0550] As the lithium cobalt oxide (LiCoO2) in step S10 of FIG. 5, commercially available lithium cobalt oxide (Cellseed C-5H, manufactured by Nippon Chemical Industry Co., Ltd.) having cobalt as the transition metal M and no particular additive element was prepared and sieved with an automatic sieving machine. For example, the treatment with the automatic sieving machine can be performed using an electromagnetic vibration sieving machine MS-200 manufactured by Ito Seisakusho Co., Ltd. under the conditions of a sieve opening of 53 μm and tapping balls. As the initial heating in step S15, this lithium cobalt oxide was placed in a setter, covered, and heated at 850° C. for 2 hours using a roller hearth kiln simulator furnace (manufactured by Noritake Company Ltd.). Air (compressed air, sufficiently dried) was flowed in the furnace at 10 L / min. The flow amount, specifically the opening width of the exhaust port, was adjusted so that the differential pressure gauge of the furnace was 5 Pa, and the furnace was made positive pressure. After the initial heating, the inside of the furnace was cooled at a rate of 200°C / hour, and the air flow was not stopped until the temperature reached 200°C.
[0551] In this embodiment, first, Mg and F were added separately as additive elements according to step S20a shown in FIG. 6(A). According to step S21 shown in FIG. 6(A), LiF was prepared as the F source, and MgF2 was prepared as the Mg source. LiF:MgF2 was weighed out so that it was 1:3 (molar ratio), and mixed in dehydrated acetone at a rotation speed of 500 rpm for 20 hours. The mixture was sieved through a sieve with 300 μm openings to produce an additive element source (A1 source) with a uniform particle size.
[0552] Next, in step S31 shown in Fig. 5, magnesium of the A1 source was weighed out so as to be 1 mol% of cobalt of lithium cobalt oxide, and the A1 source and the lithium cobalt oxide after the initial heating were stirred at a rotation speed of 3000 rpm for 10 minutes using Picobond (manufactured by Hosokawa Micron) to obtain a mixture 903 (step S32). Nobilta was used as the rotor of the Picobond. Before the next step S33, the mixture 903 was sieved with an automatic sieving machine.
[0553] Next, in step S33, the mixture 903 was heated. The heating conditions were 850° C. and 10 hours. During heating, the mixture 903 was placed in a setter and the setter was closed. Here, five conditions for the amount of the mixture 903 to be placed in the setter were prepared. Specifically, setters containing 30 g, 60 g, 120 g, 180 g, and 240 g of the mixture 903 were prepared. The condition in which 30 g of the mixture 903 was placed is called condition A, the condition in which 60 g of the mixture 903 was placed is called condition B, the condition in which 120 g of the mixture 903 was placed is called condition C, the condition in which 180 g of the mixture 903 was placed is called condition D, and the condition in which 240 g of the mixture 903 was placed is called condition E. The height H of the mixture 903 in the setter under each condition was 0.5 mm or more and 1.0 mm or less under condition A, 1.5 mm or more and 2.0 mm or less under condition B, 3.5 mm or more and 4.0 mm or less under condition C, 5.5 mm or more and 6.0 mm or less under condition D, and 7.5 mm or more and 8.0 mm or less under condition E. The above values are shown in Table 2.
[0554] [Table 2]
[0555] The setter was placed in a roller hearth kiln simulator furnace (manufactured by Noritake Company Ltd.) and heated to the above heating temperature. Oxygen was flowed into the furnace at 10 L / min (O2 flow). The flow rate, specifically the opening width of the exhaust port, was adjusted so that the furnace differential pressure gauge was 5 Pa, and the furnace was placed under positive pressure. After the initial heating, the furnace was cooled at a rate of 200°C / hour, and the oxygen flow was not stopped until the temperature reached 200°C. In this way, a composite oxide containing Mg and F was obtained (step S34a).
[0556] Next, in step S40, a composite oxide and an additive element source (A2 source) were prepared. First, according to step S41 shown in FIG. 6(C), nickel hydroxide that had undergone a pulverization process was prepared as the nickel source, and aluminum hydroxide that had undergone a pulverization process was prepared as the aluminum source, and these were used as the additive element source (A2 source). In the pulverization process, nickel hydroxide and aluminum hydroxide were each stirred in dehydrated acetone at a rotation speed of 500 rpm for 20 hours. Then, they were sieved through a sieve with an opening of 300 μm.
[0557] As the A2 source, nickel hydroxide was weighed so that the nickel was 0.5 mol % of cobalt, and aluminum hydroxide was 0.5 mol % of cobalt. The composite oxide containing Mg and F was stirred for 10 minutes at a rotation speed of 3000 rpm using a Picobond (manufactured by Hosokawa Micron) to obtain a mixture 904 (step S52). Nobilta was used as the rotor of the Picobond. Before the next step S53, the mixture 904 was sieved with an automatic sieving machine. After the conditions were divided in the above step S33, each was independently processed up to step S52. Therefore, the material processed under condition A in step S33 and processed up to step S52 is called mixture 904A, and similarly, the material processed under condition B is called mixture 904B, the material processed under condition C is called mixture 904C, the material processed under condition D is called mixture 904D, and the material processed under condition E is called mixture 904E.
[0558] Next, in step S53, the mixture 904 was heated. The heating conditions were 850°C and 2 hours. During heating, the mixture 904 was placed in a setter and covered. As in the case of dividing the conditions in step S33 above, 30 g of the mixture 904A was placed in a setter, 60 g of the mixture 904B was placed in another setter, 120 g of the mixture 904C was placed in another setter, 120 g of the mixture 904D was placed in another setter, and 240 g of the mixture 904E was placed in another setter. The condition in which 30 g of the mixture 904A was placed is called condition AA, the condition in which 60 g of the mixture 904B was placed is called condition BB, the condition in which 120 g of the mixture 904C was placed is called condition CC, the condition in which 180 g of the mixture 904D was placed is called condition DD, and the condition in which 240 g of the mixture 904E was placed is called condition EE. The height H of the mixture 904 in the setter under each condition was 0.5 mm or more and 1.0 mm or less in condition AA, 1.5 mm or more and 2.0 mm or less in condition BB, 3.5 mm or more and 4.0 mm or less in condition CC, 5.5 mm or more and 6.0 mm or less in condition DD, and 7.5 mm or more and 8.0 mm or less in condition EE. The above values are shown in Table 3.
[0559] [Table 3]
[0560] The setter was placed in a roller hearth kiln simulator furnace (manufactured by Noritake Company Ltd.) and heated to the above heating temperature. Oxygen was flowed into the furnace at 10 L / min (O2 flow). The flow rate, specifically the opening width of the exhaust port, was adjusted so that the furnace differential pressure gauge was 5 Pa, and the furnace was kept under positive pressure. After heating, the furnace was cooled at a rate of 200°C / hour, and the oxygen flow was not stopped until the temperature reached 200°C.
[0561] In this way, lithium cobalt oxide containing Mg, F, Ni, and Al was obtained (step S54). After the conditions were divided in step S53, each was processed independently up to step S54. Thus, the material processed under condition AA in step S53 and then processed up to step S54 is called positive electrode active material A, and similarly, the material processed under condition BB is called positive electrode active material B, similarly, the material processed under condition CC is called positive electrode active material C, similarly, the material processed under condition DD is called positive electrode active material D, and similarly, the material processed under condition EE is called positive electrode active material E.
[0562] <Preparation of positive electrode> The above-mentioned positive electrode active materials A to E were prepared as positive electrode active materials, acetylene black (AB) was prepared as a conductive material, and polyvinylidene fluoride (PVDF) was prepared as a binder. PVDF was prepared by dissolving it in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Next, the positive electrode active material:AB:PVDF was mixed at a weight ratio of 95:3:2 to prepare a slurry, which was then applied to an aluminum positive electrode current collector. NMP was used as the solvent for the slurry. After the slurry was applied to the positive electrode current collector, the solvent was evaporated.
[0563] Thereafter, in order to increase the density of the positive electrode active material layer on the positive electrode current collector, a pressing process was performed using a roll press machine. The pressing process was performed under a linear pressure of 210 kN / m. The upper and lower rolls of the roll press machine were both set at 120°C.
[0564] By the above steps, a positive electrode having each positive electrode active material was obtained. The amount of the positive electrode active material supported was 10 mg / cm. 2 More than 11mg / cm 2 The positive electrodes were adjusted to fall within the following ranges: the positive electrode made using positive electrode active material A is called positive electrode A, the positive electrode made using positive electrode active material B is called positive electrode B, the positive electrode made using positive electrode active material C is called positive electrode C, the positive electrode made using positive electrode active material D is called positive electrode D, and the positive electrode made using positive electrode active material E is called positive electrode E.
[0565] <Preparation of half-cell> A half cell was prepared using each of the positive electrodes A, B, C, D, and E prepared above, lithium metal foil, a separator, an electrolyte, a coin cell positive electrode can, and a coin cell negative electrode can. The size of the half cell was 2032 type (diameter 20 mm, thickness 3.2 mm). The positive electrodes were each circular with a diameter of 12 mm.
[0566] The electrolyte used was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 3:7, to which 1 mol / L of lithium hexafluorophosphate (LiPF6) was dissolved, to which 2 wt% vinylene carbonate (VC) was added as an additive.
[0567] As the separator, a porous polypropylene film having a thickness of 20 μm was used.
[0568] The half-cell made using positive electrode A is called cell A, the half-cell made using positive electrode B is called cell B, the half-cell made using positive electrode C is called cell C, the half-cell made using positive electrode D is called cell D, and the half-cell made using positive electrode E is called cell E. Three of each type of cell were made.
[0569] <Charge / discharge cycle test> A charge-discharge cycle test was carried out using the cells A to E prepared above. The charge-discharge cycle test was carried out under three conditions, namely, a maximum voltage during charging of 4.60 V (condition 1), 4.65 V (condition 2), and 4.70 V (condition 3).
[0570] In condition 1, the battery was charged at a constant current of 0.5C until the battery voltage reached 4.60V, and then charged at a constant voltage of 4.60V until the current fell below 0.05C (constant current-constant voltage charging). Discharge was performed at a constant current of 0.5C until the battery voltage reached 2.50V (constant current discharge). The charging and discharging environment temperature was 25°C, and the above charging and discharging were repeated 50 times. Condition 2 was the same as condition 1, except that the charging voltage was changed to 4.65V. Condition 3 was the same as condition 1, except that the charging voltage was changed to 4.70V. In this embodiment, 1C was 200mA / g per weight of the positive electrode active material.
[0571] The results of the charge-discharge cycle test are shown in Figs. 36 to 38. Figs. 36(A) and 36(B) are graphs showing the results of the charge-discharge cycle test under condition 1, Figs. 37(A) and 37(B) are graphs showing the results of the charge-discharge cycle test under condition 2, and Figs. 38(A) and 38(B) are graphs showing the results of the charge-discharge cycle test under condition 3. In Figs. 36(A), 37(A), and 38(A), the horizontal axis shows the number of repeated charge-discharge cycles (number of cycles), and the vertical axis shows the discharge capacity obtained by dividing the discharge capacity of the cell by the weight of the positive electrode active material of the positive electrode of the cell. In Figs. 36(B), 37(B), and 38(B), the horizontal axis shows the number of repeated charge-discharge cycles, and the vertical axis shows the discharge capacity in each cycle as a percentage (discharge capacity retention rate) of the maximum discharge capacity in the entire charge-discharge cycle test.
[0572] 36(A) and 36(B), the results of the charge-discharge cycle test under condition 1 (4.60 V condition) overlapped with each other and showed almost no difference between the results of cells A to E. The discharge capacity retention rate after 50 cycles of cells A to E exceeded 98%, showing excellent charge-discharge cycle characteristics.
[0573] As a result of the charge-discharge cycle test under condition 2 (4.65 V condition) shown in FIG. 37(A) and FIG. 37(B), the results of cell A and cell B overlap, and the discharge capacity retention rate after 50 cycles was the highest for cell A and cell B, the next highest for cell C, the next highest for cell D, and the lowest for cell E. Note that the discharge capacity retention rate after 50 cycles for cell A, cell B, and cell C exceeded 90%, and they showed excellent charge-discharge cycle characteristics under the condition of 4.65 V. In other words, the positive electrode active material A, positive electrode active material B, and positive electrode active material C, which were heated in a state in which they were accommodated in a setter so as to have a thickness of 3.5 mm or more and 4.0 mm or less in the preparation of the positive electrode active material, showed excellent charge-discharge cycle characteristics under the condition of 4.65 V.
[0574] As a result of the charge-discharge cycle test under condition 3 (4.70 V condition) shown in FIG. 38(A) and FIG. 38(B), the discharge capacity retention rate after 50 cycles was the highest for cell B, the next highest for cell A, the next highest for cell C, the next highest for cell D, and the lowest for cell E. Note that the discharge capacity retention rate after 50 cycles for cell A and cell B exceeded 80%, and they exhibited excellent charge-discharge cycle characteristics under the condition of 4.70 V. In other words, the positive electrode active material A and the positive electrode active material B, which were heated in a state in which they were accommodated in a setter so as to have a thickness of 1.5 mm or more and 2.0 mm or less in the preparation of the positive electrode active material, exhibited excellent charge-discharge cycle characteristics under the condition of 4.70 V.
[0575] Of the results of the charge-discharge cycle test shown in Figures 36 to 38, Figure 39(A) shows a graph comparing the maximum discharge capacity under each condition, and Figure 39(B) shows a graph comparing the discharge capacity retention rate under each condition. The values in the graphs of Figures 39(A) and 39(B) are shown in Tables 4, 5, and 6. Note that the horizontal axis of the graphs of Figures 39(A) and 39(B) lists information related to the positive electrode used in each cell (the thickness of the mixture (mixture 903 or mixture 904) in the setter when the positive electrode active material was produced).
[0576] [Table 4]
[0577] [Table 5]
[0578] [Table 6]
[0579] To repeat, as shown in Fig. 39(A), Fig. 39(B) and Table 4, in the preparation of the positive electrode active material, the positive electrode active material A, the positive electrode active material B, and the positive electrode active material C, which were heated in a state in which the mixture (903 or 904) was accommodated in a setter to a thickness of 3.5 mm or more and 4.0 mm or less, exhibited excellent charge-discharge cycle characteristics at a condition of 4.65 V. In addition, in the preparation of the positive electrode active material, the positive electrode active material A and the positive electrode active material B, which were heated in a state in which the mixture was accommodated in a setter to a thickness of 2.0 mm or less, exhibited excellent charge-discharge cycle characteristics at a condition of 4.70 V. EXAMPLES
[0580] In this example, a test battery (full cell) including a positive electrode active material, a negative electrode, and an electrolyte solution according to one embodiment of the present invention was fabricated, and a low-temperature charge-discharge test was performed. A fabrication process of the sample will be described, and the test results will be shown.
[0581] <Preparation of negative electrode> The negative electrode A used in this example will be described with reference to the fabrication method shown in FIG.
[0582] According to FIG. 16, graphite having an average particle size of 20 μm (Formula BT 1520, manufactured by Superior Graphite) was prepared as the graphite particles in this example.
[0583] According to FIG. 16, the silicon particles of this embodiment have a specific surface area of 12.7715 m2 according to the BET method. 2 Silicon particles (manufactured by Aldrich: product number 633097) with an average particle size of 100 nm were prepared. Silicon particles of 100 nm are called nanosilicon particles.
[0584] According to FIG. 16, polyacrylic acid (PPA) (10CL manufactured by FUJIFILM Wako Chemical Co., Ltd.) was used as the binder in this example.
[0585] According to FIG. 16, acetylene black (AB) was prepared as the conductive material in this example.
[0586] 16, graphite particles, silicon particles, AB, and PAA were mixed in a ratio of 72:8:6:14 (weight ratio) to prepare a mixture 404. The amount of the negative electrode active material carried was 3.66 mg / cm. 2 More than 3.85mg / cm 2 The range was adjusted as follows:
[0587] According to FIG. 16, deionized water was prepared as a solvent.
[0588] According to step S61 of FIG. 16, deionized water was added to the mixture 404 and mixed to obtain a slurry 406.
[0589] According to FIG. 16, a copper foil was prepared as a negative electrode current collector, and the above slurry was applied to the copper foil according to step S62.
[0590] The slurry was dried according to step S63 in Fig. 16 to obtain a negative electrode 408. As a preliminary drying step, the copper foil coated with the slurry was fixed to a hot plate heated to 50°C and left for 30 minutes. Then, as a main drying step, the copper foil coated with the slurry was left for 45 minutes in a ventilated dryer at 80°C.
[0591] <Preparation of full cell> A laminated full cell (cell BF1) was produced using the negative electrode A and the positive electrode B of Example 1. The positive electrode B was a single-sided coated positive electrode, with the area of the positive electrode active material layer (coated portion) being approximately 21 cm2. 2 The negative electrode A was a single-sided coated negative electrode, and the area of the negative electrode active material layer (coated part) was approximately 24 cm 2 It was decided.
[0592] As the electrolyte, LiPF6 was dissolved in a mixed solvent containing FEC and MTFP in a ratio of FEC:MTFP = 20:80 (volume ratio). Here, LiPF6 was dissolved in an amount of 1 mol / L relative to the mixed solvent of FEC and MTFP. No additives were used.
[0593] A porous polyimide film was used as the separator. Three 23 μm-thick polyimide films were stacked and placed between the positive electrode B and the negative electrode as a separator.
[0594] [Initial charge / discharge] The cell BF1 prepared above was subjected to initial charging and discharging. The method of initial charging and discharging is shown in Table 7. In the initial charging and discharging in Table 7, steps A6 and A7 were repeated three times in total. Steps A8 and A9 were repeated three times in total.
[0595] The initial charge and discharge may be called aging or conditioning. In this embodiment, 1C was set to 200 mA / g per weight of the positive electrode active material.
[0596] [Table 7]
[0597] <Low temperature charge / discharge test> A low-temperature charge-discharge test was performed using the cell BF1 prepared above. In the low-temperature charge-discharge test, the charge capacity and discharge capacity were measured in the following temperature environments: 25°C, 0°C, -10°C, -20°C, -30°C, and -40°C. The measurement results are shown in Figure 40, Figure 41, and Table 8.
[0598] Under each temperature environment, charging was performed at a constant current of 0.1 C until the voltage reached 4.50 V, followed by constant voltage charging at 4.50 V until the charging current was 0.01 C or less. Discharging was performed at a constant current of 0.1 C until the voltage reached 2.0 V (cutoff voltage). The current of 0.1 C can be said to be 20 mA / g per weight of the positive electrode active material, and the current of 0.01 C can be said to be 2 mA / g per weight of the positive electrode active material.
[0599] Fig. 40(A) is a graph showing charge curves for charging in an environment of 25° C., charging in an environment of 0° C., and charging in an environment of −10° C. Fig. 40(B) is a graph showing discharge curves for discharging in an environment of 25° C., discharging in an environment of 0° C., and discharging in an environment of −10° C.
[0600] Fig. 41(A) is a graph showing charge curves for charging in an environment of 25° C., −20° C., −30° C., and −40° C. Fig. 41(B) is a graph showing discharge curves for discharging in an environment of 25° C., −20° C., −30° C., and −40° C. The charge curve and discharge curve in the 25° C. environment are the same as those shown in Fig. 40.
[0601] In Table 8, the first column shows the temperature conditions, the second column shows the charge capacity of cell BF1, the third column shows the discharge capacity of cell BF1, the fourth column shows the charge capacity in each temperature environment as a charge capacity 25°C ratio (%) when the charge capacity at 25°C is set to 100%, and the fifth column shows the discharge capacity in each temperature environment as a discharge capacity 25°C ratio (%) when the discharge capacity at 25°C is set to 100%.
[0602] [Table 8]
[0603] As a result of charge and discharge measurements in a low-temperature environment, the cell BF1, which is a battery according to one embodiment of the present invention, obtained the following excellent results when the discharge capacity value measured during charge and discharge in a 25°C environment was taken as 100%. The discharge capacity value measured during charge and discharge in a -40°C environment was 64.7%, which was a good result exceeding 60%. The discharge capacity value measured during charge and discharge in a -30°C environment was 74.4%, which was a good result exceeding 70%. The discharge capacity value measured during charge and discharge in a -20°C environment was 85.7%, which was a good result exceeding 85%. The discharge capacity value measured during charge and discharge in a -10°C environment was 94.2%, which was a good result exceeding 90%. The discharge capacity value measured during charge and discharge in a 0°C environment was 97.4%, which was a good result exceeding 97%.
[0604] As shown in the above examples, it has become clear that by using the positive electrode active material obtained by the manufacturing method described in Embodiment 1 and the negative electrode and electrolyte solution described in Embodiment 2, excellent charging and discharging operations are possible in a temperature range of −40° C. or higher and 25° C. or lower. EXAMPLES
[0605] In this example, a battery including a positive electrode active material, a negative electrode, an electrolyte solution, and an exterior body according to one embodiment of the present invention was manufactured, and impact resistance was examined.
[0606] <Preparation of full cell> A laminated full cell (cell BF2) was produced using the positive electrode B of Example 1 and the negative electrode of Example 2. The positive electrode B was a positive electrode coated on one side, and the area of the positive electrode active material layer (coated part) was about 21 cm2. 2 The negative electrode was a single-sided coated negative electrode, with the area of the negative electrode active material layer (coated part) being approximately 24 cm 2 Eight sheets each of the positive electrode B and the negative electrode were used.
[0607] As the electrolyte, LiPF6 was dissolved in a mixed solvent containing FEC and MTFP in a ratio of FEC:MTFP = 20:80 (volume ratio). Here, LiPF6 was dissolved in an amount of 1 mol / L relative to the mixed solvent of FEC and MTFP. No additives were used.
[0608] As the separator, a porous polypropylene film was used.
[0609] A laminate was prepared by laminating the positive electrode B, the negative electrode, and the separator, and the laminate was placed inside the exterior body, and the outer periphery of the exterior body was sealed. The lamination method of the positive electrode B, the negative electrode, and the separator was performed in the same manner as described in Figures 19(A) to 19(C). In addition, the aluminum laminate film having a cross-wave shape described in Figure 23(A) was used as the exterior body.
[0610] A photograph of the appearance of the battery (cell BF2) fabricated as described above is shown in Fig. 42(A). X-ray CT images of cell BF2 are shown in Fig. 42(B) and Fig. 42(C). Fig. 42(B) is an X-ray CT image of the side of cell BF2, and Fig. 42(C) is an X-ray CT image of the top surface of cell BF2.
[0611] The cell BF2 prepared above was initially charged and discharged as shown in Table 7 of Example 2. In this example, 1C was 200 mA / g per weight of the positive electrode active material.
[0612] Next, the cell BF2 after the initial charge and discharge was charged and discharged under the following conditions to confirm the battery characteristics before the shock test. The battery was charged at a constant current of 0.2 C until the battery voltage reached 4.50 V, and then charged at a constant voltage of 4.50 V until the current fell below 0.02 C (constant current-constant voltage charge). The battery was discharged at a constant current of 0.2 C until the battery voltage reached 2.75 V (constant current discharge). The environmental temperature for charging and discharging was 25° C. The results of charging...
Claims
1. A method for producing a positive electrode active material using a setter that accommodates an object to be heated, comprising the steps of: A first step of heating lithium cobalt oxide having a median diameter of 10 μm or less at a temperature of 700° C. or more and 1000° C. or less for 1 hour or more and 5 hours or less; a second step of mixing the lithium cobalt oxide subjected to the first step with a fluorine source and a magnesium source to prepare a first mixture; a third step of heating the first mixture at a temperature of 800° C. to 1100° C. for 1 hour to 10 hours; a fourth step of mixing a nickel source and an aluminum source with the first mixture that has been subjected to the third step to prepare a second mixture; and a fifth step of heating the second mixture at a temperature of 800° C. to 950° C. for 1 hour to 5 hours, The third step is carried out in a state where the first mixture is contained in a first setter so that the thickness of the first mixture is 2.0 mm or less, The fifth step is carried out in a state where the second mixture is contained in a second setter so that the thickness of the second mixture is 2.0 mm or less, The method for producing a positive electrode active material, wherein the first step, the third step, and the fifth step are performed in an atmosphere containing oxygen.
2. In claim 1, the number of magnesium atoms in the magnesium source is 0.3% or more and 3% or less of the number of cobalt atoms in the lithium cobalt oxide that has been subjected to the first step.
3. In claim 2, the number of nickel atoms in the nickel source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide that has been subjected to the first step.
4. In claim 3, the number of aluminum atoms in the aluminum source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide that has been subjected to the first step.
5. A method for producing a lithium ion battery including a positive electrode, an electrolyte, a negative electrode, a separator, and an exterior body, comprising the steps of: a step of dispersing the positive electrode active material produced by the method according to any one of claims 1 to 4, a conductive material, and polyvinylidene fluoride in an organic solvent to produce a positive electrode slurry, and applying the positive electrode slurry onto a positive electrode current collector and drying the positive electrode, a step of dispersing graphite particles, silicon particles, and polyacrylic acid in water to prepare a negative electrode slurry, applying the negative electrode slurry onto a negative electrode current collector, and drying the negative electrode; preparing the electrolyte solution by mixing a lithium salt, a fluorinated cyclic carbonate, and a fluorinated chain carbonate; The positive electrode and the negative electrode are stacked with the separator interposed therebetween to prepare a laminate; The laminate and the electrolyte are contained inside the exterior body.
6. In claim 5, The lithium salt is LiPF 6 having The fluorinated cyclic carbonate comprises fluoroethylene carbonate; The method for producing a lithium ion battery, wherein the fluorinated chain carbonate has methyl trifluoropropionate.
Citation Information
Patent Citations
Nonaqueous solvent, nonaqueous electrolyte, and power storage device
JP2015026608A
Electrode and battery
JP2019165005A
Positive electrode active material and method for producing positive electrode active material
WO2020026078A1